On Misunderstanding the Second Contradiction Thesis - Rudy, Alan P. (Capitalism, Nature, Socialism, 2019)
James O'Connor's "second contradiction" thesis is widely misunderstood as an ecological crisis theory. Most of the criticisms of the theory derive from this misreading, including those which ignore relations between ecological, personal and communal conditions and those which see the "first" and "second" contradictions as materially distinct. O'Connor himself is partially responsible for the misreading, however. His writings tended to put the ecological out front, and his use of Polanyi's romantic idea of "fictitious commodities" reinforced that tendency. The defense developed here rejects ecologistic readings, ties the second contradiction thesis backwards and forwards in O'Connor's work, unpacks the meaning of "conditions" for Marx and O'Connor, and suggests that Neil Smith's argument that capitalist second natural relations generate qualitatively new processes by which nature, human nature and space are produced would have served O'Connor better.
Keywords: MARX, Karl, 1818-1883; O'CONNOR, James; POLANYI, Karl, 1886-1964; SMITH, Neil; conditions of production; contradiction; ecological Marxism; ecologism; environmental marxism; human behavior; second contradiction

Karl Polanyi, the "always-embedded market economy," and the re-writing of The Great Transformation - Lacher, Hannes (Theory & Society, 2019)
This article seeks to subject Fred Block and Margaret Somers' influential reconstruction of Karl Polanyi's The Great Transformation to a systematic review. I show that Block & Somers's central claim—that Polanyi's thinking underwent a "theoretical shift" as he wrote his seminal book—is not supported by archival evidence. I demonstrate that all the narrative keys that Block & Somers advance to lend plausibility to their discovery of a "theory of the always-embedded market economy" in The Great Transformation, wither under critical probing. While this article does not advance a comprehensive alternative reconstruction of Polanyi's main work, the essential continuities it uncovers in his social thought suggest that Polanyi's book is best understood as the culmination of his long-standing efforts to rebuild a radically transformative socialism on non-Marxist foundations. The recognition that Polanyi's political purposes extend far beyond regulated capitalism or social-democracy, I conclude, makes it possible—and indeed necessary—to read The Great Transformation as an internally coherent work of social theory.
Keywords: BLOCK, Fred L.; SOMERS, Margaret R.; capitalism and socialism; critical institutionalism; economic sociology; fascism; neo-Polanyian social theory; political economy

Networked but Commodified: The (Dis)Embeddedness of Digital Labour in the Gig Economy - Wood, Alex J; Graham, Mark; Lehdonvirta, Vili; Hjorth, Isis (Sociology, 2019)
This article investigates the (dis)embeddedness of digital labour within the remote gig economy. We use interview and survey data to highlight how platform workers in Southeast Asia and Sub-Saharan Africa are normatively disembedded from social protections through a process of commodification. Normative disembeddedness leaves workers exposed to the vagaries of the external labour market due to an absence of labour regulations and rights. It also endangers social reproduction by limiting access to healthcare and requiring workers to engage in significant unpaid 'work-for-labour'. However, we show that these workers are also simultaneously embedded within interpersonal networks of trust, which enable the work to be completed despite the low-trust nature of the gig economy. In bringing together the concepts of normative and network embeddedness, we reconnect the two sides of Polanyi's thinking and demonstrate the value of an integrated understanding of Polanyi's approach to embeddedness for understanding contemporary economic transformations.
Keywords: commodification; digital labour; disembeddedness; embeddedness; freelancing; gig economy; outsourcing

Knowledge and social freedom - Rief, Silvia (Journal of Cultural Economy, 2019)
Keywords: Karl Polanyi's Vision of a Socialist Transformation (Book); book review; commentary; freedom

Ethnoracial Populism: An Alternative to Neoliberal Globalization? - Antonio, Robert J. (Social Epistemology, 2019)
Worldwide emergence of strongmen leaderships and eroded or failed democracies suggest that the era of unchallenged neoliberal hegemony may be winding down and that alternatives are rising. The presidential election of Donald Trump has inspired rightwing populists at home and abroad. This paper will analyze the Trumpist fusion of authoritarian ethnoracial nationalism with neoliberal adventure capitalism and the broader matter of how neoliberal de-democratization opens way for right-wing populism and illiberal capitalism. The topics will be explored in part through discussions of earlier theories of Friedrich Hayek, Carl Schmitt, John Dewey, and Karl Polanyi that have been revived and deployed in the current debates over neoliberalism, populism, and democracy.
Keywords: HAYEK, Friedrich A. von (Friedrich August), 1899-1992; POLANYI, Karl, 1886-1964; Presidential elections; SCHMITT, Carl, 1888-1985; Trumpism; de-democratization; ethnoracial populism; globalization; nationalism; neoliberalism; populism; right-wing populism

Karl Polanyi and the Law of Market Society - Frerichs, Sabine (Österreichische Zeitschrift für Soziologie, 2019)
Karl Polanyi started his career as a doctor of law and practiced law for a while; but he did not become a legal scholar. As an economic historian, anthropologist, or sociologist, he was concerned with the relation of economy and society. But even though law is an important factor in mediating this relationship, Polanyi gave little attention to the law as such. As part of an endeavour to advance a ‘Polanyian’ economic sociology of law, this article develops the ‘law of market society’ as an analytical category. For this purpose, three argumentative strategies are combined. First, the article draws on The Great Transformation to reconstruct the role of law in the processes of commodification and decommodification. Second, it turns to Marxist scholarship to explore the conceptual link between law and economics and to ponder to what extent law itself can become a commodity. Third, it links Polanyi’s approach with American institutionalism, and Commons’ work in particular, to show how the evolution of the ‘law of market society’ can also be understood as a collective enterprise which continuously evolves. It is argued that these perspectives complement each other and help to bring the law back in where it is missing.
Keywords: law of market society; sociology of law

Historicizing Karl Polanyi - Gräser, Marcus (Österreichische Zeitschrift für Soziologie, 2019)
Karl Polanyi’s book The Great Transformation has found great resonance in the social sciences in recent years—especially in sociology, political economy and political science. The interest in Polanyi among historians is still modest in comparison. There are not enough studies that treat Polanyi as an object of intellectual history/history of science, nor has Polanyi been used hitherto as an idea-giver for the growing field of global history—despite the fact that his book can be understood as global history. It is high time to “historicize” Polanyi in several ways.
Keywords: history of science; intellectual history

Commodity Studies with Polanyi: Disembedding and Re-Embedding Labour and Land in Contemporary Capitalism - Langthaler, Ernst; Schüßler, Elke (Österreichische Zeitschrift für Soziologie, 2019)
This article aims to inform current debates in the field of transnational commodity studies through a Polanyian lens. Polanyi reminds us of the need to pay attention to the “double movements” in which fictitious commodities are disembedded from and re-embedded in society. We focus on two fictitious commodities, labour and land, which are conventionally treated as mere inputs for the production of genuine commodities. Through investigating the disembedding and re-embedding of labour in the garment industry, and of land in the agro-food sector since the 1970s, we gain insights regarding the commodification of fictitious commodities in the context of transnational commodity chains. The developments in both fields imply not just simple double movements, but complex entanglements of disembedding and re-embedding dynamics at the interface of state, business and civil society actors.
Keywords: commodity studies; double movement

Doing justice to Karl Polanyi - Devine, Pat (Capitalism, Nature, Socialism, 2019)
Keywords: POLANYI, Karl, 1886-1964; book review; economic activity; economics; social control; social forces

Absolute Capitalism - Foster, John Bellamy (Monthly Review: An Independent Socialist Magazine, 2019)
The article deals with the emergence of absolute capitalism due to the efforts of states to promote social reproduction. It explores the association between absolute capitalism and neoliberalism, a ruling-class political-ideological project that is connected to the rise of monopoly-finance capital. Some 20th century thinkers had their own ideas about absolute capitalism, including Karl Polanyi and John Maynard Keynes.
Keywords: KEYNES, John Maynard, 1883-1946; POLANYI, Karl, 1886-1964; capitalism; finance capitalism; neoliberalism; social reproduction

The future of capitalism: Trends, scenarios and prospects for the future - Delanty, Gerard (Journal of Classical Sociology, 2019)
The article provides a framework for thinking about how the question of the future of capitalism might be addressed. One of the problems resides in the very definition of capitalism and of what its defining features consist of and whether we should be talking about 'capitalist society' or the 'capitalist economy' or some kind of post-capitalist condition. Following Polanyi, Castoriadis and Habermas, it is argued that capitalism and democracy together constitute the defining dynamics of modernity and that the resulting tensions will provide momentum for the main circuits of potential change. Five scenarios for looking at the future are discussed. These will form the main substance of the article: varieties of capitalism, systemic crises of capitalism, catastrophic collapse, low growth capitalism and post-capitalism. In conclusion, it is argued that there are various possibilities that can be understood in terms of transitions, breakdown or transformation, but a likely future trend will be less the end of capitalism than the harnessing of 'super-capitalism' and that there are limits to the accumulation of capital.
Keywords: MARX, Karl, 1818-1883; POLANYI, Karl, 1886-1964; SCHUMPETER, Joseph Alois, 1883-1950; WEBER, Max, 1864-1920; capital; capitalism; democracy; future of capitalism; modernity; neoliberalism; varieties of capitalism

Climate Change and the Polanyian Counter-movement: Carbon Markets or Degrowth? - Stuart, Diana; Gunderson, Ryan; Petersen, Brian (New Political Economy, 2019)
In the midst of a wave of market expansion, carbon markets have been proposed as the best way to address global climate change. While some argue that carbon markets represent a modern example of a Polanyian counter-movement to the environmental crisis, we adopt a structural interpretation of Polanyi to refute this claim. Carbon markets represent a further expansion of markets that fails to address the underlying contradictions related to the commodification of nature. In addition, they increase risks to society and the domination of economic elites. While carbon markets further subject social and ecological relations to market mechanisms, we examine degrowth as a possible response to climate change that prioritises social and environmental goals over economic growth. While degrowth continues to be dismissed as impractical or impossible, a growing number of scholars, scientists and activists argue it is the only way to address global climate change. In contrast to carbon markets, we argue degrowth could represent a genuine Polanyian counter-movement in response to climate change. In addition, degrowth could help all those disenfranchised by market fundamentalism by addressing the triple crises related to the commodification of land, labour and money.
Keywords: carbon markets; carbon offsetting; climate; climate change; degrowth; economic development; economic elites; emissions (air pollution); environment; environmental studies

Capitalism in Transformation: Movements and Countermovements in the 21st Century - Atzmüller, Roland; Aulenbacher, Brigitte; Brand, Ulrich; Décieux, Fabienne; Fischer, Karin; Sauer, Birgit (Edward Elgar Publishing, 2019)
Presenting a profound and far-reaching analysis of economic, ecological, social, cultural and political developments of contemporary capitalism, this book draws on the work of Karl Polanyi, and re-reads it for our times. The renowned authors offer key insights to current changes in the relations between the economy, politics and society, and their ecological and social effects.
Keywords: biography; capitalism; countermovement; fictitious commodities

Tensions in the Triangle: Monetary Plurality between Institutional Integration, Competition and Complementarity - Blanc, Jerome (Evolutionary and Institutional Economics Review, 2018)
This text aims at accounting for the plurality of money by emphasizing the delicate and evolving balance of the legal monetary systems and the continued existence of moneys that stay outside, though their continuation is subjected to chronic difficulties. It uses Polanyian concepts to take the wide and increasing variety of money into account and mobilizes criteria able to analyse the variety of links between them. It proposes a framework based on the representation of a "plurality triangle" with institutional integration, complementarity and competition, and it analyses the positioning of moneys in this framework as well as tensions that may generate shifts in their positioning.
Keywords: current heterodox approaches: historical; evolutionary; institutional; monetary systems; money

‘Our world was made by nature’: constructions of spontaneous order - Dale, Gareth (Globalizations, 2018)
This article explores the concepts of spontaneity and spontaneous order, in particular their deployment by Friedrich Hayek and Karl Polanyi. Although in many respects these thinkers were poles apart, the article identifies a point of convergence. They both mobilize the concept of spontaneity in a manner that naturalizes a particular social process: for Hayek, the market economy, for Polanyi, society’s protective movement that arises in reaction against the market economy. To contextualize the uses of spontaneity by Hayek and Polanyi, I trace its evolution, with reference to Leibniz, Mandeville, and the thinkers of the Scottish Enlightenment. Having sketched the ways in which earlier thinkers understood spontaneity, I turn finally to Hayek and Polanyi. I argue that their invocations of spontaneity and spontaneous order contribute to a downplaying of relations of domination and exploitation. While Hayek sees the market system as the exemplar of spontaneous order, for Polanyi, the concept of spontaneity underpins his belief that the protective countermovement is a ‘natural’ reaction to the evils of market society; as such, power relations pass beneath the radar.
Keywords: HAYEK, Friedrich A. von (Friedrich August), 1899-1992; HAYEK, Salma, 1968-; POLANYI, Michael, 1891-1976; social order; socialism; spontaneity; spontaneity (philosophy); spontaneous order

"Race" and the upsurge of antagonistic popular movements in Sweden - Schierup, Carl-Ulrik; Ålund, Aleksandra; Neergaard, Anders (Ethnic & Racial Studies, 2018)
Across a crisis-stricken Europe battles rage for post-neoliberal hegemony, with "race" and "austerity" as central signifiers. One of the places where the frontlines are most pregnant is Sweden; long perceived as a role model for its welfare state, cultural equity and social equality. Sweden is, however, facing social conflicts following in the tracks of a deep transformation in terms of welfare cuts, racialization and growing social polarization, targeting in particular a disadvantaged migrant and post-migrant population. On that background, the paper focuses on the upsurge of mutually antagonistic popular movements - "racist" and "anti-racist". We use Sweden as an exemplary case of Europe's present Polanyian moment, reminiscent of the 1930s. Yet, current upheavals expound, the authors claim, a different configuration of crisis and racism as well as a dissimilar utopia for the imagineering of nation and community.
Keywords: Europe; Sweden; ethnic studies; hostility; immigration opponents; migration; neoliberalism; new right (politics); populism; race; racism; social class; social movements; sociology

Globalization and Business Regulation - Djelic, Marie-Laure; Quack, Sigrid (Annual Review of Sociology, 2018)
In the twenty-first century, global business regulation has come of age. In this article, we review the literature on globalization and business regulation from the angle of transnational governance, a recently evolving interdisciplinary field of research. Despite the multiplicity and plurality of regulatory platforms and products that have emerged over time, we identify common patterns of field structuration and parallel trajectories. We argue that a major trend, both in practice and in scholarly work, is a move away from an idealized convergence around a set of unified global rules; instead, our conceptualizations and our practices of transnational business regulation increasingly demonstrate a concern for the adaptability of transnational rules to resilient and resistant contextual specificities. Another important trend, both in practice and in scholarly fields, is a growing focus on the complex dynamics between rule making on the one hand and rule implementation and monitoring on the other.
Keywords: POLANYI, Karl, 1886-1964; business regulation; globalization; governance; market ideology; neoliberalism; soft law; transnational; value chains

The economic shift and beyond: Care as a contested terrain in contemporary capitalism - Aulenbacher, Brigitte; Décieux, Fabienne; Riegraf, Birgit (Current Sociology, 2018)
This article argues that we are witnessing a fundamental transformation of capitalism. Under the auspices of an economic shift, social reproduction and constituent care and care work are undergoing a process of reorganization. The first part draws on Karl Polanyi’s analysis of the relation between market and society and on contemporary revisions of his approach. Referring to core arguments from his perspective on the market society it identifies processes of commodification, marketization and quasi-marketization, which we can understand as an economic shift driving the development in the field of care and care work. The second part refers to empirical studies in Austria and Germany and reflects in terms of a Polanyian double movement on how far care and care work – in the case of elder and child care and, more precisely, home care agencies, residential care communities and the social investment state – have become a contested terrain. The third part, the conclusion, points out how tendencies like the economic shift touch care and care work.
Keywords: Giro económico; Virage économique; agence de soins à domicile; agencias de atención a domicilio; atención a los mayores y la infancia; capitalism; care work; communautés de soin; comunidades de atención; corporate reorganizations; doble movimiento; double movement; doublé mouvement; economic shift; elder and child care; home care agencies; inversión social; investissement social; reproducción social; reproduction sociale; residential care communities and social investment; social reproduction; social services; socioeconomics; soin aux personnes âgées et à l’enfance

Reconstructing Polanyi? - Levien, Michael (Development & Change, 2018)
Most people read Karl Polanyi today because his critique of laissez faire capitalism seems remarkably applicable to our neoliberal times. Although his late work on ancient and ‘archaic’ economies has enjoyed a consistent specialist readership, Polanyi is best known today for his 1944 magnum opus, The Great Transformation (henceforth GT). Covering a large sweep of mostly European history, the GT seeks to show that the attempt to create a ‘self-regulating market’ was a radical and recent departure from all preexisting economies; that this effort to ‘disembed’ the market from society required a great deal of state planning and force; and that the commodification of the ‘fictitious commodities’ land, labour and money was so socially destructive that it generated countermovements that demanded, and in some measure achieved, social protection. Polanyi termed this whole cycle of disembedding and re-embedding the market the ‘double movement’, and tried to show that it was the underlying cause of the great depression, fascism and two world wars. Given the relentless march of commodification in the neoliberal period and the variety of political responses this has generated (from both the left and far right), many people have been drawn to the idea that we are living through another double movement.
Keywords: DALE, Gareth; POLANYI, Karl, 1886-1964; Reconstructing Polanyi: Excavation & Critique (Book); book review; double movement; nonfiction

Capitalism goes care: Elder and child care between market, state, profession, and family and questions of justice and inequality - Aulenbacher, Brigitte; Décieux, Fabienne; Riegraf, Birgit (Equality, Diversity & Inclusion, 2018)
The starting point of the paper is the meteoric rise of care and care work upon the societal and sociological agenda. Referring to Polanyi, the authors argue that this is the manifestation of a new phase of capitalist societalisation (Vergesellschaftung) of social reproduction in the form of an economic shift. The purpose of this paper is to discuss the societal organisation of care and care work and questions of inequality and justice.Design/methodology/approach The first part of the paper illustrates some facets of the economic shift in the field of care and care work. The second part reconstructs the societal organisation of care and care work in the private sector, state, third sector and private households from the mid-twentieth century in the context of questions of inequality and justice. The third part draws on the institutional logics perspective and French pragmatic sociology and the own case studies on home care agencies (HCA), residential care communities (RCC) and early child care (ECC) in Austria and Germany and shows how conflicting demands give rise to new questions of justice. The paper ends with a short conclusion.Findings The paper shows how the commodification and de-commodification of care and care work have changed over time and how the economic shift – illustrated in the case of HCA, RCC and ECC – is accompanied by conflicting demands and questions of justice.Originality/value A Polanyian perspective on the relation between market and society is combined with the neo-institutionalist and pragmatic idea that orientations rooted in the “logics” of the market, the state, the family and the profession influence how conflicting demands in elder and child care are dealt with and how questions of inequality and justice arise.
Keywords: capitalism; care work; caring communities and social investment; community health services; countermovement; decommodification; economic systems; elder and child care; home care agencies; home care services; social justice; social reproduction

Beyond Double Movement and Re-regulation: Polanyi, the Organized Denial of Money Politics, and the Promise of Democratization - Feinig, Jakob (Sociological Theory, 2018)
Although Karl Polanyi is best known for his theorization of market regulation and the double movement, democratizing the economic was one of his core concerns. He believed societies need to bring labor, land, and money under collective oversight to displace the logic of market fundamentalism with the logic of human needs. In this article, the author draws on Polanyi’s vocabulary to shed light on the denial of money politics and the possibility of democratization. The author illustrates these dynamics through an analysis of long-term dynamics of (de)politicization in British colonial America and the United States through the 1930s. The author developed this approach hoping that it can contribute to nudging public debates beyond regulation and monetary policy techniques and toward popular involvement and knowledge.
Keywords: Polanyi; democratization; depoliticization; double movement; gold standard; money; social theory; sociology

Discursive Synergies for a ‘Great Transformation’ Towards Sustainability: Pragmatic Contributions to a Necessary Dialogue Between Human Development, Degrowth, and Buen Vivir - Beling, Adrián E.; Vanhulst, Julien; Demaria, Federico; Rabi, Violeta; Carballo, Ana E.; Pelenc, Jérôme (Ecological Economics, 2018)
There is a growing awareness that a whole-societal “Great Transformation” of Polanyian scale is needed to bring global developmental trajectories in line with ecological imperatives. The mainstream Sustainable Development discourse, however, insists in upholding the myth of compatibility of current growth-based trajectories with biophysical planetary boundaries. This article explores potentially fertile complementarities among trendy discourses challenging conventional notions of (un)sustainable development – Human Development, Degrowth, and Buen Vivir – and outlines pathways for their realization. Human Development presents relative transformative strengths in political terms, while Degrowth holds keys to unlocking unsustainable material-structural entrenchments of contemporary socio-economic arrangements, and Buen Vivir offers a space of cultural alterity and critique of the Euro-Atlantic cultural constellation. The weaknesses or blind spots (‘Achilles heels’) of each discourse can be compensated through the strengths of the other ones, creating a dialogical virtuous circle that would open pathways towards a global new “Great Transformation”. As one of the main existing platforms for pluralist and strong-sustainability discussions, Ecological Economics is in a privileged position to deliberately foster such strategic discursive dialogue. A pathway towards such dialogue is illuminated through a model identifying and articulating key discursive docking points.
Keywords: biophysics; degrowth; ecosystem services; environemntal economics; post-development; pragmatics; socio-ecological transition; strategic dialogue; sustainable development; transformation discourses

The agrifood question and rural development dynamics in Brazil and China: towards a protective ‘countermovement’ - Escher, Fabiano; Schneider, Sergio; Ye, Jingzhong (Globalizations, 2018)
This paper explores some features of the development paths taken by Brazil and China (two member countries of the BRICS grouping) in the current context of the crisis of neoliberal globalization and transformation of the political and economic world order. The authors use Polanyi’s ‘double movement’ thesis to argue that newly emerging rural development (RD) dynamics in China and Brazil are part of a protective ‘countermovement’, driven by actors and institutions responding to the contradictions of the concentration and internationalization of agrifood systems. However, thedirectionand scope of these countermovements are still open; their transformative potential should be viewed in Gramsci’s terms as a struggle for hegemony the outcome of which depends on the concrete ‘balance of social forces’. First, the paper characterizes the impacts of China’s rise on Brazil’s development, which subsequently found its economy under threat of reprimarization and deindustrialization. The paper then sketches some stylized facts of production and consumption within the Brazil–China soy–meat complex, a key element of the current global food regime, with a focus on corporate control of the soy–meat value chain, and its negative consequences. Finally, the paper identifies the key roles that actors and institutions linked to peasants and family farmers are playing in the RD dynamics of each country. Although China and Brazil represent two very different realities, the comparison shows that critical rural and agrifood issues are indeed moving onto the centre stage of the contemporary ‘double movement’.
Keywords: Brazil; Brazil–China soy–meat complex; China; deindustrialization; double movement; farming practices; food industry; globalization; production–consumption relations; rural development; rural policies

Polanyi's Economic Embeddedness, Countermovement, and Republican Political Economy - Escandell, Bru Laín (Ethics, Politics & Society, 2018)
The aim of this article is to contend that Karl Polanyi's work bears significant coincidences with the republican tradition of thought. The first of them is one of a methodological or epistemological kind, and it consists of the use of a very
Keywords: countermovement; embeddedness; political economy; political economy and history; political philosophy; republicanism

Reconfiguring the social and solidarity economy in a Danish/Nordic welfare context - Hulgård, Lars; Andersen, Linda Lundgaard (3rd EMES-Polanyi International Seminar. Welfare societies in transition. Polanyi revisited through the lens of welfare state, social democracy and solidarity economy, 2018)
When looking at definitions and understandings of the social and solidarity economy, one issue stands out as particularly significant. The issue of how it links to organizational (micro and meso level dimensions) and societal specificities. Whereas social enterprise also in the EMES ideal typical version (Borzaga & Defourny, 2001) is only indirectly linked to a Polanyian framework (Gardin, 2006), the notion of solidarity economy can hardly be understood at an elaborate level without reference to the Polanyian framework of plurality. Accordingly, in this paper we will first highlight the difference between adopting a social economy and a solidarity economy approach to social enterprise and social entrepreneurship. Within the framework of a social economy perspective, social enterprise is first defined through a set of organizational criteria leaving the relation to the broader and deeper issues of economy and democracy open. As a contrast to this, solidar-ity economy links the organizational dimension of a particular social enterprise to the broader political and economic framework of the particular society (Laville, 2010: 230 ff.). Secondly, we will present and discuss two specific social enterprises that both re-flects the diversity of social enterprise and social entrepreneurial initiatives in a Danish welfare context and provide important insights for developing theories on solidarity economy. The two initiatives differ in shape, space/geography and organizational struc-ture but are important examples of pluralism in a Danish welfare context (Andersen, 2015). Roskilde Festival and Skovgård Hotel share a number of features that place them as interesting agents of solidarity economy. They both display a differentiated activity portfolio of business; public and civil character and they display a differentiated profile of reciprocity, redistribution and democracy that place them as influential in local, regional and national/international contexts. Finally, in the concluding section we discuss how an analysis based upon solidari-ty economy differ from one based solely upon a social economy perspective, and second-ly some future perspectives for the continued evolution of the Danish/Scandinavian wel-fare model.
Keywords: Denmark; plurality; social economy; social enterprise; social entrepreneurship; solidarity economy

The social aftermath of economic disaster: Karl Polanyi, counter-movements in action, and the Greek crisis - Kentikelenis, Alexander E. (Socio-Economic Review, 2018)
The economic crisis in Greece resulted in high unemployment and the dismantlement of social protection policies. How does society respond to the collapse of both welfare-state and market mechanisms? I examine these issues through the study of one working class community in Athens over 2012-13. Since the onset of the crisis, my informants experienced a simultaneous drop in living standards, loss of social status, and debasement of their symbolic construction of reality. To respond to these pressures, they relied on a combination of material survival strategies, the reconfiguration of social resources, and the reconstruction of cultural imaginaries. To explain these findings, the article draws on Karl Polanyi's analysis of countermovements to marketization and commodification. I argue in favour of augmenting the definition of countermovements to capture local-level responses, emphasising cultural aspects of social protection, and tracing the micro-foundations of countermovements that are nonetheless shaped by the macro-institutional context shaping action. This reading of Polanyi's work seeks to integrate many moving--and potentially contradictory--parts into a holistic analysis of societal responses to rapid and radical socioeconomic change.
Keywords: Greece; capitalist systems: political economy; countermovement; economic crisis (2008); financial crises; history of economic thought: individuals; national government expenditures and welfare programs

Pop-up Polanyi: Cultural entrepreneurs and the ‘vacancy fix’ - Scott, Michael; Szili, Gerti (City, Culture and Society, 2017)
Gentrification as an urban strategy pivots upon the dual mediation of the city as a site for aesthetic consumption and pleasure, and as a space of potential ground rent. The recent rise of urban regeneration programs that assist small scale cultural entrepreneurs into disused commercial property – ‘pop-up shops’ – is one example of the convergence of the urban cultural economy and gentrification. This article presents a preliminary explanation of the function of such urban programs through Karl Polanyi's socioeconomic concepts and the case of Renew Adelaide. It is argued that Renew aligns and then stabilises different Polanyian modes of economic integration (reciprocity, redistribution, and exchange), while inducing a partial and temporary de-commodification of urban space. This approach outlines how ‘pop-up’ programs contain multiple objectives. First, they induce the images of creative city vibrancy that can be folded into contemporary place marketing. Second, they enable celebrated entrepreneurial subjectivities to be performed. Third, they illustrate how ‘vacancy fixes’ are addressed via small-scale cultural projects supporting land banking for the owners of properties whose rent gaps have yet to be closed. This Polanyian approach explains how the modes of integration undergirding these programs are assembled via an orientation to the real or symbolic processes of gentrification.
Keywords: creative cities; cultural entrepreneurs; gentrification; modes of economic integration; pop-up; rent gap

'Playing on the break': Karl Polanyi and the double-movement 'Against Modern Football' - Webber, David M (International Review for the Sociology of Sport, 2017)
While the popularity of English football increases worldwide, there has been a marked rise in the discontent expressed by a small but growing group of domestic fans. This dissent has led to the emergence of a movement broadly defined as being 'Against Modern Football' (AMF), a banner under which fans of rival clubs have gathered in an attempt to challenge the poor governance, commercialism and greed that has come to dominate the English game. This article offers a conceptualisation of what it means to be 'against modern football' based upon Karl Polanyi's analysis of the market society. Developing the dialectic of the 'double-movement' that appears in Polanyi's most famous work, The Great Transformation, this article demonstrates how these governing principles might be useful in explaining both the complex cultural political economy of English football and the possibilities that exist for the AMF movement to socially re-embed the modern game.
Keywords: English football; athletic clubs; cultural political economy; soccer; sociology of sport; sports - social aspects; sports spectators; supporters

Polanyi for the Age of Trump - Krippner, Greta R. (Critical Historical Studies, 2017)
It is no exaggeration to say that Fred Block and Margaret Somers are almost singlehandedly responsible for reviving interest in Karl Polanyi’s intellectual and political legacy in American sociology. Their contribution has consisted not only in reminding sociologists of the power of Polanyi’s analysis of the rise of market society to make sense of our troubled times but even more importantly in resolving many of the difficult theoretical tangles that Polanyi gets himself into in the course of developing this analysis. Now their various essays, written over three decades, have been revised for publication in a single volume, supplemented with several new essays that introduce novel themes and also attempt to apply Polanyi’s conceptual apparatus to current social and political problems. 1 As a compilation of essays, the resulting volume defies easy summary—and I won’t attempt to offer a full treatment of the many important …
Keywords: United States; capitalism; economic policy; free enterprise; historical sociology; market ideology

Karl Polanyi in an Age of Uncertainty - Block, Fred; Somers, Margaret R. (Contemporary Sociology, 2017)
Keywords: DALE, Gareth; For a New West: Essays 1919-1958 (Book); Karl Polanyi: A Life on the Left (Book); POLANYI, Karl, 1886-1964; book review; nonfiction; socialism

Free market ideology and deregulation in Colorado’s oil fields: Evidence for triple movement activism? - Malin, Stephanie A.; Mayer, Adam; Shreeve, Kelly; Olson-Hazboun, Shawn K.; Adgate, John (Environmental Politics, 2017)
Unconventional oil and gas extraction (UOGE) has spurred an unprecedented boom in onshore production in the US. Despite a surge in related research, a void exists regarding inquiries into policy outcomes and perceptions. To address this, support for federal regulatory exemptions for UOGE is examined using survey data collected in 2015 from two Northern Colorado communities. Current regulatory exemptions for UOGE can be understood as components of broader societal processes of neoliberalization. Free market ideology increases public support for federal regulatory exemptions for UOGE. Perceived negative impacts do not necessarily drive people to support increased federal regulation. Utilizing neo-Polanyian theory, interaction between free market ideology and perceived negative impacts is explored. Free market ideology appears to moderate people’s views of regulation:increasingthe effect of perceived negative impacts while simultaneously increasing support forderegulation. To conclude, the ways in which free market ideology might normalize the impacts of UOGE activity are discussed.
Keywords: Colorado; deregulation - government policy; double movement; environmental sociology; fracking; free enterprise; free markets; gas extraction; hydraulic fracturing; market ideology; neoliberalism; oil fields; public support; triple movement; unconventional oil and gas production

Fixing network failures? The contested case of the American Manufacturing Extension Partnership - Brandt, Philipp; Whitford, Josh (Socio-Economic Review, 2017)
The article uses a case study of the American Manufacturing Extension Partnership to explore economic and industrial policy in the contemporary USA. Extensive quantitative and qualitative data are mobilized to show that: (a) the agency is pressured politically to limit its activities to 'blunt' remedies for identifiable 'market failures'; even as (b) regional centers in fact often orient also, and sometimes instead, toward 'coordination-oriented' policies to mitigate 'network failures'; and (c) these latter generate better results, on average, for client manufacturers. The findings challenge neo-institutional claims that economic policies are most effective only when complementary to the dominant institutional coordinating capacities embedded in the existing American political economy, or when they have the exceptional support of the American security establishment. They are, however, consistent with an alternative neo-Polanyian approach that explains when and how streetlevel policymakers dispersed across American federalism sometimes sidestep the ideological hegemony of 'market fundamentalism'.
Keywords: United States; economic policy; embeddedness; industrial organization; industrial policy; institutional complementarity; manufactures; market failure; market fundamentalism; partnership (business); public policy; regional economies

The four modes of coexistence in social systems - Nechansky, Helmut (Kybernetes, 2017)
Purpose The paper aims to relate the four modes of coexistence of goal-orientated systems – conflict, hierarchy, the niche and cooperation – to static behavioral descriptions of social systems.Design/methodology/approach Analyzing the options for interactions of goal-orientated systems leads the four modes of coexistence. These show certain behavioral characteristics. Searching for these characteristics in selected behavioral descriptions in organizational theory, sociology, political science and system science allows relating them to certain modes.Findings In organizations, the four modes of coexistence show in general (Cameron and Quinn) and dyadic interaction patterns (Argyris). In sociology, they show in educational schemes preparing for specific modes (Bernstein) and in different exchange patterns (Polanyi). In political theory, the four modes of coexistence show in preferred policies of parties, in institutional development, in oligarch power politics (Winters) and in external policy. In system science, they show in problem solving strategies (Jackson) and “mindscapes” (Murayama).Research limitations/implications The analysis is restricted to static patterns leaving out dynamic developments, for example, in networks.Practical implications Together with previous investigations, the paper shows how behavioral descriptions ranging from psychology to politics correspond to the four modes of coexistence, and it suggests interrelations and alignments of the modes via various levels of societal organization.Originality/value The four modes of coexistence provide an unequivocal theoretical framework that allows finding parallels in behavioral descriptions ranging from psychology via sociology to politics.
Keywords: business planning; cybernetics; decision making; decision-making; forms of integration; industrial organization (economic theory); interaction; politics; redistribution; sociology; systems theory

‘Hipster Capitalism’ in the Age of Austerity? Polanyi Meets Bourdieu’s New Petite Bourgeoisie - Scott, Michael (Cultural Sociology, 2017)
This article dialogues Polanyi and Bourdieu to propose a new research agenda within the sociology of cultural production. Extending recent literature on hipsters, this iconic figure is shifted from the world of consumption to the world of production via Bourdieu’s conceptualisation of the new petite bourgeoisie. Using secondary empirical material of cultural micro-enterprises, two ideal-typical career strategies are sketched: cultural-capital oriented seeking to secure positions within established creative industries, and economic-capital orientated stylising ‘old’ petite bourgeoisie occupations to access economic returns. However, within the context of ongoing austerity policies, Bourdieu’s economic capital does not fully account for the variegated forms of material resources these nascent enterprises draw on. Bringing Polanyi’s modes of economic integration – reciprocity, redistribution and exchange – to Bourdieu opens new questions on how hipster capitalism is the practice of intermediating between these ‘backstage’ material modes and the ‘frontstage’ selling of style.
Keywords: BOURDIEU, Pierre, 1930-2002; austerity; capitalism; cultural capital; cultural production; cultural sociology; hipster; hipsters (subculture); micro-enterprise; modes of economic integration; new cultural economy; new petite bourgeoisie

Karl Polanyi on the Rise of Fascism and Market Economy - Komlik, Oleg (Economic Sociology and Political Economy, 2017)
A spectre is haunting Europe and the world — the spectre of Fascism (veiled as defensive democracy and common-sense patriotism) and authoritarian neoliberalism (disguised as social protectionism an…
Keywords: economic sociology; fascism

The State in Classical Laissez-Faire, Its Crisis, and the Establishment of Fordism - Bonanno, Alessandro (The Legitimation Crisis of Neoliberalism, 2017)
This chapter stresses the point that contrary to arguments proposed by neoliberals, the state has consistently been a relevant actor in the organization of the economy and society. It indicates that the role played by the state was fundamental in the expansion and stability of capitalism in its early stages, during the laissez-faire era of the nineteenth century and under Fordism in the twentieth century. This argument is illustrated through a review of salient aspects of classical liberal theories of the state such as those of John Locke, Adam Smith, Jeremy Bentham, and John Stuart Mill and a brief review of the theory of Marx and early twentieth century contributions such as those of Karl Polanyic and John M. Keynes. An analysis of the theories of the role of the state under Fordism is proposed in the final sections of the chapter.
Keywords: Fordism; MARX, Karl, 1818-1883; double movement; economic sociology; organizational studies; regulated capitalism

Deindustrialisation and the Historical Sociological Imagination: Making Sense of Work and Industrial Change - Strangleman, Tim (SOCIOLOGY-THE JOURNAL OF THE BRITISH SOCIOLOGICAL ASSOCIATION, 2017)
Following recent calls for a more self-aware and historically sensitive sociology this article reflects on the concept of deindustrialisation and industrial change in this spirit. Using EP Thompson’s classic The Making of the English Working Class and his examination of industrialising culture with its stress on experience, the article asks how these insights might be of value in understanding contemporary processes of deindustrialisation and work. Drawing on a range of sociological, cultural and literary studies it conceptualises the differences and similarities between two historic moments of industrial change and loss. In particular it draws on the literary concept of the ‘half-life of deindustrialisation’ to explore these periods. The article has important implications for how we think about contemporary and historical industrial decline.
Keywords: THOMPSON, E. P. (Edward Palmer), 1924-1993; half-life of deindistrialisation; historical sociology; work meaning and identity

Climate change and the welfare state? Exploring Australian attitudes to climate and social policy - Spies-Butcher, Ben; Stebbing, Adam (Journal of Sociology, 2016)
Despite growing evidence of significant impacts from human-induced climate change, policy responses have been slow. Understanding this policy inertia has led to competing explanations, which either point to the need to build a consensual politics separated from economic partisanship, or which encourage solidarities between environmental and social movements and issues. This article analyses a recent successful mobilisation, leading to the passage of the Clean Energy Act in Australia, to explore the relationship between attitudes to environmental and social protection, particularly among the core constituency in favour of stronger climate action. Using social survey data from the Australian Election Study, the article finds evidence of independent associations between prioritising environmental concerns and support for welfare state expansion, and a realignment of materialist and post-materialist values. This we argue is consistent with Polanyian analysis that posits a link between social and environmental causes based on resistance to commodification.
Keywords: clean energy; climate policy; climatic changes - government policy; commodification; law and legislation; political attitudes; social policy; welfare state

How Will Capitalism End?: Essays on a Failing System - Streeck, Wolfgang (Verso Books, 2016)
The provocative political thinker asks if it will be with a bang or a whimperAfter years of ill health, capitalism is now in a critical condition. Growth has given way to stagnation; inequality is leading to instability; and confidence in the money economy has all but evaporated.In How Will Capitalism End?, the acclaimed analyst of contemporary politics and economics Wolfgang Streeck argues that the world is about to change. The marriage between democracy and capitalism, ill-suited partners brought together in the shadow of World War Two, is coming to an end. The regulatory institutions that once restrained the financial sector’s excesses have collapsed and, after the final victory of capitalism at the end of the Cold War, there is no political agency capable of rolling back the liberalization of the markets.Ours has become a world defined by declining growth, oligarchic rule, a shrinking public sphere, institutional corruption and international anarchy, and no cure to these ills is at hand.
Keywords: political science / globalization; political science / political economy; political science / political ideologies / democracy

'Socialist Accounting' by Karl Polanyi: with preface 'Socialism and the embedded economy' - Bockman, Johanna; Fischer, Ariane; Woodruff, David (Theory & Society, 2016)
Ariane Fischer, David Woodruff, and Johanna Bockman have translated Karl Polanyi's 'Sozialistische Rechnungslegung' ['Socialist Accounting'] from 1922. In this article, Polanyi laid out his model of a future socialism, a world in which the economy is subordinated to society. Polanyi described the nature of this society and a kind of socialism that he would remain committed to his entire life. Accompanying the translation is the preface titled 'Socialism and the embedded economy.' In the preface, Bockman explains the historical context of the article and its significance to the socialist calculation debate, the social sciences, and socialism more broadly. Based on her reading of the accounting and society that Polanyi offers here, Bockman argues that scholars have too narrowly used Polanyi's work to support the Keynesian welfare state to the exclusion of other institutions, have too broadly used his work to study social institutions indiscriminately, and have not recognized that his work shares fundamental commonalities with and often unacknowledged distinctions from neoclassical economics.
Keywords: Keynesian economics; Keynesianism; embeddedness; neoclassical economics; social accounting; socialism; socialist accounting; socialist calculation debate; welfare state

Polanyi, political-economic opportunity structure and protest: capitalism and contention in the post-communist Czech Republic - Císař, Ondřej; Navrátil, Jiří (Social Movement Studies, 2016)
Drawing on Polanyian logic, we focus on the gradual institutionalization of capitalism in the Czech Republic and the protests accompanying this process. We hypothesize that different configurations of political economy, or what we term the political economic opportunity structure, trigger different popular responses and are a potent indicator of expected protest forms. To analyze this we chose to carry out a country case study, in which many variables commonly associated with political mobilization, in particular the state’s institutional structure, are kept constant. By contrast, models of political economy vary over time, as a function of the extent and form of the international integration of capitalism. We focus on three configurations of political economy – national, globalized and austerity models – and for each one, identify the characteristics and mechanisms, i.e. concrete policy measures, that shape particular protest patterns in the context of our case study. In theoretical terms, this paper seeks to present one possible response, in this case a Polanyian response, to recent complaints about the disappearance of capitalism from social movement studies. At the same time, given the focus of this special issue, our goal is to analyze the current wave of anti-austerity protest that emerged in relation to what has been labelled the Great Recession.
Keywords: Czech Republic; anti-austerity; economic protest; political economic opportunity structure; political opportunity structure; social movement studies

Formal Economy, Substantive Economy, and Economism - Sobel, Richard; Postel, Nicolas (Philosophy of the Social Sciences, 2016)
Polanyi analyzes the historical deployment of a “formal” economic science starting from the “market-scarcity-instrumental rationality triptych.” This triptych, and the knowledge associated with it, is shown to be more than merely a “substantial” economic science’s interest in the triptych “need-nature-institution.” While we must agree with Polanyi that economism is ill-suited to the first triptych, we hesitate to accept his suggested alternative, a heterogeneous mixture of naturalism and institutionalism, essentialism and historicism.
Keywords: capital shortages; capitalism; economic systems; economism; essentialism (philosophy); formal economy; historicism; institutionalism (religion); profit; rationality; scarcity; substantive economy

Globalization and Its Countermovement: Marxian Contention or Polanyian Resistance? - Gemici, Kurtuluş; Nair, Manjusha (Sociology Compass, 2016)
This article surveys the scholarship on the countermovement against the diffusion of capitalism and market economy in the Global South. We identify two streams of analysis in the literature. On the one hand, scholars observe contentious politics instances where the spread of capitalist production relations enables the associational capacity and bargaining power of social classes. On the other hand, there are voluminous studies on contentious politics in the Global South where groups such as peasants, shopkeepers, and urban poor resist the intensification of the market economy. We use Beverly Silver's distinction between Marx-type and Polanyi-type protests, which focuses on how globalization makes and unmakes social groups, to unpack the heterogeneity of the impacts and experiences of globalization. We argue that although Silver's distinction is of great analytical value, there are strong warrants for separating the effects of the market economy from capitalism in studying contentious politics against globalization. Such an analytical strategy (i) expands the scope of the distinction between Marxian and Polanyian contention to social groups other than the working class and (ii) emphasizes that the roots of these struggles lie in the interconnected diffusion of capitalism and market economy.
Keywords: Global South; MARX, Karl, 1818-1883; SILVER, Beverly; countermovement; global south; globalization

Apple, Foxconn, and Chinese workers’ struggles from a global labor perspective - Pun, Ngai; Shen, Yuan; Guo, Yuhua; Lu, Huilin; Chan, Jenny; Selden, Mark (Inter-Asia Cultural Studies, 2016)
To enrich the discussion of global labor, between 2010 and 2016, we studied Apple’s value chain, Foxconn’s mode of labor control, and Chinese workers’ struggles. Through our fieldwork in China we also examined Apple’s and Foxconn’s responses to the spate of worker suicides, workers’ resistance, the activism of scholar and student groups, and transnational justice campaigns. We conclude with reflection on global labor studies in light of the debates between Karl Polanyi’s counter movement and Karl Marx’s class-based struggle.
Keywords: Apple; Apple Inc.; China; Chinese workers; Foxconn; Foxconn Technology Group (Company); MARX, Karl, 1818-1883; POLANYI, Karl, 1886-1964; countermovement; global labor studies; global labour studies; student and scholar activism; value chains; working class

The Commonalities of Global Crises: Markets, Communities and Nostalgia - Karner, Christian; Weicht, Bernhard (Springer, 2016)
Bringing together contributions from an international group of social scientists, this collection examines diverse crises, both historical and contemporary, which implicate market forces, widening inequalities, social exclusion, forms of resistance, and ideological polarisation. The Commonalities of Global Crises offers carefully researched case studies which stretch across large geographical distances- from Egypt to the US and from northern, central, eastern and southern Europe to South America- and covers timely issues including human rights, slavery, care, migration, racism, and the far right. The volume demonstrates that such different settings and diverse concerns are characterized by a common tension in which the crises that unfold around pressures of widening marketization and commodification are met by the (re)building or re-assertion of various communities, and competing politics of solidarity and nostalgia.
Keywords: business & economics / general; commodification; disembedding; double movement; economic theory; political science / general; social science / general

Karl Polanyi and twenty-first century socialism - Block, Fred (openDemocracy, 2016)
Polanyi’s views were the exact opposite of his contemporary, Joseph Schumpeter, who famously defined democracy as giving people a choice over which elite group would rule over them.
Keywords: socialism

Public Capital and the Post-Communist Welfare State: The Case of Poland - Rae, Gavin (Polish Sociological Review, 2016)
This paper provides an overview of some of the main theories of the welfare state. It builds upon Polanyi's theory of the double-movement and relates this to Bourdieu's concept of multiple capitals. It argues that the welfare state can be understood as a form of public capital, both in an economic and sociological sense. The welfare state emerges and is maintained due to a social countermovement that at least partly removes areas of socio-economic life out of commodity relations. In turn this creates public capital, which is both economic and social. In the post-Communist countries most of this public capital was created during a period when almost the whole of economic and social life was controlled by the state. Once the Communist system collapsed, so the accompanying policy of full-employment and system of social welfare organised through state enterprises disappeared. This was met with a large rise in unemployment and labour deactivation, meaning that many social benefits were created during the initial years of the transition. Also, the post-Communist systems inherited large amounts of public capital in the form of public services such as health and education. Through the example of Poland this paper analyses how this public capital was initially maintained and even developed during the early transition period, but then how a process of commodifying it was later begun.
Keywords: BOURDIEU, Pierre, 1930-2002; Poland; capital; communism; countermovement; post-communism; public welfare; social movements; social policy; social services; welfare state

Polanyi’s ‘substantive approach’ to the economy in action? Conceptualising social enterprise as a public health ‘intervention’ - Roy, Michael J.; Hackett, Michelle T. (Review of Social Economy, 2016)
For several decades now, critical public health researchers have highlighted the deleterious effects that pursuing neoliberal policies can have on the ‘causes of the causes’ of poor health and upon growing health inequalities. This paper argues that the conceptual tools of Karl Polanyi can help lend particular insight into this issue. The specific example that this paper focuses upon is the ‘social enterprise’: a form of organisation that combines both social and business objectives. The paper explores, conceptually, whether social enterprises may have the potential to act as one component of a neo-Polanyian countermovement: helping to re-embed the economy back into society, and offering greater recognition for a more comprehensive and socially imbued concept of health. Importantly, this potential is critically examined in the context of neoliberal hegemony, where challenges to the status quo have regularly been met with assimilation, co-option and/or repression.
Keywords: health inequality; public health; social enterprise; substantive approach

England's Great Transformation: Law, Labor, and the Industrial Revolution - Steinberg, Marc W. (University of Chicago Press, 2016)
With England’s Great Transformation, Marc W. Steinberg throws a wrench into our understanding of the English Industrial Revolution, largely revising the thesis at heart of Karl Polanyi’s landmark The Great Transformation. The conventional wisdom has been that in the nineteenth century, England quickly moved toward a modern labor market where workers were free to shift from employer to employer in response to market signals. Expanding on recent historical research, Steinberg finds to the contrary that labor contracts, centered on insidious master-servant laws, allowed employers and legal institutions to work in tandem to keep employees in line. Building his argument on three case studies—the Hanley pottery industry, Hull fisheries, and Redditch needlemakers—Steinberg employs both local and national analyses to emphasize the ways in which these master-servant laws allowed employers to use the criminal prosecutions of workers to maintain control of their labor force. Steinberg provides a fresh perspective on the dynamics of labor control and class power, integrating the complex pathways of Marxism, historical institutionalism, and feminism, and giving readers a subtle yet revelatory new understanding of workplace control and power during England’s Industrial Revolution.
Keywords: business & economics / economic history; economic history; history / Europe / Great Britain; history / general; industrial revolution; social science / sociology / general

Fair trade certification as oversight: an analysis of fair trade international and the small producers' symbol - Clark, Patrick; Hussey, Ian (New Political Economy, 2016)
In this article we analyse Fair Trade as a form of non-state regulation, building on the literature on the internal politics and governance of Fair Trade International (FTI) certification. We focus on recent developments in the FTI certification system, including the split of Fair Trade USA from FTI and the emergence of the Small Producer's Symbol (SPP) as an alternative to FTI certification. We highlight the role of the three regional Producer Networks, in particular the Latin American Producer Network, the CLAC, in the politics and governance of the FTI system. In order to analyse these issues we employ an alternative reading of Karl Polanyi's work in relation to Fair Trade. We problematise the claim made by some in the literature that FTI certification is an example of Polanyi's concept of re-embedding. Instead, we draw on Polanyi's concept of oversight to analyse Fair Trade certification. We argue that the emergence of the SPP out of the CLAC shows promise for being a mechanism of oversight more reflective of Polanyian re-embedding than FTI certification. We also emphasise how the growth of the SPP and the pressure from the Producer Networks have prompted governance reform within the FTI system.
Keywords: Canada; Carleton University; European Union countries; certification; economic conditions; fair trade; financial crises; financial crisis; governance; liberalization (finance); municipal services; producer networks; small producers; unfair competition

Neoliberalism, Polanyi's Protective Response, and Veblenian Waste - Wrenn, Mary V. (Journal of Economic Issues (Taylor & Francis Ltd), 2016)
As capitalism unfolds, continual technological advance -- in combination with the relentless accumulation imperative -- serves to amplify material progress. The expanding economic sphere begins to pervade the everyday lives and thinking of the individual. The institutionalization of the market fundamentally changes the structure of society and, in so doing, fundamentally changes the institutional structure through which individuals are socialized. The social dislocation generated therein prompts Karl Polanyi's protective response. Despite this market intensification, the existence of the economic surplus undermines the syllogistics of market-determined pricing. Evidence of the economic surplus and Veblenian waste as well as of the fact that the competitive law of value is not operable under neoliberalism is found in the lobby industry and campaign contributions. This research seeks to explicitly connect the concepts of Polanyi's protective response with Veblenian waste and the economic surplus in order to better understand how the irrational system of neoliberalism continues to evolve.
Keywords: Veblen; capitalism; economic sociology; economic surplus; institutional economics; neoliberalism

Saving the Commons in an Age of Plunder - Batt, H. William (American Journal of Economics and Sociology, 2016)
Land ownership, as commonly understood today, originated with the enclosure movement during the English Tudor era almost four centuries ago. Karl Polanyi referred to this “propertization” of nature as the “great transformation.” That land, water, and air was a social commons is now archaic and forgotten, and with it the classical economic concept of rent, which was, in theory, once paid to royalty as the earth's guardian. Garrett Hardin's article, “The Tragedy of the Commons,” raised alarm about the abuse and loss of this realm, and he recommended constraints and privatization to prevent this. Most people view titles to landed property much as they do their household goods, but Henry George saw that the earth should be seen as a common resource and its value taxed to benefit everyone. This would restore economic equilibrium to market exchanges and pay for government services. The capture of natural resource rents can supplant taxes on wages and capital goods, and it comports with all textbook principles of sound tax theory. This policy can be the modern replacement for the commons, and implementing resource rent capture is both economically and technically feasible.
Keywords: commons; propertization of nature

Beyond the Minsky and Polanyi Moments - Gemici, Kurtuluş (Politics & Society, 2016)
The period of very high foreclosure rates sets the 2007–8 financial meltdown apart from similar banking crises fueled by asset price booms. Why did the 2007–8 meltdown lead to a prolonged foreclosure crisis? Through a theoretical perspective built on Minsky’s financial instability hypothesis, Polanyi’s ideas about adverse consequences of commodity fiction, financialization of homes, and institutional coupling, I argue that commodifying houses as financial assets exposed mortgage loan holders to price fluctuations originating in capital markets and elevated their risk of default. I show how increased exposure to price fluctuations followed from the tight coupling between U.S. housing and capital markets, a coupling that resulted directly from the rising preponderance of securitization in U.S. housing finance. I provide further evidence from countries where housing finance was tightly coupled with capital markets (Iceland and Ireland) to countries where housing finance did not rely dominantly on capital markets (Canada and the Netherlands).
Keywords: MINSKY, Hyman; United States; asset-backed financing; economic aspects; financial instability; financialization; foreclosure; great recession; housing foreclosures; institutional coupling; recessions - 2008-2013; securitization

The New Urban Fiscal Crisis - Kirkpatrick, L. Owen (Politics & Society, 2016)
Numerous U.S. cities suffered immense fiscal strain following the subprime mortgage crisis and financial crash of 2007–8. Diminished revenues, tightened credit, and speculative financing that went bad in the aftermath fueled widespread fiscal distress on the local scale. Although the current moment resembles fiscal crises that crested in cities in the 1970s–90s, two factors distinguish the current period. First, municipal affairs have become thoroughly financialized—dominated by speculative securities and volatile debt arrangements—such that local crisis can no longer be understood apart from financial market instability. Second, local fiscal politics have become increasingly removed from democratic oversight and control. This de-democratization hinders the capacity of political communities to reregulate markets and rebuild urban communities. An analytic model derived from the work of Hyman Minsky and Karl Polanyi emphasizes how cities become ensnared in a “financial instability” cycle and how communities seek to protect themselves by way of the “double movement.”
Keywords: Chicago; Detroit; MINSKY, Hyman; United States - economic conditions; de-democratization; financialization; municipal bonds; municipal finance; recessions - 2008-2013; urban fiscal crisis

The contradictory logics of financialization: Bringing together hyman minsky and Karl Polanyi - Block, F. (Politics and Society, 2016)
This introduction explains the logic of bringing together the perspectives of Hyman Minsky and Karl Polanyi to analyze processes of financialization. Although Minsky and Polanyi have very different intellectual trajectories, there are important complementarities in their approaches. The introduction also explains the focus of the three papers in this special section written by Kurtuluşc Gemici, Lucas Kirkpatrick, and David Woodruff. © 2015 SAGE Publications.
Keywords: MINSKY, Hyman; finance; financial crises; financial crisis; financialization; political economy; speculation

Treble Troubles? Marketization, Social Protection and Emancipation Considered Through the Lens of Slavery - Davidson, Julia O’Connell (The Commonalities of Global Crises, 2016)
This chapter considers white European and American thinking on transatlantic slavery historically and, more briefly, in relation to today’s antislavery movement. Combining historical longue durée and a critical engagement with Nancy Fraser’s neo-Polanyian position, O’Connell Davidson shows that abolitionists were, and are, hard to fix as proponents of either market freedom or social protection, or indeed of ‘emancipation’. The postabolition experience of freed slaves shows that marketization, social protection and emancipation are not fully disarticulable political forces, suggesting that the idea of the ‘triple movement’ may be less useful for those committed to a politics of nondomination than it may initially appear.
Keywords: economics; public choice; slavery; social choice; social inequality; social protection; social structure; triple movement; welfare economics

Domesticating the market: moral exchange and the sharing economy - Fitzmaurice, Connor; Ladegaard, Isak; Attwood-Charles, William; Cansoy, Mehmet; Carfagna, Luka; Schor, Juliet; Wengronowitz, Robert (Under review at Socio-Economic Review, 2016)
The sharing economy has generated enormous excitement with its promise of transforming work and consumption through technology and novel socio-economic relations. However, critics see the phenomenon as a further development of neoliberalism. Platforms such as Airbnb and TaskRabbit, monetize a previously uncommodified realm of life via renting of bedrooms, possessions, space and labor time. In this paper, we analyze the meanings and attitudes of sharing economy participants. On the basis of 100 interviews in two for-profit and three not-for-profit sites, we find that most see the sharing economy as an opportunity to build a radically different market, from the bottom up. They are critical of the neoliberal market order, and envision an economy of personalized exchanges that are morally attuned, based on ideals of community, and that help them achieve creative and financial autonomy in their working lives. To our respondents, the sharing economy is an opportunity to domesticate the market.
Keywords: domestic production; economic sociology; hostile worlds; markets; morality; neoliberalism; sharing economy

Local Embeddedness - Pickles, John (International Encyclopedia of Geography: People, the Earth, Environment and Technology, 2016)
In economic geography and economic sociology, embeddedness refers to the ways in which relational, institutional, and cultural contexts shape economic life. In contrast to the undersocialized and utilitarian assumptions of neoclassical economics, rational choice theory, and new institutional economics, theories of embeddedness focus on the ways in which markets and society are variously articulated in particular societies, organizations, and places. Embeddedness in this sense is associated first and foremost with the work of Karl Polanyi. Polanyi argued that the market generally sought to disembed itself from social regulation, while society responded by attempting to socialize and regulate (re-embed) the excesses of unregulated markets. It is also associated with the work of Granovetter in economic sociology, who cautioned against oversocializing, as well as undersocializing, the economy, in favor of a much more detailed analysis of the specific ways in which social relations structured economic practices.
Keywords: POLANYI, Karl, 1886-1964; culture; economy; embeddedness; institutions; society; undersocialized

The evolution of false self-employment in the British construction industry: a neo-Polanyian account of labour market formation - Behling, Felix; Harvey, Mark (Work, Employment & Society, 2015)
Governments in Europe and elsewhere have renewed their attention to the fiscal regulation of their economies in order to close tax loopholes and boost revenues in response to the financial crisis. The article uses a neo-Polanyian ‘instituted economic process’ approach to explore and explain the uniquely high level of bogus self-employment in the UK construction industry, facilitated by confused law and stimulated by a bespoke construction fiscal regime, resulting in endemic tax evasion. It examines how the co-evolution of employment status law and a sector-specific fiscal regime maps tightly onto the emergence of mass self-employment, as evidenced by comparative labour market and sectoral statistics. Seeing competition as an instituted process within these distinctive market arrangements, it identifies a form of ‘degenerative competition’, driving out both genuine direct-employment and self-employment, and driving in bogus self-employment, with its attendant substantial fiscal losses, failed skill reproduction and poor productivity.
Keywords: British construction industry; Great Britain; bogus self-employment; business revenue; construction industry; economic sociology; instituted economic process; labour market formation; self-employment; tax evasion; tax loopholes

Sharing Economy: A Step towards the Re-embeddedness of the Economy? - Pais, Ivana; Provasi, Giancarlo (Stato e Mercato, 2015)
The expression "sharing economy" has spread exponentially in the past few years, a sign of the growing interest in a phenomenon that continues to maintain boundaries that are somewhat vague. The hypothesis of this paper is that this can be attributed not only to the pervasiveness and enabling power of new technologies but also to the need to fill a social vacuum due to the failures of the market and the state. The sharing economy is introducing collaborative social forms able (at least ideally) to embed economic relations within social ones. To test this hypothesis, the article uses the instrumentation implemented by Karl Polanyi to analyze the forms of integration of economy and society (exchange, reciprocity, redistribution). The political economy of the late twentieth century was especially interested in exchange (market) and redistribution (state), leaving social reciprocity in the background. However, we have to look at this more carefully to grasp any social and institutional innovation that the sharing economy can promote. The first part of this paper is devoted to an analysis of the forms of integration and, in particular, to reciprocity in its different variants. The second part, in light of the taxonomy proposed in the first, analyzes some of the most significant experiences of the sharing economy, seeking to determine the institutional characteristics and social dynamics that this could (at least potentially) engender and support. The conclusions will attempt to answer the questions formulated and indicate avenues for further research.
Keywords: cooperative enterprises; economic anthropology; economic sociology; market structure, pricing, and design; open source products and markets; other economic systems: general; prices; public goods; reciprocity; renewable resources and conservation: demand and supply; sharing economy; social and economic stratification

Re-Imagining Economic Sociology - Aspers, Patrik; Dodd, Nigel (Oxford University Press, 2015)
The purpose of this book is to explore new developments in the field of economic sociology. It contains cutting-edge theoretical discussions by some of the world's leading economic sociologists, with chapters on topics such as the economic convention, relational sociology, economic identity, economy and law, economic networks and institutions. The book is distinctive in a number of ways. First, it focuses on theoretical contributions, by pulling together and extending what the contributors believe to be the most important theoretical innovations within their own particular areas of the field. Second, there are contributions by leading economic sociologists from both the US and Europe, which gives the book both wider scope and appeal, while also creating the opportunity for some interesting dialogue between distinct theoretical traditions. The book will be of interest to researchers, Ph.D. students, and advanced students on both side of the Atlantic, and indispensible in advanced economic sociology courses.
Keywords: business & economics; economic sociology; economic theory; social science / sociology / general

Disembedded markets as a mirror of society - Deutschmann, Christoph (European Journal of Social Theory, 2015)
In the Marxist tradition, capitalism is understood as a commodified society based on markets. The article argues that the ultimate justification of this position does not lie in any ‘materialistic’ approach, but in the disembedding of markets that was the result of the historical ‘Great Transformation’ analysed by Karl Polanyi. Disembedded markets are not an economic subsystem within society but take the place of the most encompassing social system, which Durkheim had reserved for religion. The article distinguishes between spatial, social, material and temporal dimensions of disembedding, thereby elaborating and correcting the analysis of Karl Polanyi. As a genuine form of society, disembedded markets give rise to the epistemological dilemma, which, as Luhmann had shown, is fundamental to any encompassing social theory: Society as a whole cannot be viewed by any observer. According to this viewpoint, economic theories take on ‘theological’ functions, as they provide rationality and legitimacy to a reality that is unknowable.
Keywords: Marxist philosophy; capitalism; disembedded markets; disembedding; markets; religion; social theory; uncertainty

Polanyi in the European Single Market: The Re- Regulation of Insurance - Mabbett, Deborah (Economic Sociology: The European Electronic Newsletter, 2015)
This article discusses the difference between a social policy approach to the regulatory embedding of a market and a moral economy approach using the insurance case wherein the European Union's Court of Justice ruled that insurers may not discriminate on grounds of sex in identifying risks.
Keywords: Court of Justice of the European Union; insurance; lawsuits & claims; reembedding; regulation; social policy

A hidden counter-movement? Precarity, politics, and social protection before and beyond the neoliberal era - Harris, Kevan; Scully, Ben (Theory & Society, 2015)
To grasp what might exist beyond neoliberalism, we need to rethink the history of development before neoliberalism. This article makes two arguments. First, for poorer countries, processes of commodification which are highlighted as evidence of neoliberalism often predate the neoliberal era. Third World development policies tended to make social and economic life more precarious as a corollary to capital accumulation before neoliberalism as an ideology took hold. Second, the intense theoretical and discursive focus on neoliberalism has obscured a tangible shift towards de-commodification in much of the global South. The most salient examples today are state-led social assistance programs that have been implemented across the former Third World. These emerged not out of technocratic fixes from above but often out of political and social struggles from below. The rise and spread of these programs are not only in stark contrast to popular conceptions of a neoliberal reinforcement, but are also specifically targeted at social strata whose precarity commonly originated in developmental policies before the neoliberal era. Utilizing a database of 183 active flagship social assistance programs in 84 developing countries, we present macro-level quantitative evidence of the rise and spread of social protection policies over the past two decades in the global South. We then detail these programs for four middle-income countries-China, Brazil, India, and South Africa. To those who lament that the 2008 crisis has produced no Polanyian double movement, we argue that these state-driven social assistance policies are such a mechanism.
Keywords: Global South; abstracts; countermovement; developing countries; double movement; global south; ideology; labor studies; labour studies; middle-income countries; neoliberalism; peasant studies; social policy; social services; welfare studies

Regulatory Transformations: Rethinking Economy-Society Interactions - Lange, Bettina; Haines, Fiona; Thomas, Dania (Bloomsbury Publishing, 2015)
The issue of whether transnational risk can be regulated through a social sphere goes to the heart of what John Ruggie has described as 'embedded liberalism': how capitalist countries have reconciled markets with the social community that markets require to survive and thrive. This collection, located in the wider debates about global capitalism and its regulation, tackles the challenge of finding a way forward for regulation. It rejects the old divisions of state and market, citizens and consumers, social movements and transnational corporations, as well as 'economic' and 'social' regulation. Instead this rich, multidisciplinary collection engages with a critical theme-the idea of harnessing the regulatory capacity of a social sphere by recognising the embeddedness of economic transactions within a social and political landscape. This collection therefore explores how social norms, practices, actors and institutions frame economic transactions, and thereby regulate risks generated by and for business, state and citizens.A key strength of this book is its integration of three distinct areas of scholarship: Karl Polanyi's economic sociology, regulation studies and socio-legal studies of transnational hazards. The collection is distinct in that it links the study of specific transnational risk regulatory regimes back to a social–theoretical discussion about economy–society interactions, informed by Polanyi's work. Each of the chapters addresses the way in which economics, as well as economic and social regulation, can never be understood separately from the social, particularly in the transnational context.Endorsement'This thought-provoking collection asks the most critical question of our time – how to civilise markets through social accountability and political action. The climate and financial crises we face show how crucial this challenge is. Lange, Haines and Thomas have put together a series of fruitful case studies of the possibilities for embedding economic relationships in social relationships by a series of top-class researchers within their own illuminating and sensitive framing of the issue'.Professor Christine Parker, Professor of Regulatory Studies at Monash University.
Keywords: administrative law & regulatory practice; economic regulation; economic sociology; embedded liberalism; social regulation; socio-legal studies

Markets, Nature, and Society Embedding Economic & Environmental Sociology - Kaup, Brent Z. (Sociological Theory, 2015)
Social scientists have drawn on theories of embeddedness to explain the different ways legal, political, and cultural frameworks shape markets. Often overlooked, however, is how the materiality of nature also structures markets. In this article, I suggest that neo-Polanyian scholars, and economic sociologists more generally, should better engage in a historical sociology of concept formation to problematize the human exemptionalist paradigm their work upholds and recognize the role of nature in shaping markets and society. Unearthing nature in the work of Karl Polanyi, I develop a theory of embeddedness that more closely accounts for the economic, the social, and the ecological. In doing so, I provide a way for scholars to conceptualize both how market societies shape nature and how nature shapes market societies.
Keywords: ecology; embeddedness; environmental sociology; materiality; socionatural

Karl Polanyi and the Problem of Corporate Social Responsibility - Moncrieff, Lilian (Journal of Law and Society, 2015)
This article considers Corporate Social Responsibility (CSR) as part of the projects in ‘new governance and decentred regulation’, which draw social forces towards the regulation of economic behaviour. It uses Karl Polanyi to open up pertinent interfaces between society and economy for observation, and Gunther Teubner to substantiate a ‘regulatory’ view of the company's social relationships. The article finds that CSR combines movements for the recognition of social relationships, on an unprecedented scale, with rigorous simultaneous movements for market building and social abstraction. Twenty-first-century market economy is defined by a capacity to contain ‘the social,’ which is thrown between the two movements, creating opportunities for companies to void the market's social limits. The article counterposes that the social that ‘returns’ after marketization needs to find its way past market-building CSR, to constructively unshackle and redefine the framing of social conflicts that concern the corporation.
Keywords: CSR; corporate social responsibility; marketization

Hard cash, easy credit, fictitious capital: Critical reflections on money as a fetishised social relation - Jessop, Bob (Finance and Society, 2015)
Keywords: Marxism; commodity; credit; debt; fictitious capital; money

Marketization: Theoretical Reflections Building on the Perspectives of Polanyi and Habermas - Ebner, Alexander (Review of Political Economy, 2015)
The concept of marketization denotes the expansion of market coordination into non-market coordinated social domains as well as its intensification in already market-dominated settings. This article sets out to reconstruct an institutionalist theory of marketization. As a point of departure, it critically examines the related contributions of Karl Polanyi and Jürgen Habermas. The analytical strength of Polanyi's theory of marketization lies in the discussion of the contested embeddedness of markets and the view of marketization as a politically shaped process of institutional change. This concern with the societal expansion of markets is further developed in the Habermasian thesis of the ‘colonisation of the lifeworld’. However, both Polanyi and Habermas lack a specification of the social substance of markets and thus tend to underestimate the complexity of marketization. To address this issue, the present article utilizes the concept of collective goods to introduce new arguments about the institutional dynamics of marketization in the diverse fields of society.
Keywords: HABERMAS, Jurgen; collective goods; economics; embeddedness; marketization; markets; socioeconomics

Marketization and the public-private divide - Rekhviashvili, Lela (International Journal of Sociology & Social Policy, 2015)
Purpose – The purpose of this paper is to critically examine the reasons behind a decade long contestations between the Georgian government and the petty traders over the access to the public space for commercial use. Design/methodology/approach – The paper relies on the repeated ethnographic fieldwork conducted in Tbilisi in 2012 and 2013. The ethnographic interviews with legally operating traders and illegal street vendors are supplemented by the in-depth interviews with the representatives of the city government and secondary literature on Georgia’s post-revolutionary transformation. Findings – Bridging the critical literature on the politics of the public space with Polanyi’s theory on commodification of fictitious commodities as a precondition of establishment of a market economy, the author argues that for the Georgian government control of the public space was necessary to pursue neoliberal marketisation policies. These policies required removal of the petty traders from public spaces because the state needed to restrict access to public space and limit its commercial usage to delineate public and private property and allow commodification of the urban land and property. As the commodification intensified and the rent prices started growing and fluctuating, the access to the public space became even more valuable for the petty traders. Therefore, the traders developed subversive tactics undermining the division between public and private space and property. Originality/value – The paper demonstrates the importance of enforcing the public-private divide in the process of establishing a market economy in transitional settings. Moreover, it illustrates little discussed social costs of establishing such a divide.
Keywords: Tbilisi; commodification; fictitious commodities; informal economy; marketization; municipal government; neoliberalism; petty trade; public space; public spaces; public-private sector cooperation; transition economies

The Neoclassical Origins of Polanyi’s Self-Regulating Market - Gemici, Kurtuluş (Sociological Theory, 2015)
This article shows, through a detailed examination of Karl Polanyi’s published works and unpublished writings, that Polanyi relies heavily on the neoclassical economics of his time in his conceptualization of the market in capitalist societies. This approach is instrumental to the thesis of The Great Transformation concerning the destructive impact of the market on society. However, such an analytical perspective neglects the social character of the market economy. This perspective is also deficient in capturing why the market is destructive to the social fabric. By identifying the origins and limitations of Polanyi’s self-regulating market, this article contributes to critical reevaluations of his work that aim to expand the scope of Polanyian analysis. In particular, this article outlines how the analysis of the market’s contradictory place is not predicated on the notion of self-regulation. Polanyi’s own historical work, as opposed to his theoretical articulations, illustrates such an analysis.
Keywords: double movement; neoclassical economics; self-regulating market

Migration, Precarization and the Democratic Deficit in Global Governance - Schierup, Carl-Ulrik; Ålund, Aleksandra; Likić-Brborić, Branka (International Migration, 2015)
This article attempts to provide a critical understanding of the dual signification of “precarity”. It explores what “precarity” as a concept may potentially offer to studies of the changing contemporary political economy of migration. It discusses shifting trends in global migration and point to tendencies for a possible convergence between “South” and “North”, “East” and “West”. Based on a review of current advances in research, it discusses, with reference to the classical work of Karl Polanyi, the potential for a contemporary “countermovement” which would challenge the precarity of migrants. Bringing forward the issue of the “space for civil society” the article addresses a still lingering democratic deficit in the global governance of migration. Policy Implications The article is relevant to policymakers, trade unions and civil society organizations. It contributes to the understanding of policy making processes in emerging multilevel global governance and focuses on issues of precarization, migration, and the implementation and accountability of human, migrant and labour rights.
Keywords: countermovement; democratic deficit; ethnicity; global governance; migration; precarity; social welfare studies

Between Marx and Polanyi: New labour mobilisations in the Italian crisis - Caruso, Loris (Capital & Class, 2015)
The current scenario in western countries is characterised by a crisis over the last thirty years of class conflict; by the mainly negative consequences of globalisation and of the transformations by production processes of the mobilising strength of work; by the cancellation of the relationship between labour and political representation; by the difficulties of traditional trade unionism; and by the emergence of the social movement unionism (SMU) paradigm. In this article, these phenomena are analysed from the point of view of the workers’ struggles against the closure of factories. The analysis concerns the mobilisation factors on which the struggle rests; the presence or absence, in the representations of workers, of references to class conflict; the major proximity of these mobilisations to the paradigm of traditional syndicalism or to the SMU paradigm; and the prevalence within them of the Marxist or the Polanyian root of conflict. This analysis is mainly based on an empirical study carried out in an engineering company in the province of Milan, Italy.
Keywords: MARX, Karl, 1818-1883; class cleavage; class conflict; crisis; globalisation; globalizaton - research; labor mobility; labor unions; labour mobilisations; labour mobility; labour unions; research; social conflict; social movements

Gellner’s genealogy of the open society: Biopolitics as fragment and remainder - Ryan, Kevin (Thesis Eleven, 2015)
A decade before Foucault began to work with the related concepts of biopolitics and biopower, Gellner posed a series of questions which are suggestive of a similar line of inquiry. Gellner did not pursue this strand of his thought as an historical sociologist however. Instead he packaged it into a functionalist account of how industrial society reproduces itself. In Gellner’s writings, biopolitics is both present and absent, like a redacted text. This is the focus of this article, which locates Gellner’s method of inquiry within a corpus of genealogical studies that includes the work of Polanyi, Weber and Foucault. What distinguishes Gellner is that the history he reconstructs is a story of achievement in the face of terrible historical odds, but this culminates in a normative genealogy that limits the scope for critical analysis. The article concludes by adopting an alternative – yet still Gellnerian – approach to the question of social reproduction, thereby using Gellner to critique Gellner.
Keywords: FOUCAULT, Michel, 1926-1984; GELLNER, Ernest; biopolitics; biopolitics (philosophy); biopower; genealogy; historical sociology; realism; social aspects

The course, contradictions, and consequences of extending competition as a mode of (meta-)governance: towards a sociology of competition and its limits - Jessop, Bob (Distinktion: Journal of Social Theory, 2015)
This article examines the use of competition as an object and mode of governance. It first considers how competition might become a principle of economic organization and, relatedly, how it may become part of state projects and practices. Second, it comments on the discursive and material dimensions of competition, considering it as a social construct and as a social constraint. Third, it examines the rather idealized representations of competition in the broader doxa of liberalism and neo-liberalism considered in terms of a rough threefold distinction among economic, political, and ideological imaginaries and the limits to the reproduction of these doxa in terms of the complexities of capitalist social relations. Fourth, it explores the complexities of competition in the actually existing world and their role in differential accumulation. In this context it distinguishes neo-classical, Austrian, and Schumpeterian views on competition and entrepreneurship and their contribution to equilibration or creative destruction. Fifth, it considers efforts to steer competition through, inter alia, the competition state and competition law. Sixth, it relates competition to other modes of governance and identifies limits to its role in this regard and introduces ‘meta-governance’ as a response to these limits. Finally, seventh, it comments on the fetishization of competition as a means to subsume society under the dominance of profit-oriented, market-mediated accumulation. It concludes with comments on the limits of competition in relation to fictitious commodities and goods and services that contribute to human flourishing.
Keywords: commodification; competition; competition law; competition state; competitiveness; governance; neoliberalism; new public management; social theory

Explaining Political Tunnel Vision: Politics and Economics in Crisis-Ridden Europe, Then and Now - Mudge, Stephanie L. (European Journal of Sociology, 2015)
The grip of austerity in European politics since 2008 presents a double puzzle: electorally weak center-left parties offering no definite alternative, and the surprisingly efficient pursuit of “fiscal consolidation”. To understand this double puzzle this article investigates the institutional bases of alternative economic thinking during the 1930s versus the post-2008 crisis years. Noting the recent prominence of a new social type, the European economist-technocrat (eet), I highlight the historically specific order to which the eet is indigenous: rarefied, international professional circuits that tend to work over, not through, party politics. This contrasts sharply with the nationally-based, party-connected economists who developed new economic orthodoxies between the 1930s and 1960s, including Keynes himself. Approaching the study of economic culture in the public sphere in a Polanyian moral markets framework, I argue that the linkages between European economics and financial technocracies help to explain Europe’s double puzzle. Theoretically, I argue that a focus on expertise and parties, and not just states, is central to our understanding of economic culture in the public sphere. (English)
Keywords: European Union; Europäische Union; Frachkenntnisse; Sparmaβnahmen; Union européenne; austerity; austerité; compétence; economics; economists; expertise; partis politiques; political parties; politics and economics; politischen parteien; public sphere; technocracy; wirtschaft; économie

A Neo-Polanyian Theory of Economic Crises - Block, Fred (American Journal of Economics and Sociology, 2015)
This article seeks to use Karl Polanyi's book, The Great Transformation, first published in 1944, to understand the global financial crisis that began in 2008. Polanyi's basic premise was that a great crisis must result from powerful causes. He argued that the crisis of the 1930s was a consequence of three distinct processes: deep imbalances in the global trading system, a crisis within the global financial mechanism that was supposed to manage those imbalances, and a failure of adaptation in the world's leading economy, the United States. The same processes can be seen at work in the last decade.
Keywords: global financial crisis

Pursuing a Great Transformation - Evans, Peter (Sociology of Development, 2015)
Polanyi offers a powerful vision of a “great transformation” that will reverse the subordination of society to the economy and reassert the primacy of social protection in the context of modern society. Pursuit of the great transformation is one way of conceptualizing the quest for “development” in the positive sense of ecologically sustainable human flourishing. This paper explores how the contemporary interaction of national and global political dynamics affects the trajectory of Polanyi's “double movement.” Does the shift of economic power to globally organized capital while the space for contentious politics remains primarily at the national level “checkmate” the movement for social protection? Or is there more potential for political contestation and policies supporting social protection at the national level than the “global checkmate” thesis claims? And, if so, can this potential be magnified by productive, synergistic alliances between national and global movements, resulting in a global auxiliary effect instead of a global checkmate effect? Answering these questions requires analyzing the relative autonomy of national political regimes vis-à-vis global capital as well as evaluating the ability of movements to connect effectively across levels.
Keywords: Great Transformation, The (Book); double movement; global capital; social protection; transnational social movements

Protecting Markets from Society: Non-Pecuniary Claims in American Corporate Democracy - Gershenson, Carl (Politics & Society, 2015)
The state incentivizes investors to entrust capital to public corporations by granting shareholders enforceable rights over managers. However, these rights create legal “access points” through which social movements can make nonpecuniary claims on the corporation. I use original historical research on the Securities and Exchange Commission’s administration of federal securities law to show that concern over nonpecuniary claims motivates the state to enact the role of “market protector.” In this role, the commission insulates managers of corporations from shareholders’ claims that it deems illegitimate because they are insufficiently profit-oriented. Thus the inverse of Polanyi’s observation that society protects itself from markets is also true: the state creates market boundaries so that “always embedded” markets function more like autonomous, profit-oriented markets. Accordingly, the extent to which corporate democracy represents general, social interests or narrow, profit-oriented interests is largely a function of political contestation and state policy.
Keywords: United States; United States Securities & Exchange Commission; corporate accountability; corporate democracy; corporations - government policy; economic sociology; legal status of stockholders; markets; markets - government policy; political sociology; social responsibility of business - United States

Reading The Great Transformation - Martin, Isaac William (Contemporary Sociology, 2015)
Karl Polanyi’s book The Great Transformation is a classic... it has come to be recognized as a founding charter for economic sociology. It anticipated major accomplishments of late-twentieth-century social science (including, among others, Ben Bernanke’s studies of the Great Depression and Amartya Sen’s work on famine). Its core problems—how do societies respond to globalization? how do they address the risks of market failure?—are central to contemporary macrosociology. It is probably time to recognize the canonical status of this book and put it on the classical theory syllabus alongside Marx, Weber, and Durkheim. But The Great Transformation is also—can we admit this about our classics?—a mess. It is conceptually sloppy. Some key terms (such as “market society” and “social dislocation”) are never explicitly defined. Others (such as “a ‘movement’”) are defined with pedantic care, and then used willy-nilly, as if Polanyi forgot what he said the words meant. Important steps in the argument assume what is to be proven. Inconsistencies abound. The treatment of historical sources is casual. To round it all off, the book concludes with a breathtakingly wrong prediction: namely, that the era of market liberalism is over for good—as of 1944. To salvage a theory from all this, let alone one that we can apply to societies in the present day, surely requires a heroic effort of interpretation. Fred Block and Margaret R. Somers undertake the salvage effort...
Keywords: BLOCK, Fred L.; Great Transformation, The (Book); Power of Market Fundamentalism: Karl Polanyi's Critique, The (Book); SOMERS, Margaret R.; book review; nonfiction

The Evolution of the Property Relation: Understanding Paradigms, Debates, and Prospects - Davis, Anne E. (Springer, 2015)
Evolution of the Property Relation defines an approach to economics which is centered around the concept of property and explores the historical evolution of the relationship of the individual, private property, and the state, and the distinctive changes wrought by the emergence of the market.
Keywords: business & economics; economic development; economic history; economic theory; labor; labour; management; organizational behavior; social science; sociology; strategic planning

Embedding and disembedding of political elites: a filter system approach - Davis, Aeron (Sociological Review, 2015)
This article looks at the issue of political disengagement in mature democracies and the growing tendency towards disconnect between citizens and their political representatives. It locates itself in relation to 'demand-side' (external to politics) and critical 'supply-side' (focused on the political centre) explanations of disengagement. It concentrates on the latter and, accordingly, builds on critical, post-Marxist and elite-oriented work. As such it follows on from earlier calls in the journal for a return to elite-based research ( Savage and Williams, 2008). Drawing on general concepts in economic sociology ( Polanyi, Granovetter) the article presents an alternative embedding-disembedding paradigm for explaining and evaluating this tendency towards political elite disengagement. The propensity for politicians to disembed from wider society is explained by way of a series of eight 'filters'. Such filters work, alone or cumulatively, both to socially embed political elites within the institutions and networks of formal politics and also to disembed them from wider society and the populace they represent. The interpretive framework outlined here draws on a combination of secondary literature and ongoing interview-based research with some 150 political actors (politicians, journalists, officials) working at Westminster. As such, the filters and embedding-disembedding paradigm focuses primarily on the UK case. However, the framework is easily adaptable to other nations and systems.
Keywords: Great Britain - politics & government; communication; disengagement; elite (social sciences); embedding/disembedding; organizations; political communication; political elites; political organizations; political participation laws; politicians

Facing an unequal world - Burawoy, Michael (Current Sociology, 2015)
To face an unequal world requires us to interpret and explain it, to be sure, but also to engage it, that is, to recognize that we are part of it and that we are partly responsible for it. In other words, inequality is not just something external to us, but also invades our own world. I begin, therefore, by examining the global community of sociology through the lens of inequality. I then consider two recent perspectives on our unequal world from outside sociology: the moral radicalism of Pope Francis that emphasizes exclusion from market society, and the innovative research of the economist Thomas Piketty that emphasizes unequal inclusion in market society. These two faces of global inequality mirror the social movements reverberating from the economic crisis of 2008 but which have their roots in a reaction to a broader wave of marketization, the third to engulf modern capitalism. To explore the meaning of third-wave marketization, otherwise known as neoliberalism, and the social movements it provokes I draw on two concepts from Karl Polanyi – ‘fictitious commodities’ and ‘countermovement’ – as well as a theory of the dynamics of capitalism. I conclude with three challenges facing a global sociology that centers social movements: to develop a theory that speaks to the globally diverse experiences of commodification; to develop a methodology that recognizes that we are unavoidably participants in the world we study; and to develop a politics that defends a particular vision of that world, a vision that has defined the sociological tradition from its beginning, namely one that upholds the centrality of civil society against the over-extension of market and state.
Keywords: globalization; inequality; markets; social movements; sociology

Reforming States, Agricultural Transformation, and Economic Development in Russia and Japan, 1853-1913 - Cohen, Mark (2015)
Capitalist economic development has occurred unevenly, as certain economies began sustained growth relatively early, opening up an increasingly large gap with lagging countries. This well-known fact has encouraged much research on the prospects for undeveloped economies to "catch up" to the earlier developers. Japan and Russia in the late nineteenth century were two of the first countries outside of western Europe to experience substantial catch-up growth. Beginning in the 1860s, political elites in both countries adopted wide-ranging reforms in pursuit of military modernization and its political and economic prerequisites. This paper analyzes the impact of the two states' reform programs on their countries' rural economies, which represented the vast majority of population and production. Adopting a Polanyian perspective on economic development, this paper finds that only in Japan were agrarian relations transformed so as to set off a process of capitalist economic development centered on rural areas. This divergence is explained by the different stances of the two reforming states towards landlords and peasant communities.
Keywords: Japan; Russia; economic development; rural economies

Karl Polanyi's Environmental Sociology - Fenner, IV, Weston Henry; Brechin, Steven R. (Conference Papers -- American Sociological Association, 2015)
Drawing upon The Great Transformation (1944), we outline Karl Polanyi's environmental sociology by presenting his major insights on economic substantivism, fictitious commodities, and double movements. Polanyi wrote his opus in challenge to Von Mises' Austrian School of Economics and its pursuit of an autonomous, self-regulating global free market. Polanyi's recognized the social and environmental limits of a fully free market and reasoned that inevitable market excesses would result in the rise of society self-protection to preserve land along with labor and money. We believe Polanyi's insights make him an important classical contributor to environmental sociology on par with Robert Malthus, Karl Marx, Max Weber, and Emile Durkheim. We conclude by outlining possible connections to established environmental sociology theories and literatures.
Keywords: double movement; double movements; economic substantivism; environmental sociology; fictitious commodities; market fundamentalism; social theory

Denaturalizing the Market: Primitive Accumulation, Class Reformation, and the Rise of Colombia's Anti-Neoliberal Countermovement - Hough, Phillip A. (2015)
This paper addresses what labor movement scholars are calling the "Polanyi-problem" - how societal movements can effectively re-embed neoliberal markets back into society - by drawing upon recent interpretations of Karl Marx writings on primitive accumulation and class formation. The author focuses on the case of Colombia's coffee farmers (cafeteros) - a class of producers whose historically-privileged modality of class reproduction was undermined by the liberalization of the coffee market in the 1990s and who have engaged in two major waves of protest aimed at re-embedding the coffee market back into society (1993-2001; 2013-2014). While similar in terms of movement targets, tactics, and general goals, a significant shift has occurred in the cafeteros' demands which is reflective of a fundamental transformation of their class identity away from one that 'naturalized' their dependence upon the coffee market to meet their subsistence needs and towards one that 'de-naturalizes' their dependence upon this market. This 'denaturalizatization of the market' undermined their ability to mobilize around a privileged form of class identity. Yet, it provided them with the ability to generalize their struggle beyond the confines of the coffee economy and therefore develop into a broad, national anti-neoliberal agrarian Polanyian counter-movement.
Keywords: Colombia; Polanyi problem; countermovement; primitive accumulation; reembedding

Challenging Dominant Market Theories in Five Ways[1] - Janoski, Thomas (disClosure, 2015)
This article discusses why many social scientists including Karl Polanyi, Max Weber, and Karl Marx are dissatisfied with an overreliance on markets, and a conceptualization of markets being efficient, fair and rational. Topics include five types of arguments critical of markets including the Marxian approach to markets, the rise of Karl Polanyi's view that markets are fragile, and a more complex decision-making approach starting with Max Weber's view of social action.
Keywords: MARX, Karl, 1818-1883; WEBER, Max, 1864-1920; markets; social action; social scientists

The politics of Piketty: what political science can learn from, and contribute to, the debate on Capital in the Twenty-First Century - Hopkin, Jonathan (The British Journal of Sociology, 2014)
Thomas Piketty's imposing volume has brought serious economics firmly into the mainstream of public debate on inequality, yet political science has been mostly absent from this debate. This article argues that political science has an essential contribution to make to this debate, and that Piketty's important and powerful book lacks a clear political theory. It develops this argument by first assessing and critiquing the changing nature of political science and its account of contemporary capitalism, and then suggesting how Piketty's thesis can be complemented, extended and challenged by focusing on the ways in which politics and collective action shape the economy and the distribution of income and wealth. Although Capital's principal message is that ‘capital is back’ and that without political interventions active political interventions will continue to grow, a political economy perspective would suggest another rather more fundamental critique: the very economic forces Piketty describes are embedded in institutional arrangements which can only be properly understood as political phenomena. In a sense capital itself – the central concept of the book – is almost meaningless without proper consideration of its political foundations. Even if the fact of capital accumulation may respond to an economic logic, the process is embedded in a very political logic. The examples of housing policy and the regulation, and failure to regulate, financial markets are used to illustrate these points.
Keywords: capital; inequality; institutions; political science

Towards a Polanyian Sociology - Gemici, Kurtuluş (European Journal of Sociology, 2014)
Keywords: BLOCK, Fred L.; Power of Market Fundamentalism: Karl Polanyi's Critique, The (Book); SOMERS, Margaret R.; anthropology; nonfiction; review

Capital in the Twenty-First Century by Thomas Piketty translated by Arthur Goldhammer (Cambridge, MA, Harvard University Press, 2014) - Milkman, Ruth (European Journal of Sociology / Archives Européennes de Sociologie, 2014)
KM - A book review of Capital in the Twenty-First Century that points out the glaring omission of Polanyi.
Keywords: Great Transformation, The (Book); PIKETTY, Thomas; book review

Polanyian Themes: From Budapest to the Caribbean - Block, Fred (Development & Change, 2014)
KM: Book review of "From the Great Transformation to the Great Financialization"
Keywords: FROM the Great Transformation to the Great Financialization (Book); From the Great Transformation to the Great Financialization (Book); LEVITT, Kari, 1923-; POLANYI LEVITT, Kari; economic development; nonfiction

Karl Polanyi: New Perspectives on the Place of the Economy in Society - Harvey, Mark; Ramlogan, Ronnie; Randles, Sally (Oxford University Press, 2014)
The work of Karl Polanyi has gained in influence in recent years to become a point of reference to a wide range of leading authors in the fields of economics, politics, sociology and social policy. Newly available in paperback, this volume is a combination of reflections on, and assessment of, the nature of Polanyi's contribution and new strands of work, both theoretical and empirical, that has been inspired by Polanyi's insights. It gathers together the key contributions to the first ever workshop on the work of Karl Polanyi held in the United Kingdom. Several of the contributions develop Polanyian ideas in relation to contemporary capitalism. However, in a critical spirit, other contributions in the volume substantially transform his concept 'instituted economic process' in considering a broad range of contemporary socio-economic change: markets for mobile telephony, call centre operations and European labour markets.
Keywords: business & economics; economic theory

Income Inequality in Advanced Capitalism: How Protective Institutions can Promote Egalitarian Societies - Kollmeyer, Christopher (Comparative Sociology, 2014)
This study develops a Polanyian perspective on income inequality in advanced capitalist countries. Polanyi's historical account of the rise and fall of classic liberalism in Britain illustrated how social groups and society at large devised "protective institutions" to shield themselves from socially destructive market forces. Recent qualitative applications of this idea identify three protective institutions as being the most important - the public sector economy, trade unions, and the family. Using data from 16 Western countries from 1970 to 2010, this study demonstrates that cross-national and temporal variations in these protective institutions explain a considerable amount of the observed patterns of income inequality among these countries, helping to explain why some countries have recently experienced rising inequality but others have not. The study ends by arguing that a Polanyian perspective provides more analytical and theoretical leverage than other sociological approaches to understanding income inequality.
Keywords: The Great U-Turn; capitalism; economic sociology; income distribution; income inequality; labor unions; labour unions; liberalism; protective institutions; research; social groups - research

Informalizing the Economy: The Return of the Social Question at a Global Level - Breman, Jan; van der Linden, Marcel (Development and Change, 2014)
The classical conceptualization of the working class, of workers’ collective action and, especially, of trade unionism, was implicitly or explicitly based on the Standard Employment Relationship that, for a few decades, has been dominant in North America, Europe, Japan and Australasia. The ‘classical’ model of collective bargaining, which has shaped the world's traditional labour movements, was based on this conceptualization. However, it is now increasingly undermined by the rapid spread of ‘informal’ or ‘precarious’ labour in the global North. It is our contention that the ‘classical’ view of the working class and workers’ collective action is fundamentally biased and takes as a norm or standard what was in fact an historical exception. The real norm or standard in global capitalism is insecurity, informality or precariousness, and the Standard Employment Relationship is an historical phenomenon which had a deep impact in a limited part of the world for a relatively short period of time. If, as we argue, the ‘Rest’ is not now becoming like the ‘West’, but the other way round, then the ‘traditional’ forms of collective action that have developed in the North Atlantic region during the last two centuries are gradually losing much of their impact. New forms of collective action are emerging, though these are often still at an embryonic stage. It is, therefore, high time to rethink the concept of the working class and the ways in which it can further its interests.
Keywords: informalization; precarity

Alienated Politics: Labour Insurgency and the Paternalistic State in China - Friedman, Eli (Development and Change, 2014)
Is there a labour movement in China? This contribution argues that China does not have a labour movement, but that contestation between workers, state and capital is best characterized as a form of ‘alienated politics’. Widespread worker resistance is highly effective at the level of the firm because of its ability to inflict losses on capital and disrupt public order. But authoritarian politics in China prevent workers from formulating political demands. Despite the spectacular repressive capacity of the state, the central government has in fact responded to highly localized resistance by passing generally pro-labour legislation over the past decade. The consequence of this is that worker unrest has produced important political shifts at the national level, but these have come about without workers’ direct involvement in the process. In other words, workers are alienated from the political object that they themselves have produced. As a consequence, when the state intervenes in labour politics, it appears to be doing so of its own accord, i.e. paternalistically. This framework helps us to understand how worker unrest in China has become highly antagonistic towards employers and the local state, while maintaining the stability of the system as a whole.
Keywords: China; alienated politics; labor movement; labour movement; paternalistic state

The Food-Energy-Climate Change Trilemma: Toward a Socio-Economic Analysis - Harvey, Mark (Theory, Culture & Society, 2014)
The food-energy-climate change trilemma refers to the stark alternatives presented by the need to feed a world population growing to nine billion, the attendant risks of land conversion and use for global climate change, and the way these are interconnected with the energy crisis arising from the depletion of oil. Theorizing the interactions between political economies and their related natural environments, in terms of both finitudes of resources and generation of greenhouse gases, presents a major challenge to social sciences. Approaches from classical political economy, transition theory, economic geography, and political ecology, are reviewed before elaborating the neo-Polanyian approach adopted here. The case of Brazil, analysed with an `instituted economic process’ framework, demonstrates how the trilemma is a spatial and historical socio-economic phenomenon, varying significantly in its dynamics in different environmental and resource contexts. The paper concludes by highlighting challenges to developing a social scientific theory in this field.
Keywords: climate change; climatic changes; economic geography; energy consumption; energy shortages; food consumption; food security; instituted economic process; limits to growth; peak oil; political ecology; socioeconomics; sociogenesis

Making Capitalism Fit For Society - Crouch, Colin (John Wiley & Sons, 2014)
Capitalism is the only complex system known to us that can provide an efficient and innovative economy, but the financial crisis has brought out the pernicious side of capitalism and shown that it remains dependent on the state to rescue it from its own deficiencies. Can capitalism be reshaped so that it is fit for society, or must we acquiesce to the neoliberal view that society will be at its best when markets are given free rein in all areas of life? The aim of this book is to show that the acceptance of capitalism and the market does not require us to accept the full neoliberal agenda of unrestrained markets, insecurity in our working lives, and neglect of the environment and of public services. In particular, it should not mean supporting the growing dominance of public life by corporate wealth. The world’s most successful mature economies are those that fully embrace both the discipline of the market and the need for protection against its negative outcomes. Indeed, a continuing, unresolved clash between these two forces is itself a major source of vitality and innovation for economy and society. But maintenance of that tension depends on the enduring strength of trade unions and other critical groups in civil society - a strength that is threatened by neoliberalism’s increasingly intolerant onward march. Outlining the principles for a renewed and more assertive social democracy, this timely and important book shows that real possibilities exist to create a better world than that which is being offered by the wealthy elites who dominate our public and private lives.
Keywords: business & economics; capitalism; economic theory

Spatial egalitarianism as a social ‘counter-movement’: on socio-economic reforms in Chongqing - Lim, Kean Fan (Economy & Society, 2014)
Through a framework drawn from Karl Polanyi's substantivist theorization of economic practices, this paper evaluates the quest for equitable urbanization in Chongqing, a major city-region in south-western China. Illuminating the tensions arising from two interrelated reforms, namely the ambitious attempt to construct 40 million m2of public rental housing between 2010 and 2012, and the large-scale drive to ensure peasant migrants enjoy equal access to social benefits as current urban residents, the paper explains how the quest for equitable urbanization magnifies two nationwide dimensions of institutionalized uneven development, namely (i) the caste-like categorization of populations according to ‘urban’ and ‘rural’; and (ii) the coastal bias in national economic development. The paper concludes that this state-driven pursuit of spatial egalitarianism in Chongqing expresses the dialecticism of economic development in China: it is a social ‘counter-movement’ against the effects of an uneven spatiality that was instituted to drive and deepen the marketization of Chinese society.
Keywords: China; Chongqing; double movement; economic reform; equality; hukou; public welfare; social change; spatial egalitarianism; state–market relations; substantivist; urban–rural integration

Communication Policy and the "Double Movement" - Ashley, Seth (Javnost-The Public, 2014)
Karl Polanyi's concept of a "double movement" has been used to describe the protectionist measures taken by governments to mitigate damage caused by the expansion of markets. Through a lens of political economy and historical institutionalism, this article uses Polanyi's framework to examine competing notions of the public interest as exemplified by the socially constructed nature of American and British broadcasting and the legitimating discourse that produced divergent outcomes. A historical analysis points to a decline of the double movement in communication policy, particularly in the U.S., and lends support to calls for noncommercial, public media structures and increased regulation of communication industries.
Keywords: communication policy; double movement; economic research; institutionalism (religion); marketing research; media system structure; protectionism

Can productivity be socially embedded? Reflections on some productivity measures of 2000s - Kocer, Ruya Gokhan (International Journal of Productivity & Performance Management, 2014)
Purpose – The purpose of this paper is to give an overview of items that are included in recent productivity programmes in various countries and integrate these items with the ideas of virtuous circuit of productivity and socially embedded productivity. Design/methodology/approach – In depth analysis of an illustrative set of productivity measures. The analysis reveals how each measure/programme could make sense to the industrial relations actors. A new conceptual reformulation of analysed measures and programmes. Findings – Bilateral productivity deals between trade unions and employers are not necessarily good from the perspective of national policy making. For this kind of uncoordinated productivity measures, though may be good for individual enterprises, may increase unemployment by pushing other domestic competitors out of the market or compelling them to lay-off workers in a reactive fashion. By drawing on Polanyi, one may argue that it is possible to strike a good balance between productivity concerns and societal interests by embedding the former into the latter. Research limitations/implications – The purpose is to introduce a new conceptualization, thus the empirical material is meant to be illustrative rather than extensive. Originality/value – By using graphical displays and empirical argumentation two new concepts are introduced: first, virtuous circuit of productivity and second, socially embedded productivity.
Keywords: employees; employers; industrial relations research; labor productivity; labor unions; labour productivity; labour relations; labour unions; productivity; research; social embeddedness; social partners

Living permanent liminality: the recent transition experience in Ireland - Szakolczai, Arpad (Irish Journal of Sociology, 2014)
Modernity, or the combination of market economy, liberal democratic polity and a society driven by technological progress, we are led to believe, is the end-state of history; the glorious condition of a fully enlightened society of free citizens equipped with equal rights at which all traditional societies are bound to arrive, after a period of transition which might involve some temporary difficulties or 'sacrifices'. However, and in contrast to this, modernity rather involves an infinite period of transition, in which the stable elements of social life, representing not just rigid external constraints on individual freedom, but also the condition of possibility of meaningful life, are one by one liquidated. This article argues that the anthropological concept 'liminality' is particularly helpful in understanding the formative aspects of transition experiences, like the Celtic Tiger phenomenon in Ireland. It also helps to move beyond the conventional 'transition to modernity' framework by pointing out that advanced modernity is identical to a permanent state of transitionality.
Keywords: FOUCAULT, Michel, 1926-1984; Ireland; POLANYI, Karl, 1886-1964; capitalism; genealogy; liminality; manners & customs; modern society; modernity; technological innovations & economics; tradition; trickster

Different Meanings of ‘Knowledge as Commodity’ in the Context of Higher Education - Kauppinen, Ilkka (Critical Sociology (Sage Publications, Ltd.), 2014)
Commodification has been and still is one of the key processes within capitalist market economies. Since the 1970s, different forms of knowledge have increasingly been subjected to this process. In this paper the commodification of knowledge in the field of higher education is defined in a broad sense as an example of the intensive enlargement of capitalism. I argue that knowledge shares some features of public goods and can be subjected to commodification both as an educational product and academic research itself. However, the simple dichotomy of public vs. private good is not nuanced enough to understand the status of knowledge within higher education. How to reconstruct this dichotomy, whether knowledge should be commodified, and how to justify one’s normative stance in this respect are three important issues for further study.
Keywords: academic capitalism; capitalism; capitalists & financiers; commodification; commodification of knowledge; commodity; higher education; knowledge; public goods

The Return of Karl Polanyi - Somers, Margaret; Block, Fred (Dissent, 2014)
In the first half century of Dissent’s history, Karl Polanyi almost never made an appearance in the magazine’s pages. On one level this is surprising, because Polanyi was a presence in socialist circles in New York City from 1947 through the mid-1950s, the period of Dissent’s gestation. On another level it is unsurprising, in that Polanyi was a heterodox thinker—even among fellow socialists. With some significant exceptions, it has taken decades to recognize the extraordinary theoretical contributions to socialist thought that he made in his masterpiece, The Great Transformation: The Social and Political Origins of Our Time,first published in 1944.
Keywords: Vienna (Austria); democracy; economics; primacy of politics; socialism

The Power of Market Fundamentalism - Block, Fred; Somers, Margaret R. (Harvard University Press, 2014)
What is it about free-market ideas that give them tenacious staying power in the face of such manifest failures as persistent unemployment, widening inequality, and the severe financial crises that have stressed Western economies over the past forty years? Fred Block and Margaret Somers extend the work of the great political economist Karl Polanyi to explain why these ideas have revived from disrepute in the wake of the Great Depression and World War II, to become the dominant economic ideology of our time.Polanyi contends that the free market championed by market liberals never actually existed. While markets are essential to enable individual choice, they cannot be self-regulating because they require ongoing state action. Furthermore, they cannot by themselves provide such necessities of social existence as education, health care, social and personal security, and the right to earn a livelihood. When these public goods are subjected to market principles, social life is threatened and major crises ensue.Despite these theoretical flaws, market principles are powerfully seductive because they promise to diminish the role of politics in civic and social life. Because politics entails coercion and unsatisfying compromises among groups with deep conflicts, the wish to narrow its scope is understandable. But like Marx's theory that communism will lead to a "withering away of the State," the ideology that free markets can replace government is just as utopian and dangerous.
Keywords: United States history; business & economics; economic history; economic policy; economic theory; free enterprise; political economy; political science; public policy; sociology

The Rise and Fall of Ireland's Celtic Tiger: Liberalism, Boom and Bust - Ó Riain, Seán (Cambridge University Press, 2014)
In 2008 Ireland experienced one of the most dramatic economic crises of any economy in the world. It remains at the heart of the international crisis, sitting uneasily between the US and European economies. Not long ago, however, Ireland was celebrated as an example of successful market-led globalisation and economic growth. How can we explain the Irish crisis? What does it tell us about the causes of the international crisis? How should we rethink our understanding of contemporary economies and the workings of economic liberalism based on the Irish experience? This book combines economic sociology and comparative political economy to analyse the causes, dynamics and implications of Ireland's economic 'boom to bust'. It examines the interplay between the financial system, European integration and Irish national politics to show how financial speculation overwhelmed the economic and social development of the 1990s 'Celtic Tiger'.
Keywords: business & economics; economic conditions; economic development; economic history; economic policy; liberalism; political science; public policy

Sociology as a vocation: Moral commitment and scientific imagination - Burawoy, Michael (Current Sociology, 2014)
Public sociology and the sacrifices it entails, richly described in the case studies in this monograph, are driven by moral commitment. This is one element of sociology as a vocation. The other element is sociology as a science. The case studies are built on an embryonic sociology of commodification, understood in its historical dimensions and its global consequences. This sociology of commodification examines the disasters created by third-wave marketization and the bleak future for human existence, thereby, fueling the original moral commitment of public sociology.
Keywords: countermovement; double movement; fictitious commodities; marketization; public sociology

The Debate on Globalization and International Revitalization of Labor. A Critical Review - Fleming, Daniel; Søborg, Henrik (Nordic Journal of Working Life Studies, 2014)
This article discusses some alternative or critical theoretical contributions regarding globalization and labor. The main question in this discussion is if there are changes in direction of a possible revitalization of labor movements and if international solidarity can increase due to globalization. This question also relates to discussions of changes in division of work, the concept of work, working class, commodification, decommodification, and new centers of global production--all related to different paradigms or new concepts. The reason or need for reconceptualizing comes from the great transformation of capitalism in forms of neoliberal globalization, in a different direction than predicted by Polanyi. That is, instead of increased public sector decommodification (not profit- or market-oriented production) and national regulation, embedding capitalist markets, as seen after 1945, the last three decades have witnessed a countertransformation and large-scale recommodification by privatizing, disembedding, and deregulating global markets. As a consequence, inequality in income and working life conditions has increased in most countries and been used to press trade unions. Western industrial unions have been declining as many industries and labor-intensive, low-paid jobs moved to developing countries. Most blue-collar jobs are now in Asia, especially China, with about one-third of its employment blue collars. Is the center of global capital-labor contradictions and dynamics moving to the South, with a possibility of a new revitalization of labor and international solidarity? We discuss different optimistic and pessimistic views on a possible international revitalization of labor.
Keywords: commodification; decommodification; globalization; income distribution; international solidarity; knowledge workers; labor organizing; labour organizing; occupational citizenship; precariat; revitalization of labor; skill capture; work environment; working class; working class concept

The Pyrrhic Triumph of Finance Capital and the Return of Polanyi - Harrison, Trevor W. (Athens Journal of Social Sciences, 2014)
This paper examines the declining support for centrist parties in many western countries. Using the seminal ideas of Karl Polanyi, the paper argues this decline is attributable to the rise of neo-liberal free market policies that have resulted in widespread insecurity and led many voters to seek out political alternatives on the right and left. The paper further examines possible reasons why parties of the right, rather than the left, have been more successful at this historical juncture in channeling political disenchantment.
Keywords: countermovement; fascism; finance capital; neoliberalism

From the Apocalypse to the Revolution - Pellicani, Luciano (Telos, 2014)
The article discusses the emergence of millennialism, which is considered as one of the outcomes of the spiritual victory of Christianity over the Greco-Roman culture. The formulation of the historical-sociological category of cultural catastrophe by Hungarian economic historian Karl Polanyi is tackled. The presence of a divine messenger as one of the three elements of a messianic movement is cited. The concepts of revolutionarism, Jacobinism and Marxism are also addressed.
Keywords: Christianity; POLANYI, Karl, 1886-1964; communism; critical theory; cultural catastrophe; messianism; millennialism

The Renewal of a Critical Theory of Capitalism and Crisis – A Comment on Nancy Fraser’s Interpretation of Polanyi’s works - Deutsche Digitale Bibliothek - Sparsam,, J.; Eversberg, D.; Haubner, T.; Mader, D.; Muraca, B.; Hanno, P. (Working Paper 7/2014 of the DFG-Kollegforscher_innengruppe Postwachstumsgesellschfaten., 2014)
The paper examines Nancy Fraser’s Polanyian reading of the current capitalist crisis and her expansion of Polanyi’s notion of the ‘double movement’–social forces struggling for marketization and social protection– into a ‘triple movement’ by adding the struggle for emancipation as a third factor. In its first part, the paper reviews Fraser’s central arguments with a special focus on her reading of Polanyi’s idea of the “fictitious commodities” land, labor, and money. Second, the authors examine Fraser’s conceptualization of social forces, domination and emancipation drawing on Environmental Philosophy, Political Ecology, Marxism, Feminism, Social Philosophy as well as Polanyi himself. In the end, the paper argues that Fraser’s conception of capitalism and emancipation are in need of improvement if critical theory wants to adequately grasp the current crisis of capitalism.
Keywords: FRASER, Nancy; fictitious commodities; interpretation; triple movement

From Economy to Society: Perspectives on Transnational Risk Regulation - Lange, Bettina; Thomas, Dania; Sarat, Austin (Emerald Group Publishing, 2013)
This special issue asks what role society can play in the regulation of transnational risks, as an alternative to or at least significant addition to reliance on state regulatory activity and the myth of the self-regulatory capacity of markets (Stiglitz, 2001, p. xiii). How can a social sphere contribute to the prevention and management of risks, often transnational in nature, posed by economic activity? Leading socio-legal scholars explore whether and how the idea of harnessing the regulatory capacity of a social sphere provides a new analytical lens that can provide fresh insights into transnational risk regulation, and whether this idea helps to identify innovative approaches to regulating transnational risks. KM - Parts I and II theoretically equgage specifically with Polanyi, and apply and develop Polanyian ideas.
Keywords: administrative law & regulatory practice; commercial law; comparative law; embeddedness; emotions; international law; international trade law; risk; self-regulating market

Transforming Capitalism: The Triple Crisis - Kirby, Peadar (Irish Journal of Sociology, 2013)
This article identifies a triple crisis of capitalism based on the three fictitious commodities as identified by Karl Polanyi: labour, money and land. This framework is used to integrate the environmental crisis into the wider crisis of capitalism. It argues that international actions required to reduce greenhouse gas emissions are going to present major challenges for capitalism with implications for the current dominance of market power and the subservience of state and social power. The article critically examines the potential of climate capitalism to achieve a low-carbon society by 2050 and introduces the need to face the challenges of degrowth.
Keywords: climate capitalism; climate change; de-growth; degrowth; development models; fictitious commodities; sustainability

Capitalism: restless and unbounded? Some neo-Polanyian and Schumpeterian reflections - Harvey, Mark; McMeekin, Andrew (Economics of Innovation & New Technology, 2013)
This paper first explores the notion that the limitlessness of knowledge is a privileged source of the restlessness of capitalism [Metcalfe, J. S. 2001. “Institutions and Progress.”Industrial and Corporate Change10 (3): 561–586; 2002. “Knowledge of Growth and Growth of Knowledge.”Journal of Evolutionary Economics12 (1): 3–13; 2004. “The Entrepreneur and the Style of Modern Economies.”Journal of Evolutionary Economics14 (2): 157–175; 2010. “University and Business Relations: Connecting the Knowledge Economy.”Minerva48 (1): 5–33] when combined with incentives of entrepreneurialism in a market society. Metcalfe gives a central paradigm of evolutionary economics a distinctive turn, with knowledge the pre-eminent source of variation, and markets the primary arena of selection. The paper engages this approach with a neo-Polanyian approach of ‘instituted economic process’, in which the variation and selection dynamic is itself seen as instituted within a particular historical economic context. The paper develops a critique of the evolutionary paradigm firstly by suggesting variations in instituted ‘economies of knowledge’ within a multi-modal conception of capitalism. Further breaking with the bipolar variation-selection paradigm, the paper argues that there has been a significant role of the state as a distinctive source of variation and selection in innovation and economic transformation. This leads us finally to analyse the shifting place of economy in society and polity, and the strategic responses in the USA, Brazil and Europe to the historically novel conjuncture of peak oil and global climate change, as a further source of variation. We conclude that a choice between evolutionary and historical approaches to innovation and economic transformation is a false one, once a universalising and unbounded paradigm of variation and selection is abandoned.
Keywords: SCHUMPETER, Joseph Alois, 1883-1950; capitalism; economic development; entrepreneurship; evolution; evolutionary economics; instituted economic process; mixed economy; multi-modality; organizational change; variation and selection

The Politics of Dispossession: Theorizing India’s “Land Wars” - Levien, Michael (Politics & Society, 2013)
While struggles over land dispossession have recently proliferated across the developing world and become particularly significant in India, this paper argues that existing theories of political agency do not capture the specificity of the politics of dispossession. Based on two years of ethnographic research on anti-dispossession movements across rural India, the paper argues that the dispossession of land creates a specific kind of politics, distinct not just from labor politics, but also from various other forms of peasant politics that have been theorized in the social sciences. It illustrates how the process of land dispossession itself shapes the targets, strategy and tactics, organization, social composition, goals, and ideologies of anti-dispossession struggles. It concludes with reflections on why land conflicts are less easily institutionalized than labor conflicts and may therefore constitute a significantly disruptive force in the emerging centers of global capitalism for the foreseeable future.
Keywords: India; accumulation by dispossession; agrarian change; agriculture; capitalism; eviction; land grabs; peasant politics; peasants; property rights; social movements

From the Great Transformation to the Great Financialization: On Karl Polanyi and Other Essays - Polanyi Levitt, Kari (Zed Books, 2013)
Four years into the unfolding of the most serious crisis since the 1930s, Karl Polanyi's prediction of the fateful consequences of unleashing the destructive power of unregulated market capitalism on peoples, nations, and the natural environment have assumed new urgency and relevance. Polanyi's insistence that 'the self-regulating market' must be made subordinate to democracy otherwise society itself may be put at risk is as true today as it was when Polanyi wrote. Written from the unique perspective of his daughter, From the Great Transformation to the Great Financialization is an essential contribution to our understanding of the evolution and contemporary significance of Karl Polanyi's work, and should be read against the background of the accelerating accumulation of global finance that created a series of financial crises in Latin America, Russia, Asia, and, eventually, the heartlands of capitalism itself.
Keywords: HAYEK, Friedrich A. von (Friedrich August), 1899-1992; Latin America; business & economics; economic conditions; economic development; economic history; global financial crisis; political economy; political science

Polanyi in an Hourglass: The Two Lives of a Sociological Classic - Frerichs, Sabine (Studies in Law, Politics & Society, 2013)
This article aims to show that studies of transnational risk regulation can benefit from Polanyian and neo-Polanyian research agendas in the field of law, economy, and society. Risk regulation would then be under-stood as a corrective force within the market society. Drawing on the relevant literature in the field, Karl Polanyi's work is contextualized both in the past ("scholarship before and beside Polanyi") and in the present ("scholarship after and beyond Polanyi"). The review considers developments within sociology, its neighboring disciplines economics and jurisprudence, and the interdisciplinary research fields of "economy and society," "law and society," and "law and economy." The article demon-strates that Polanyi is a "late classic" who shares the holistic orientation of classical historical scholarship. At the same time, it is argued that his "early revival" is due to the topicality of his criticism of the market society, and its inherent risks, in an era of neoliberalism and globaliza-tion. By going back and forth in time, the article situates Polanyi in a line of holistically minded scholarship that combines insights of general, economic, and legal sociology in what can be called the "economic sociol-ogy of law." This is "old" and "new," at the same time.
Keywords: classical sociology; contemporary sociology; economic sociology; economic sociology of law; general review; interdisciplanary research; law and economics; market society; neoliberalism; risk regulation; sociological research

After a Romantic Aspiration to Society: Harnessing the Regulatory Capacity of a Social Sphere - Lange, Bettina (Studies in Law, Politics & Society, 2013)
This introduction unpacks the key question that informs the articles in this special issue. How does a social sphere inform regulation and, more specifically, how can the regulatory capacity of a social sphere be har-nessed, as an alternative or significant complementary force to state reg-ulation and reliance on the self-regulatory capacity of markets? This question is salient and topical also in light of the search for new regula-tory strategies and perspectives in the aftermath of the 2007 financial and subsequent EU sovereign debt crises, which have led to a major rea-lignment of economy and society in a number of countries. This introduction argues that economic sociology is a crucial reference point for understanding more about the social practices that constitute business behavior. It enables to explore the scope and significance of often interlinked social and legal norms for regulating various transna-tional risks that economic activity can give rise to. The introduction therefore locates the quest for understanding more about the regulatory capacity of a social sphere in debates that draw on Karl Polanyi's analy-sis of the embedding, disembedding, and re-embedding of economic activ-ity into social norms. The introduction highlights one of the key themes developed in this special issue, the idea of society within economy which questions an assumed conceptual distinction between economy and society. This introduction concludes by specifying how the accounts of risk regu-lation developed in this special issue chart a path that is different from recent explorations of the role of a social sphere in regulation, which were conducted under the banner of "the sociological citizen," "regula-tory sociability," and "collaborative governance."
Keywords: European Sovereign Debt Crisis, 2009-; European Union; crisis; economic sociology; economic sociology of law; financial crisis; international business enterprises; regulation; social sphere; socio-legal studies; state regulation; transnational risk

From Polanyi to Discourse Theory - Lange, Bettina (Studies in Law, Politics & Society, 2013)
This article starts from the assumption that economic sociology, including Karl Polanyi's work, can contribute fresh perspectives to regulation debates because it opens up new understandings of the nature of economic activity, a key target of legal regulation. In particular this article examines Polanyi's idea that society drives regulation. For Polanyi the "regulatory counter-movement" is society's response to the disembedding -- in particular through the proliferation of markets -- of economic out of social relationships. Section One of the article identifies three key chal-lenges that arise from this Polanyian take on regulation for contempor-ary regulation researchers. First, Polanyi focuses on social norms restraining business behavior, but neglects social norms embedded in law as also shaping regulation. Second, he seems to imply a clear-cut concep-tual distinction between "economy" and "society." Third, his analysis sidelines the role of interest politics in the development of regulation. Addressing the first of these three key challenges, Section Two of this article therefore argues that a Polanyian vision of "socialized" legal reg-ulation should build on contemporary accounts of responsive law and reg-ulation, which focus attention on social norms informing legal regulation. Section Three of this article tackles the second key challenge raised by Polanyi's work for contemporary regulation researchers, that is, how to transcend a modernist perspective of "economy" and "society" as clearly demarcated, distinct fields of social action. It argues that discourse the-ory is an important alternative theoretical resource. Drawing on Laclau and Mouffe, the article suggests that understanding "economy" and "society" as performed by open and relationally constructed discourses helps to capture interconnections between "economy" and "society" that become particularly visible when we analyze how specific regulatory regimes work at a medium- and small-scale level. These points are further brought to life in Section Four through a discussion of the European Union (EU) regulatory regime for trade in risky, transgenic agricultural products, and in particular the current reform debates about the consideration of the "socioeconomic impacts" of such products.
Keywords: European Union; European Union regulation; discourse theory; economic sociology; embeddedness; embedding theorems; responsive regulation; socio-economic impacts; socioeconomics; transgenic agricultural products

A Systems Theory Perspective on Polanyi's Great Transformation: The Case of Financial Derivative Contracts - Paterson, John (Studies in Law, Politics & Society, 2013)
Whereas much of the renewed interest in Polanyi's Great Transform-ation speculates that the rebalancing of economy and society he foresaw might now be emerging in the context of the financial crisis, the systems theory perspective adopted in this article concludes that there are good reasons to believe that such a shift may be no closer. From an examina-tion of credit default swaps and corporate bonds, the article suggests that finance may best be understood as an internally differentiated subsystem of the economy and thus perhaps peculiarly proof against efforts to exert control over it. Concluding that Polanyi's analysis lacks the conceptual tools to cope with contemporary conditions when compared to systems theory, the article nevertheless suggests that his approach may usefully be extended by adding a fourth fictitious commodity - risk -- to the familiar trio of land, labor, and money.
Keywords: POLANYI, Karl, 1886-1964; contracts; corporate bonds; derivatives; economic aspects; economic sociology; economy; markets; prices; society; swaps (finance); systems theory

Trust and Regulation: Insights from the Mining Industry - Schiavi, Petrina (Studies in Law, Politics & Society, 2013)
This article develops Polanyi's (2001) theme of harnessing the regula-tory capacity of a social sphere by focusing on trust as an emotion for framing risk regulatory regimes. Using the global mining sector as its focus, it explores the role of trust in the regulation and corporate man-agement of social and environmental risk Sociological perspectives on trust are employed to identify and analyze dynamics of trust in the mining industry. The article draws on data col-lected between 2004 and 2008 by way of participant observation, docu-ment analysis, and in-depth qualitative interviews with around 40 representatives of the mining industry, NGOs, and regulators. Trust-rela-tionships are an example of harnessing the regulatory capacity of a social sphere, but they can also undermine regulatory effort where trust is abused. The effectiveness of trust-based regulation would be enhanced by sanctions for nonperformance that target corporate motivations and financial performance. This research focused on a selection of large, multinational mining corporations with a presence in Australia. Generalizations could not be made from this research about smaller mining entities or single-country or state-owned corporations. A better understanding of corporate trust-building behaviors and motiva-tions can help inform more effective regulatory strategy for improving corporate, social, and environmental impacts. This article contributes to the body of knowledge about the regulation of the social and environmen-tal performance of the mining industry. This is important as many of the remaining accessible mineral deposits across the globe are in areas of environmental and social significance.
Keywords: POLANYI, Karl, 1886-1964; corporate responsibility; delegated legislation; environmental risk assessment; financial risk; mineral industries; mining industry; regulation; risk; social responsibility of business; trust

"Etiquette and Magic": Between Embedding and Embedded Corporate Social Responsibility - Voiculescu, Aurora (Studies in Law, Politics & Society, 2013)
This article looks at corporate social responsibility (CSR) as a discur-sive social practice that attempts to interrogate the global market econ-omy and its neoliberal underpinnings and that reflects as well as frames and shapes domestic and global politics and institutions. Drawing upon Karl Polanyi's notions of reciprocity and redistribution while also emphasizing the normative content of the concept, the article inquires into the position that the CSR discourse occupies in addressing the cor-porate transnational risks derived from social tensions and conflicts and more generally, in answering social expectations for justice. The Polanyian perspective highlights the CSR discursive quest for a missing conceptual consistency and implicitly, for a constructive "critical" core. From this perspective, the article shows CSR to reside within controver-sial conceptual boundaries; a discursive social practice that engages with the social aspiration of embedding market economy in society while it is also in need of reclaiming its critical core and its potential for social change.
Keywords: civil economy; corporate social responsibility; embedding theorems; neoliberalism; reciprocity (commerce); reciprocity and redistribution; social change; social embeddedness; social responsibility of business; socio-legal studies

The Institution, the Economy and the Market: Karl Polanyi's Institutional Thought for Economists - Maucourant, Jerome; Plociniczak, Sebastien (Review of Political Economy, 2013)
This paper aims to clarify the logical structure of Karl Polanyi's concept of institution, especially with regard to his most important contribution to political economy—the conception of self-regulating markets as institutions. Although Polanyi did not provide a well-developed concept of institution, this article argues that such a concept exists in his work. Moreover, there is in Polanyi's work a sophisticated institutionalist account of the self-regulating market that has been largely overlooked as Polanyi does not present it explicitly. Analyzing the economy as an institutionalized process, as Polanyi does, reveals that the market is neither a natural nor a spontaneous phenomenon—a conclusion that runs counter to conventional economic thinking. Polanyi's approach enables us to view capitalism (the ‘market society’ in Polanyi's language) through a highly specific cultural fact: the fiction of the self-regulating market. This institutional perspective needs to be reassessed beyond new-institutionalist theoretical constructions.
Keywords: economic structure; free enterprise; institutions (philosophy); philosophy of economics; social facts

Rudderless in a Sea of Yellow: The European Political Economy Impasse for Renewable Transport Energy - Harvey, Mark; Pilgrim, Sarah (New Political Economy, 2013)
Faced with the twin challenges of anthropogenic climate change and ‘peak oil’, the need for an urgent and radical transformation of transport energy has been widely recognised. Adopting a neo-Polanyian economic sociology approach, this article asks what conditions European governance capacity to respond to these challenges, at either national or regional levels, using biofuels as a case study. It asks if the complexity of its political institutions, and the heterogeneity of interests and economic organisations, present ‘the biggest obstacle of all’ (Cohen 2007) to reduce fossil fuel dependency. By examining the European Commission level and comparing five countries, evidence is produced for a political failure in terms of continued fossil fuel dependency. Incumbent interests in the agricultural sector and a distinctively European legacy of a transport fleet dependent on fossil diesel, have led to a marriage of convenience between rapeseed farmers and vehicle manufacturers. As a consequence, rather than escaping from the path dependency on fossil fuels (Unruh 2000), Europe has gone down a cul-de-sac of rapeseed biodiesel inherently limited in scope, and with the low levels of greenhouse gas emissions savings. Ironically this outcome is in part an unintended consequence of opposition to biofuels from environmentalist groups and politics.
Keywords: agriculture; biodiesel fuels; biofuels; biomass energy research; climate change; climate change research; economics; peak oil; politically instituted markets; rapeseed

Towards an Economic Sociology of Law - Ashiagbor, Diamond; Kotiswaran, Prabha; Perry-Kessaris, Amanda (Wiley-Blackwell, 2013)
Reflecting a developing trend towards interdisciplinary research in economics and law, this agenda–setting volume makes the case for economic sociology of law  an emerging field that draws on empirical, analytical and normative insights from sociology to investigate relationships between legal and economic phenomena. It locates this novel subject in a wider socio–legal tradition and identifies common ground between Polanyian and Weberian approaches to the law, economy, and society, despite the two theorists  divergent views on the functionality of the capitalist model. The volume provides a platform for researchers critical responses to the social embeddedness of market societies. Contributors demonstrate the value of applying a combination of methods in their work, from heterogeneous disciplines such as legal history and ethnography. They consider the position in the western and developed nations, as well as in post–colonial polities. The resulting publication is a well–crafted primer on a specialism that, by combining the insights of socio–economic analysis with the formative influences exerted by their specific legal contexts, informs a more nuanced assessment of law, economics and society.
Keywords: WEBER, Max, 1864-1920; economic sociology; economic sociology of law; law

Rethinking ‘Embeddedness’: Law, Economy, Community - Cotterrell, Roger (Journal of Law and Society, 2013)
Ideas (of Karl Polanyi and others) that economies and markets are ‘socially embedded’ are central to recent research in economic sociology, closely paralleling socio-legal claims for studying law in ‘social context’. But the concept of embeddedness is imprecise and inadequate: a sociology of law and economy cannot rely on it but must address intellectual and moral-political concerns that its use reflects. Max Weber's writings on law and economy have inspired advocates of a new economic sociology of law, but some of Weber's key claims may be outdated, and he treats law and economy as distinct spheres rather than as facets of the social. Sociological research on law and economy should focus on ‘networks of community’ and their regulation, thus illuminating the social character of both law and economic relations. Viewing the social (including economic life) through a ‘community lens’ makes it possible to analyse cultural factors in regulating markets, while emphasizing links between economic relations and other aspects of social life.
Keywords: embeddedness

Law, Social Policy, and the Constitution of Markets and Profit Making - Veitch, Kenneth (Journal of Law and Society, 2013)
This article explores the relationship between law, society, and economy in the context of the contemporary British welfare state. Drawing on themes in Polanyi's The Great Transformation, it identifies the constitutive role of contemporary social policy and law in the creation and maintenance of markets and opportunities for the private sector in the field of welfare, focusing on the institutional mechanisms being put in place to encourage this. What emerges is a reformulation of the function of the welfare state and related law, as these are no longer predominantly driven by a logic of social protection via redistribution to those in need, but increasingly reflect the state's desire to create openings for the private sector within welfare. The institutions that once contributed to ensuring the embeddedness of the market economy in society now play an important role in processes of disembedding – with potentially detrimental consequences for those seeking assistance from the welfare state.
Keywords: Great Britain; disembeddedness; welfare state

A More Perfect Commodity: Bottled Water, Global Accumulation, and Local Contestation - Jaffee, Daniel; Newman, Soren (Rural Sociology, 2013)
Bottled water sits at the intersection of debates regarding the social and environmental effects of the commodification of nature and the ways neoliberal globalization alters the provision of public services. Utilizing Polanyi's concept of fictitious commodities and Harvey's work on accumulation by dispossession, this article traces bottled water's transformation from elite niche item to a product consumed by three fourths of U. S. households. Drawing on ethnographic research with participants in two cases of proposed spring water extraction from rural communities by industry leader Nestlé Waters, we make two principal arguments. First, the case of bottled water necessitates a reevaluation of existing theoretical frameworks regarding water privatization and commodification. Municipal tap water networks pose substantial barriers to capital accumulation, leading one influential scholar to frame water as an 'uncooperative commodity.' However, bottled water's characteristics enable it to evade many of these constraints, rendering it a 'more perfect commodity' for accumulation. Second, expansion of the market good of bottled water alters the prospects for the largely publicly provided good of tap water. We conclude that the growth of this relatively new commodity represents a more serious threat to the project of universal public drinking water provision than that posed by tap water privatization.
Keywords: HARVEY, David; bottled water; commercial products; drinking water; ethnographic analysis; fictitious commodities; globalization; households; municipal services; primitive accumulation; privatization; research

Decommodification and Welfare State: the Case of Workplace Accident Victims - Tabin, Jean-Pierre; Probst, Isabelle; Waardenburg, George; Dransart, Dolores Angela Castelli; Pasche, Geneviève; Bolzman, Claudio (Dekommodifizierung und Wohlfahrtsstaat: der Fall von Opfern von Arbeitsunfällen., 2013)
To what extent does the social treatment of workplace injury in Switzerland enable victims to be decommodified in the sense given by Gøsta Esping-Andersen (1990) to this concept, i.e. enable them to leave the labor market in a way that allows them to uphold a socially acceptable standard of living? After a sociological discussion about the concept of decommodification, we present the results of a qualitative study conducted in Switzerland about workplace accident victims and show that the kind of index proposed by Esping-Andersen in order to compare welfare states is based on a faulty premise. (English)
Keywords: Arbeitsunfall; POLANYI, Karl, 1886-1964; Schweiz; Suisse; Switzerland; Wohlfahrtsstaat; accident du travail; accident insurance; commodification; cost & standard of living; decommodification; dekommodifizierung; démarchandisation; kommodifizierung; labor laws & legislation; labour laws & legislation; marchandisation; qualitative research; welfare state; work-related injuries; workplace accident; état social

Karl Polanyi - Vail, John (Routledge Studies in Social and Political Thought, 2013)
Keywords: business & economics / economics / theory

Nationalist Politics and the Double Movement: The Problem of Legitimacy in Neoliberal States - Blad, Cory (2013)
This paper argues that the contemporary efficacy of nationalist politics is a strategic response to neoliberal conditions of state legitimation. Using the double movement as a theoretical framework, I argue that neoliberalism alters the policy alternatives available to state actors by reducing the viability of economic protectionist initiatives once dominant in the embedded liberal era. This policy capacity reduction inhibits some of the key means for state legitimation (e.g., public spending, regulatory protectionism), which exacerbate the negative effects of capitalist liberalization. As national populations view the state as unwilling or unable to mitigate economic adversities or provide traditional socio-economic services, significant potential exists for a delegitimation of state actors and institutions. In response, neoliberal state actors have gravitated toward an increasingly cultural rhetoric of nationalism as a means to maintain popular legitimacy. This shift goes beyond simple political power struggles - in accordance with the double movement framework, systemic global capitalism requires legitimate state authority to ensure both local stability and sustained capital accumulation. Neoliberal ideology, however, discourages traditional means of state legitimation. A Polanyian examination of this ironic condition offers a structural explanation for the increased efficacy of nationalist politics; however, it also raises serious questions about the sustainability of this legitimation strategy.
Keywords: double movement; globalization; nationalism; neoliberalism; state legitimation

Economic support personal networks of rural entrepreneurships - Cid-Aguayo, Beatriz E.; Sandoval-Nazal, Daniel; Carrasco, Juan Antonio (2013)
The Polanyian discussion about the embeddedness of the economy in social relations, finds a new stream through the social network analysis, from which is possible to map the cooperation relations that underlie economic ones. From the latter, this article shows the analysis of nine family-based economic entrepreneurships linked to a cooperative of services and agrofood products. Through personal networks analysis we mapped and highlighted the diversity of collaborations, monetary and non-monetary exchanges the entrepreneurships perform with their networks. In consequence, we characterized the support networks identifying the different economic exercises that take part in relation to the entrepreneurships. By this way, we accounted some relevant aspects such as the formality or informality condition, the entrepreneurships level, the networks' cohesion and the types of exchange, among other issues.
Keywords: embeddedness; rural entrepreneurships; social networks

Marxism After Polanyi - Burawoy, Michael (Marxisms in the 21st Century: Crisis, Critique and Struggle, 2013)
KM - What should we do with Marxism ? For most the answer is simple. Bury it ! Mainstream social science has long since bid farewell to Marxism. The approach adopted here is that Marxism is a living tradition that enjoys renewal and reconstruction as the world it describes and seeks to transform undergoes change ... However, Marxsm cannot simply mirror the world. It seeks to change the world, but changing such a variegated world requires a variegated theory that keeps up with the times and accommodates places.
Keywords: MARX, Karl, 1818-1883; Marxism; fictitious commodities

Europe and Problems of Marketization: from Polanyi to Scharpf - Crouch, Colin (Firenze University Press, 2013)
The author uses the theory of the 'Great Transformation' of the industrialisation of England developed by Karl Polanyi to describe the current situation in Europe. There is a strong marketisation of the economy and also of social life, but what is missing is the social policy that needs to accompany this process, if there are not to be major problems. From this perspective marketization and social policy do not exist in a zero-sum game, but are mutually dependent. The emphasis on negative rather than positive integration (to use the terms conceived by Fritz Scharpf) in the development of Europe makes this interdependence more difficult to achieve. The division of competences between the European level (market policies) and the nation states (social policies) makes this situation even worse. The only way forward is a strengthening of the European social dimension.
Keywords: Europe; business & economics; commodification; economic theory; social policy

Insurgency and institutionalization: the Polanyian countermovement and Chinese labor politics - Friedman, Eli (Theory and Society, 2013)
Why is it that in the nearly 10 years since the Chinese central government began making symbolic and material moves towards class compromise that labor unrest has expanded greatly? In this article I reconfigure Karl Polanyi's theory of the coutermovement to account for recent developments in Chinese labor politics. Specifically, I argue that countermovements must be broken down into two constituent but intertwined "moments": the insurgent moment that consists of spontaneous resistance to the market, and the institutional moment, when class compromise is established in the economic and political spheres. In China, the transition from insurgency to institutionalization has thus far been confounded by conditions of "appropriated representation," where the only worker organizations allowed to exist are those within the state-run All China Federation of Trade Unions. However, in drawing on two case studies of strikes in capital-intensive industries in Guangdong province, I show that the relationship between insurgency and institutionalization shifted between 2007 and 2010.
Keywords: ACFTU; China; countermovement; economic capital; insurgency; labor; labour; social movements

Mechanism of Governance of Economic Relations - Rus, Andrej (Teorija in Praksa, 2012)
The problem of the governance of economic transactions arises from the fact that they are sequential. This creates uncertainty regarding the fulfilment of implicit or explicit contracts. Institutional economics understands this uncertainty as arising from opportunism and seeks a solution in specialised contract enforcement institutions. Economic sociology understands the uncertainty as a result of misunderstanding and finds a solution in mechanisms of governance that, in addition to sanctions, allow for coordination among participants in a transaction. In this paper, we confront the arguments made by sociology and economics regarding the mechanism of governance of economic transactions. Following Polanyi, we distinguish three governance mechanisms of economic relations and note that, to be operational, each of them requires a different social structure and social regulation.
Keywords: economic activity; economic sociology; economics; governance mechanisms; institutional economics; social structure; socioeconomics

Polanyi defanged - Turner, Stephen (Social Studies of Science (Sage Publications, Ltd.), 2012)
A literary criticism of the book "Michael Polanyi and His Generation: Origins of the Social Construction of Science," by Mary Jo Nye is presented. The author discusses the significance of Michael Polanyi in the history of science studies and provides insight on his life and his relationship with his brother Karl. He analyzes how the book presents the origins of science studies, Polanyi’s activities as an economist, and his fight against Communism.
Keywords: Dahomey and the Slave Trade; James Bryant Conant; Karl Polanyi; Michael Polanyi & His Generation: Origins of the Social Construction of Science (Book); NYE, Mary Jo; POLANYI, Michael, 1891-1976; communism & science; economists; planning of science; science - study & teaching

A second double movement? Polanyi and shifting global opinions on neoliberalism - Levien, Michael; Paret, Marcel (International Sociology, 2012)
Karl Polanyi’s theory of the ‘double movement’ has gained great currency in recent years to explain the global growth of contemporary social movements resisting neoliberalism. However, there has been no statistical research demonstrating whether these protest movements represent a more general trend of growing discontent with ‘disembedding’ markets from public control. This article uses questions from the World Values Survey to construct an ‘embeddedness’ index measuring public opinion on the desired relationship between states and markets. Focusing on public opinion in 20 countries during the 1990s, the analysis poses three questions: First, is there evidence of increasing global support for ‘re-embedding’ markets? Second, how does such opinion vary across regions of the world? Finally, what is the class and gender composition of this latent countermovement? The results provide substantial evidence of an emerging countermovement in public opinion over the 1990s with complex class, gender, and geopolitical variation.
Keywords: countermovement; double movement; embeddedness; neoliberalism

Consumer markets and national income inequality: A study of 18 advanced capitalist countries - Kollmeyer, Christopher (International Journal of Comparative Sociology (Sage Publications, Ltd.), 2012)
Sociologists have paid scant attention to the possibility that the structure of the macro-economy is an important determinant of income inequality. Although prior research finds negative links between the size of the public sector and income inequality, no study to date considers whether the size of consumer markets has distributional consequences as well. To investigate this possibility, the present study measures the size of national consumer markets with the System of National Accounts used by governments to calculate gross domestic product (GDP). Based on data from 18 advanced capitalist countries over nearly a 40-year period, two-way random effects regression models reveal a strong and positive link between the size of consumer markets and income inequality. This finding is robust to the inclusion of numerous control variables, and to the consideration of endogeneity within the causal relationship. The proposed theoretical explanation centers on ideas developed by Polanyi, and suggests that economic activity in consumer markets creates higher levels of individual differentiation, and hence higher levels of income inequality, than economic activity in other sectors of the economy. The study concludes by highlighting ways future research can advance our theoretical and empirical understanding of this topic.
Keywords: Keynesian economics; Keynesianism; consumer goods; consumer markets; distributive justice; economic aspects; economic sociology; equality - economic aspects; income distribution; income inequality; markets - social aspects; research; social classes; social stratification

Problems and opportunities in Polanyian analysis today - Holmes, Christopher (Economy & Society, 2012)
The three books under review in this article all demonstrate the beginnings of a shift in the tone of literature on or derived from the work of Karl Polanyi. On one hand, the authors all show a willingness to admit a variety of problems and weaknesses in his work. But on the other hand, it is precisely this degree of critical introspection that enables the authors under review to identify some of the most important and contemporarily relevant aspects of Polanyi's thought. In the two main sections of this article – on Polanyi's concepts of ‘embeddedness’ and ‘double movement’ – I define the problems highlighted in previous iterations of Polanyian literature, moving on to examine how the texts under review address those problems, laying particular emphasis on the ideational components of Polanyi's thought. I conclude by suggesting future directions for Polanyian scholarship, mooting the possibility of a distinctively ‘post-Polanyian’ perspective in which ideas, discourse and framing are placed centre stage.
Keywords: DALE, Gareth; HANN, Chris; HART, Keith; Karl Polanyi: The Limits of the Market (Book); Market & Society: The Great Transformation Today (Book); book review; discourse; double movement; economic anthropology: history, ethnography, critique; economic ideas; embeddedness; nonfiction; post-Polanyi

Development Theory and the Constitution of Market Society: A Polanyian View - Scott, Alan (Comparative Sociology, 2012)
Abstract This paper argues that development studies could benefit from a closer engagement with the arguments of Karl Polanyi. Firstly, a Polanyian perspective gives greater weight to non-economic and non-material factors in making, maintaining and modifying markets. Secondly, it focuses research on the problematic, state- sponsored and contested process of bringing the market actor into being. Finally, a Polanyian approach might better link a, broadly speaking, leftist analysis to 'real world' policy debates about the relative balance between market freedoms and regulation. The conclusion elaborates this final point.
Keywords: POLANYI, Karl, 1886-1964; development; disembedding and reembedding; economic development; financial crises; globalization; market making and modifying; mixed economy; neoliberalism; regulation

Economic and Ecological Crises: Green new deals and no-growth economies - Jessop, Bob (Development, 2012)
Bob Jessop applies cultural political economy to the global economic and ecological crisis. He presents theoretical preliminaries concerning economic and ecological imaginaries, and then goes on to highlight the multidimensional nature of the current crisis and struggles over its interpretation.
Keywords: cultural political economy; ecological imaginary; economic imaginary; finance-dominated accumulation; finance-led accumulation; green new deal; neoliberalism; post-neoliberalism

A Polanyian Analysis of Capitalism: A Commentary on Fred Block - Bandelj, Nina (Political Power & Social Theory, 2012)
This chapter responds to Fred Block's article about the weaknesses of the concept of capitalism because of its close association with Marxism, and his proposal for a Polanyian analysis of political economy. In this chapter, I interrogate what may be the commonalities as opposed to divergences between Marx and Polanyi, and I question whether the concept of capitalism is really so wedded to Marxism so as to loose its analytic value, and be better replaced by notions such as market society, or political economy, as used by Polanyi. I agree with Block that a Polanyian analysis importantly widens our view beyond economic reductionism to an understanding of economy and society as co-constitutive. However, I see utility in adding the qualifier "capitalist" to "political economy" to differentiate between socialist and capitalist political economies, for instance, and to properly characterize a system based on private property rights, guided by pursuit of material gain, which advantages some strata in society more than others, leading to endemic social inequality. I propose that a Polanyian focus on society and economy as co-constitutive is more effectively coupled with an analysis that considers capitalism not as a self-driven system of surplus extraction and accumulation, but as an institutional order dependent on political choices. Such a perspective would advance a Polanyian analysis of capitalism.
Keywords: BLOCK, Fred L.; Marxist philosophy; capitalism; economics; equality; market society; political economy; political science

Varieties of What? Should We Still Be Using the Concept of Capitalism? - Block, Fred (Political Power & Social Theory, 2012)
This article argues that social scientists should reconsider the analytic value of the term "capitalism." The paper argues that the two most coherent definitions of capitalism are those derived from classical Marxism and from the Worm System theory of Immanuel Wallerstein. Marx and Engels' formulation was basically a genetic theory in which the structure of a mode of production is determined by the mode of surplus extraction. During the course of the 20th century, however, Marxist theorists had to modify this framework and the result has been an uncomfortable hybrid. Wallerstein resolved these tensions by redefining capitalism in terms of the logic of a worm system. However, his argument has difficulty in explaining the consequential variations over time in the specific rules and institutional structures that operate at the global level. The article goes on to argue in favor of Karl Polanyi's concept of market society because it focuses attention on the political governance of market societies at both the national and the global levels.
Keywords: Marxist philosophy; capitalism; mixed economy; political science; public administration; variational principles

Double movements and pendular forces: Polanyian perspectives on the neoliberal age - Dale, Gareth (Current Sociology, 2012)
In the neoliberal era, Karl Polanyi’s notion of the ‘double movement’ has been widely deployed by social scientists as a critique of the prevailing order and a predictor of its demise. This article presents the double movement theorem, drawing upon Polanyi’s published and unpublished writings. It explores parallels between his explanation of the advent of the 19th-century free-market regime in Britain and recent Polanyian accounts of the rise of neoliberalism. Following an analysis of the ‘pendular’ refunctioning of Polanyi’s thesis, it closes by asking whether the recent global financial crisis heralds a pendulum swing from neoliberalism (or ‘market fundamentalism’) towards a form of socially coordinated capitalism, or towards ‘more of the same’. As of 2011, it appears that neoliberal policy and ideology remain hegemonic, not in reinvigorated form but as an ‘undead’ policy regime, one that has spawned a burgeoning literature on ‘zombie capitalism’ and ‘zombie neoliberalism’.
Keywords: Great Britain; Great Britain - economic conditions - 19th century; crise financière; crisis financiera; double movement; financial crises; financial crisis; free enterprise; international competition; mouvement double; movimiento doble; neoliberalism; neoliberalismo; néolibéralisme; social scientists; zombi; zombie

Marx, Weber, and the "Ceaseless Accumulation of Capital." - Ho-Fung Hung (Political Power & Social Theory, 2012)
Seeing capitalism as a system defined by the imperative of the ceaseless accumulation of capital, instead of using the definition based on wage labor or international trade as Block questions, I argue that the concept of capitalism is still too useful to be abandoned, and cannot be replaced by the Polanyian concept of market in our critique of political economy. As Fernand Braudel and Giovanni Arrighi contend, the capitalist logic of capital accumulation, which is affined to monopoly and state power, is antithetical to the logic of market exchange, which is decentralized and prioritizes livelihoods over profits. Historically, capitalism sometimes made use of the market and sometimes subjugated the market to facilitate accumulation. Likewise, globalization today is a combined movement of expanding free market in certain aspects of life through financial deregulation, privatization, trade liberalization, etc. on the one hand, and exclusion of various processes and costs outside the market through revival of extra-economic coercion, externalization of environmental costs, etc., on the other hand. The imperative of capital accumulation drive capitalists and capitalist states to foster marketization and demarketization in different times and spaces. The critique of and resistance to our capitalist system needs to be antimarket in some instances and pro-market in others. A Polanyian critique of the free market is surely powerful and helpful, but it is not enough for our full understanding of the economic malaises of our times. It is at best counterproductive to throw away the concept of capitalism altogether.
Keywords: ARRIGHI, Giovanni; BLOCK, Fred; BRAUDEL, Fernand, 1902-1985; capitalism; economics; globalization; international trade; wages

Dispossession, Class Formation, and the Political Imaginary of Colombia's Coffee Producers Over the Longue Durée: Beyond the Polanyian Analytic - Hough, Phillip A.; Bair, Jennifer (Journal of World-Systems Research, 2012)
For more than a decade, social scientists have been analyzing the implications of the neoliberal turn in development policy and the implications of market-led agrarian reform for agricultural producers in the global South. Among this work is a spate of recent scholarship celebrating a number of flagship movements, such as the Zapatistas in Mexico or the landless movement in Brazil, which are interpreted as efforts by rural communities to resist the threat posed by the commodification of livelihoods and the privatization of natural resources. In this article, we aim to problematize what we diagnose as the "Polanyian analytic" underlying accounts of the current conjuncture which emphasize the imminent potential of neoliberalism to spawn protective counter-movements of the sort described in The Great Transformation. We do so through an analysis of the Unidad Cafetero Nacional (UCN) movement, an organization of Colombian coffee farmers that effectively mobilized large numbers of cafeteros in the 1990s to protest the liberalization of the global coffee market and the decline of state support for the domestic coffee sector. While the UCN may be read as a struggle to resist the dispossession of Colombian coffee farmers, we argue that it represented a particular segment of rural producers who wanted, first and foremost, a restoration of their relatively privileged status within the political economy of Colombian agriculture. Our interpretation of the UCN suggests that whether movements emerge in response to neoliberalism depends on the political imaginaries of the social actors who would create them, and further, that these imaginaries are produced through processes of class formation over the longue durée that shape the meaning of dispossession in particular contexts.
Keywords: Colombia; agriculture; coffee growers; coffee plantations; commodification; liberalization (finance); neoliberalism; privatization

On Fred Block, Varieties of What? Should We Still Be Using the Concept of Capitalism? - Streeck, Wolfgang (Political Power & Social Theory, 2012)
There are good reasons for preferring the concept of capitalism over that of "market economy." A capitalist economy is one that depends on the commercialization-through-monetarization of ever more social relations. The result is disequilibrium as the normal condition of a society placed under pressure by its "economy" for continuous reorganization in line with a need for ongoing capital accumulation. A capitalist society enlists the possessive individualism of its members as its principal vehicle of social progress, measured as an increase in wealth-as-money. While Polanyian theory has pointed out important features of advanced capitalist societies, there is no need to sacrifice core Marxian concepts for it. Marxian theory helps avoid the trap of political voluntarism, which stipulates a priority of politics in the capitalist political economy or a fundamental difference between "varieties" of capitalism. Moreover, rather than regarding the capitalist economy as by definition "always embedded," political-economic theory must allow for a self-destructive, and indeed socially destructive, tendency of capitalist political economies to "disembed" themselves by struggling free from social controls and dictating to social life the imperatives of market efficiency and a market-conforming distribution of life chances.
Keywords: BLOCK, Fred L.; Marxist philosophy; always embedded economy; capitalism; equilibrium (economics); saving and investment; social control; social theory; varieties of capitalism

Fight or Acquiesce? Religion and Political Process in Turkey's and Egypt's Neoliberalizations - Tuğal, Cihan (Development & Change, 2012)
The Polanyian expectation that disruptive marketization will lead to movements and policies that seek to 'embed' the market in society needs to be tempered by closer scrutiny to historical, religious and political contexts. This article studies how movements respond to marketization. The analysis proceeds through a comparison of the Turkish and Egyptian neoliberalizations, religious movements of the last decades, secular opposition, and finally recent processes, which have led to generally different social takes on neoliberalism. The irony of the Turkish case is that with the empowerment of the Islamists, religious opposition to neoliberalism was muted and secular opposition further marginalized and labelled as 'anti-democratic'. As a result, free market policies were not only sustained, but deepened and intensified, turning Turkey into a neoliberal 'success story'. The (thus far) sustained mobilization of youth and labour in Egypt makes a direct imitation unlikely. Another major factor that would prevent a 'Turkish' solution to Egypt's crisis is the contrasting structure of the religious fields. Moreover, while the passive revolution has further solidified the professional and unified religious field in Turkey, the revolutionary process in Egypt seems to reinforce the fragmentation of the religious field. The article points out that making Islam compatible with neoliberalism would be more difficult in a country with a fragmented religious field, such as Egypt. Although neoliberalism was imposed from above and resisted from below in both nations, in Turkey it came to be embraced in the name of Islam and democracy, whereas in Egypt it remains an imposition and popular struggles against it persist. It is suggested that this process and field-based approach to a Polanyian problem can also shed new light on discussions about 'actually existing neoliberalisms'.
Keywords: Egypt; Turkey; Turkey - economic conditions - 1960; economic conditions in Egypt - 1952; economic policy; economics - religious aspects - Islam; neoliberalism; religion & politics

Understanding the “economization” of social formations - Jessop, Bob (The marketization of society: economizing the non-economic - Editors - Uwe Schimank, Ute Volkmann, 2012)
A critical review of nine dimensions of economization of social relations and their repercussions on societal dynamics. Discusses fictitious commodification, financialization, finance-dominated accumulation, and issues of ecological dominance. Bibliographic note: Book contains selected papers from conference on Marketization of Societies, organized at Bremen University, 1-2 June 2012. This is the pre-print version of a planned conference collection with a commercial publisher.
Keywords: fictitious commodification; fictitious commodities; financialization

The Embedded Market and Ideology Critique - Johnson, Pauline (Critical Horizons, 2011)
The article examines the ideology critical potentials of the concept of the embedded market, made famous by philosopher and economic historian Karl Polanyi. It explores several readings of this concept and assesses their ability to revive critical powers of sociology. It discusses the book "The New Spirit of Capitalism," by Luc Boltanski and Eve Chiapello, as a specific take on such an idea. It also offers a re-examination of Polanyi's interpretations of the embedded markets thesis.
Keywords: Boltanski and Chiapello; embedded markets; ideology; neoliberalism; philosophers; philosophy; social theory; sociology

Work and Neoliberal Globalization: A Polanyian Synthesis - Bandelj, Nina; Shorette, Kristen; Sowers, Elizabeth (Sociology Compass, 2011)
This article reviews sociological research about economic globalization’s impact on work and labor in developed and developing countries since the 1980s. We find that this period of neoliberal globalization influences work because of intensified activities of multinational corporations (MNCs), financialization of the global economy, and amplified prominence of international organizations, some of which diffuse neoliberal policy scripts while others mobilize a transnational civil society. Research we review generally points to liabilities of neoliberal globalization for workers. To understand these findings, we apply Karl Polanyi’s concepts of fictitious commodities, the self-regulating market, and the double movement. We propose that, on the one hand, the activities of MNCs, international financial organizations, and many states exemplify pushes for institutional separation of economy and society in effort to institutionalize the idea of a self-regulating market at a global scale, which increases labor commodification and global inequalities. On the other hand, the activities of social movements, including unions and transnational actors that target globalization’s impact on work, constitute the counter movement at national and global levels resisting marketization and pushing for labor decommodification. The aftermath of the ongoing economic crisis will tell to what extent this countermovement will be successful in generating an alternative to neoliberal globalization, and more protections for workers.
Keywords: double movement; fictitious commodities; globalization; neoliberalism; self-regulating market

Contracts in the English NHS: Market levers and social embeddedness - Hughes, David; Petsoulas, Christina; Allen, Pauline; Doheny, Shane; Vincent-Jones, Peter (Health Sociology Review, 2011)
This paper draws parallels between the market trend in the English NHS and Polanyi's (1957) The Great Transformation account of how the rise of markets provokes a self-protective counter-reaction that tries to re-embed economic relations in social relations. We report findings from a qualitative study of NHS contracting, which examines the recent move to harder-edged contracts with greater use of financial penalties and incentives. In practice, use of these techniques tended to be confined to nationally-mandated sections of the contract rather than emerging from local bilateral agreements, and when things went wrong the parties relied more on cooperative behaviour than on the provisions of the contract to find solutions. Making the current contracting system work depended more on existing relational networks than on the incentive structures created by recent 'marketisation' initiatives, but the inability of the market to evolve as expected has encouraged policy makers to publish plans for further radical reforms.
Keywords: England; English NHS; NHS reforms; competition (economics); contracting; contracting out; cooperativeness; decentralization in management; financing of research; government agencies; health sociology; incentives in industry; information storage & retrieval systems - medical care; institutional cooperation; interviewing; marketisation; meetings; methodology; national health services; negotiation; organizational effectiveness - evaluation; organizational structure; organizational change; pay for performance; purchaser/provider relations; qualitative research; research methodology; risk management in business; secondary analysis; social context; sociology; theory

The Commodification of Pollution and a Preemptive Double Movement in Environmental Governance: The Case of Water Quality Trading - Mariola, Matt J. (Organization & Environment, 2011)
The management of environmental pollution has traditionally been accomplished via the regulatory power of the state, but more recently the rise of a new, market-based form of governance has been observed. This article examines the sector of water quality trading, in which caps are placed on surface water pollution and polluters can purchase “offset credits” from farms or other polluters who are under their cap. Using a content analysis of program case studies and federal and state trading rules, the author analyzes this emergent form of environmental governance using an expanded Polanyian framework that he terms the preemptive double movement. Instead of the state reacting to the dangers of a new market form after the fact, here the state uses its existing authority to constrain the market so that further environmental damage does not result. The author describes eight specific regulatory mechanisms that illustrate this preemptive double movement at work.
Keywords: Polanyi; business & the environment; commodification; double movement; ecological impact; nutrient trading; pollution; water quality management; water quality trading

Grounding Globalization: Labour in the Age of Insecurity - Webster, Edward; Lambert, Rob; Beziudenhout, Andries (John Wiley & Sons, 2011)
*Winner of the 2009 Distinguished Scholarly Monograph Prize, awarded by the American Sociological Association Labor and Labor Movements section* Claims have been made on the emergence of a new labour internationalism in response to the growing insecurity created by globalization. However, when persons face conditions of insecurity they often turn inwards. The book contains a warning and a sign of hope. Some workers become fatalistic, even xenophobic. Others are attempting to globalize their own struggles. Examines the claim that a new labour internationalism is emerging by grounding the book in evidence, rather than assertion Analyzes three distinct places – Orange, Australia; Changwon, South Korea; and Ezakheni, South Africa – and how they dealt with manufacturing plants undergoing restructuring Explores worker responses to rising levels of insecurity and examines preconditions for the emergence of counter-movements to such insecurities Highlights the significance of 'place' and 'scale', and demonstrates how the restructuring of multi-national corporations, and worker responses to this, connect the two concepts
Keywords: Polanyi problem; critique; globalization; internationalism; labour; science / earth sciences / geography

Karl Polanyi: The Limits of the Market - Barnes, Tom (Journal of Australian Political Economy, 2011)
The article reviews the book "Karl Polanyi: The Limits of the Market," by Gareth Dale.
Keywords: DALE, Gareth; KARL Polanyi: The Limits of the Market (Book); Polanyi, Karl, 1886-1964

Embedding Economic Relationships through Social Learning? The Limits of Patient and Public Involvement in Healthcare Governance in England - Vincent-Jones, Peter (Journal of Law & Society, 2011)
The strategy for NHS modernization in England is privileging individual choice over collective voice in the governance of healthcare. This paper explores the tension between economic and democratic strands in the current reform agenda, drawing on sociological conceptions of embeddedness and on theories of reflexive governance. Building on a Polanyian account of the disembedding effects of the increasing commercialization of health services, we consider the prospects for re-embedding economic relationships in this field. An analysis is provided of the limits of the present legal and regulatory framework of Patient and Public Involvement (PPI) in establishing the democratic and pragmatist conditions of social learning necessary for effective embedding. We show how the attainment of reflexive governance in the public interest is dependent on such conditions, and on the capacities of patients and the public to contribute to debate and deliberation in decision making, including on fundamental policy questions such as how services are provided and by whom.
Keywords: Great Britain; National Health Service; disembeddedness; embeddedness; medical care; public interest; social learning

Would You Barter with God? Why Holy Debts and Not Profane Markets Created Money - Semenova, Alla (American Journal of Economics and Sociology, 2011)
Attempting to revitalize the substantive approach to economics in the tradition of K. Polanyi, this paper revives the neglected substantive theory of money's origins by Bernhard Laum and thus disputes the formal approaches that see the origins of money in the context of trade. A wide range of evidence, from archeological to etymological, is utilized to demonstrate that relations between men and God, carried out through the intermediary of state-religious authorities, played a causal role in the genesis of the ox-unit of value and account, and, further, in the origins of money, and, subsequently, coinage. The substantive state-religious approach presented in this paper is also compared and contrasted to the Chartalist perspective on money's origins. It is concluded that the substantive approach presented in this paper differs from the more formal approaches (e.g., Metallism) because it does not rely upon a projection of modern institutions and habits of thought (e.g., a medium of exchange; monetary taxation) into ancient societies.
Keywords: ancient societies; money; substantive approach

Lineages of Embeddedness: On the Antecedents and Successors of a Polanyian Concept - Dale, Gareth (American Journal of Economics & Sociology, 2011)
Since the 1980s, much debate has revolved around Karl Polanyi's concept of the 'dis/embedded economy,' generating some light and not a little heat. This paper looks at three reasons that account for part of the 'heat.' It begins by tracing the sources upon which Polanyi drew. They include Karl Marx, Ferdinand Tönnies, and Max Weber, along with anthropology of the inter-war period, and German and American Institutionalist economics. After exploring the differing ways in which these varying currents conceptualize the relationship between economy and society, I explore the different interpretations of what Polanyi means by embeddedness, and the different purposes to which contemporary economic sociologists have put the term. For some, he is held up as the originator of a line of sociological analysis that treats 'the economy' as a subsystem 'embedded in' a social system. In this reading the emphasis is upon the moral underpinnings of market behavior, in contrast to the naturalism of Ricardo, Malthus and their heirs. For others, his 'disembedding' thesis contains a more radical tale: of the market economy coming to dominate 'society,' bringing forth a sorcerer's apprentice world of untrammeled market forces that, although human creations, lie beyond conscious human control.
Keywords: MARX, Karl, 1818-1883; POLANYI, Karl, 1886-1964; TONNIES, Ferdinand, 1855-1936; WEBER, Max, 1864-1920; economic philosophy; economics; embeddedness; influence (psychology); intellectual life - history; socioeconomics

Another ‘Great Transformation’ or Common Ruin? - Smart, Barry (Theory, Culture & Society, 2011)
In the aftermath of the 1930s Great Depression, and as the Second World War was drawing to a close, Karl Polanyi concluded a critical analysis of market capitalism on an optimistic — and with the benefit of hindsight we can add premature — note, remarking that the ‘primacy of society’ over the economic system had been ‘secured’. Eighty years later, amidst the unresolved turmoil of another comparable global capitalist economic crisis and accumulating signs of a growing environmental crisis, both a direct legacy of the operation of the ‘market economy’, the remedy advocated by governments and policy-makers is effectively a return to ‘business as usual’. Notwithstanding various manifestations of public expression of dissatisfaction with the consequences of global ‘free-market’ capitalism, which include increasing inequality, poverty, unemployment, depletion of scarce natural resources, environmental destruction, pollution and waste, the default policy setting remains to restore global economic growth, to generate further increases in production and cultivate ever-rising rates of consumption, even if the risk is ‘common ruin’. However, there are a number of realistic, progressive and radical alternatives proposed by critical analysts, including a political program for ‘de-growth’ , a reinvention of communism and detailed policy proposals outlining the measures necessary to promote a transition to a ‘post-capitalist’ society with a sustainable economy.
Keywords: BAUMAN, Zygmunt; Farewell to Growth (Book); First As Tragedy, Then As Farce (Book); LATOUCHE, Serge; Living on Borrowed Time: Conversations With Citlali Rovirosa-Madrazo (Book); ZIZEK, Slavoj, 1949-; capitalism; communist hypothesis; de-growth; degrowth; economic growth; environment; financial crisis; nonfiction; sustainability

Positivism and 'Functional Theory' in the Thought of Karl Polanyi, 1907-1922 - Dale, Gareth (Sociology Compass, 2011)
Karl Polanyi is the author of a modern social science classic, The Great Transformation, as well as a number of well-known and widely debated essays collected in Trade and Market in the Early Empires and Primitive, Archaic and Modern Economies. These texts were researched and written either during his second exile in 1930s Britain or in wartime or post-war North America. Not so well known, however, are his Hungarian writings from the 1910s. Until recently, very few of these had been republished or translated, although this is in the process of being rectified [: Karl Polanyi: The Hungarian Writings]. With reference to new translations of his Hungarian writings, to interviews with his daughter, Kari Polanyi-Levitt, as well as to biographical essays by György Litván, Évá Gábor, Endre Kiss, and Zoltán Horváth, this article explores his early influences, drawing attention in particular to his flirtation with and then violent reaction against philosophical materialism and 'objectivist' sociology, his appreciation of Ernst Mach's positivism, and his adherence to the 'functional theory' of contemporary Guild Socialism.
Keywords: positivism; religion; social sciences; socialism

Crisis and renewal: the outlines of a twenty-first century new deal - Block, Fred (Socio-Economic Review, 2011)
Most analyses of the US financial crisis of 2007–2009 focus on the proximate causes. This article sees the crisis as a consequence of the decline of a long-term pattern of accumulation in the USA and seeks to outline the requirements for a new period of dynamic economic growth. Drawing on work done by the French Regulation theorists and the US analysts of Social Structures of Accumulation, the paper attempts to describe the types of institutional changes that would be needed to spark a new period of stable economic growth in the USA and in the rest of the world economy. The paper outlines what a green mass consumption economy might involve.
Keywords: United States; capitalism; capitalist systems; crises; economic change; economic reform; financial crisis; green economy; institutional change

NAFTA and Gatekeeper: A Theoretical Assessment of Border Enforcement in the Era of the Neoliberal State - Ackerman, Edwin (Berkeley Journal of Sociology, 2011)
The coexistence of border-enforcement policies such as Operation Gatekeeper and economic liberalization programs such as NAFTA is arguably paradoxical given the simultaneous push towards afree flow of products but curtailed flow of labor. This paper presents a critical review and reassement of existing accounts of neoliberal statehood to make sense of this apparent puzzle. While some have argued that the state is eroding under neoliberal globalization, a more sophisticated analysis has focused on how it has been transformed. David Harvey and LoIc Wacquant focus on the role of the repressive apparatus in upholding neoliberalism. Building on Harvey and Wacquant, and returning to Karl Polanyi, I emphasize the ways in which the state has tried to make use of a repressive apparatus as a claim to social protection a function that becomes necessary as the state advances liberalization. The coexistence of NAFTA and Gatekeeper should be not be understood as an anomaly but rather as an expected feature of contemporary statehood.
Keywords: North American Free Trade Agreement (NAFTA); United States; border security; finance; free trade; liberalization; neoliberalism; social protection

On the Nation-Specific Features of Modernization in Russia - Yadov, Vladimir (Social Sciences, 2011)
The article offers information on the features that contribute to the modernization in Russia. It discusses various value structure theories from various persons. It says that from the analysis of world survey statistics, Yevgeny Yasin concluded that Russians are more conservative compared to other western countries. Details regarding the mentality of Russian people are discussed including Russians' high score on cycloid scale and their tendency to fulfill their task at the last moment. Moreover, it says that Russia's activist theories, Karl Polanyi and Douglas North's path dependence theory, and the global world system theory as a new phase to human civilization's history are important features to the country's modernization.
Keywords: Russia; Russia - social conditions; YASIN, Yevgeny; economic development; modernization (social science); modernization theory; nation-state; national interest; social development theory

After Neoliberalism - Antonio, Robert J. (The Wiley-Blackwell Companion to Sociology, 2011)
This chapter contains sections titled: * Clashing Models of Capitalism: Hayek VS. Polanyi * Market Liberalism's Return: From the “Not Quite Golden Age” to the “Great U - Turn” * Hegemonic Neoliberalism: From Crest to Crisis to Emphatic Reassertion(?) * Capitalism at the Point of Inflection: Neoliberalism's Wake * Conclusion * References
Keywords: 2008 financial meltdown; HAYEK, Friedrich A. von (Friedrich August), 1899-1992; Hayek's and Polanyi's classic texts; New Deal; The Great U-Turn; ascendant neoliberalism; cutting edge issues; great recession; hegemonic culture; neoliberalism; neoliberalism's wake; self-regulating market

Polanyi on Markets, Democracy and the Crisis of Liberalism - Ebner, Alexander (The Beginnings of Scholarly Economic Journalism, 2011)
Karl Polanyi, who was born in 1886 in Vienna and died in 1964 in Pickering, Ontario remains a most influential theoretical figure in the social sciences, in particular stimulating both analytical and policy-related concerns that are related with the new institutionalism in economics, sociology and political science. Polanyian insights on the political economy of economic development from an institutional perspective have persistently shaped a variety of discourses that range from the theory of the welfare state to research in comparative economic systems and economic anthropology. Polanyi’s “Great Transformation” may be singled out as a key contribution to both the domains of economic sociology and political economy, as it addresses basic tensions between the developmental dynamics of the market economy and the institutional substance of political democracy (Block 2001).
Keywords: crisis of liberalism; early writings; methodology; methodology of the social sciences

Karl Polanyi and the New Economic Sociology: Notes on the Concept of (Dis)Embeddedness - Machado, Nuno Miguel Cardoso (Social Science Research Network, 2011)
Within the context of the New Economic Sociology, Karl Polanyi is almost universally considered the "father" of the concept of embeddedness. However, this concept has been subject to selective appropriation by this discipline and its relationship to the remaining theoretical edifice constructed by Polanyi has been neglected. It is, in fact, possible to refer to the "great transformation" to which the concept of embeddedness has been subjected: whereas in Polanyi’s work it is associated with the macro(economic) level and is used as evidence of the exceptional nature of the capitalist market economy –- disembedded from society –- in NES, it is normally associated with the meso (and even micro) level, on the assumption that all economies –- including capitalist economies -– are embedded. in RCCS Annual Review, No. 3, pp. 119-140
Keywords: Karl Polanyi; capitalism; embeddedness; market economy; new economic sociology

Whither the Counter-Movement? Hayek, Polanyi, and the Politics of No Alternative - Mudge, Stephanie (Conference Papers -- American Sociological Association, 2011)
This paper turns Karl Polanyi's concept of the "double movement" back on Polanyi and his intellectual contemporary, Friedrich Hayek, as a means to insight into the structural conditions of counter-movement in the second half of the 20th Century. After elaborating on the double movement concept, I contrast the trajectory of Polanyi and his greatest work, The Great Transformation, with that of Friedrich Hayek and his contemporaneous Road to Serfdom--treating each as protagonists in the movement/counter-movement system of relations that, for Polanyi, is the site of history's forward motion. Building on citation data, news articles, archival records and secondary sources, I argue that Polanyi's conditions of intellectual production--including a lack of economic allies in the capitalist West, professional instability, tenuous ties to academic economics, and a lifetime of financial insecurity--explain the ongoing quarantine of Transformation within the academic social sciences. These conditions of production contrast starkly with the Hayekian counterexample. Taken together, the analysis casts light on the ongoing hegemony of the "liberal creed" and the weakness of effective opposition: the trajectory of the two figures offers clues into how structures of intellectual production are linked to (or severed from) movement and counter-movement, offering insight into why, even in the face of financial crisis and significant public anger against the moneyed ranks of the financial sector, we continue to exist in a world of "no alternative".
Keywords: HAYEK, Friedrich A. von (Friedrich August), 1899-1992; POLANYI, Karl, 1886-1964; capitalism; intellectuals; protagonists (persons)

Reading the Story of Law and Embeddesness through a Community Lens: A Polanyi-Meets-Cotterrell Economic Sociology of Law [article] - Perry-Kessaris, Amanda (Northern Ireland Legal Quarterly, 2011)
In this paper I propose that role of law in Karl Polanyi's concept of the 'always embedded economy' (Block 2003) can be enriched by the application of the lens of community (Perry-Kessaris 2008) developed by Roger Cotterrell (1996-present). I begin with Polanyi's suggestion that economic action and interaction are always 'embedded' in wider social life. Reading through the lens of community, we can be more specific: any actor is at once engaged, to different degrees (from fleeting to stable), in multiple types (whether focusing on instrumental, traditional, affective and/or belief-based action) of social life. I then explore a second, implicit, cornerstone of Polanyi's argument: that analytical and normative approaches to economy may become dis-embedded from wider social life. Reading through the lens of community we can again be more specific: In the transformation to a market society, the analytical and normative approaches that are central to economic actions and interactions are confused with, and privileged over, those that are central to non-economic actions and interactions. This confusion and privileging can have what we might call a performative effect on action and interaction. Finally, I explore Polanyi's story of law as a facilitator both of dis-embedding movements and of re-embedding counter-movements. The application of a law-and-community lens suggests some additional details of that storyline and that there are additional plotlines to be pursued. The practical potential of this Polanyi-meets-Cotterrell economic sociology of law is briefly illustrated with references to two 21st Century cautionary tales: the World Bank's investment climate programme and the 2008 financial crisis.
Keywords: COTTERRELL, Roger; United Kingdom; economic sociology of law; embeddedness; investment climate; law and community

Double Movements of Destruction and Regulation: Commodity Chains and a New Political Economy of the Environment - Roberts, J.; Carmin, JoAnn; Rudel, Thomas (Conference Papers -- American Sociological Association, 2011)
Sociologists have examined the ways in which capitalism contributes to environmental degradation as well as how, in selected circumstances, it increases efficiency while reducing pollution and human injustices. In this review, we draw on Polanyi's concept of the double movement to illustrate how self regulating markets give rise to environmental degradation and inequities and, in response, how these conditions often stimulate the emergence of collective action in pursuit of regulatory and social reforms. This process is iterative, with capitalist initiated degradation of the environment followed by regulatory reform and then efforts to weaken the regulatory regimes. We illustrate how resource extraction contributes to environmental degradation and power inequalities, pollution from industrial production is unequally distributed among workers and communities, and how the desire to limit exposure to risk has opened new markets and led to policies that contribute to consumption.
Keywords: capitalism; commodity chains; consumption (economics); double movement; environmental degradation; industries; pollution

“The Great Transformation” and Suicide: Local and Long-Lasting Effects of 1930 Bank Suspensions - Baller, Robert D.; Levchak, Phil; Schultz, Mark (Suicide and Life-Threatening Behavior, 2010)
Depression-era bank suspensions and failures are conceptualized as products of the first part of what Polanyi (1994) called “The Great Transformation,” which involved an imbalanced institutional arrangement in which the economy dominated other institutions. Relying on Durkheim (1897/1951) and Merton (1938, 1968), it is argued that these banking problems accentuated the type of chronic anomie that Durkheim theorized would create normative deregulation and elevated suicide rates over the long-term. Results from county-level analyses are supportive as the 1930 bank suspension rate is positively related to the 2000 suicide rate, controlling for contemporary and historical factors. The mediating roles of integration and chronic anomie are considered, with the latter measured using data from the geocoded General Social Survey.
Keywords: DURKHEIM, Emile; MERTON, Robert; The Great Depression; anomie; countermovement; suicide; suicidology

'False' Optimism: The Key to Historic Breakthroughs? A Response to Michael Burawoy's 'From Polanyi to Pollyanna: The False Optimism of Global Labour Studies' - Clawson, Dan (Global Labour Journal, 2010)
Keywords: BURAWOY, Michael; borderline; global labor studies; global labour studies

From Critical Sociology to Combat Sport? A Response to Michael Burawoy's 'From Polanyi to Pollyanna: The False Optimism of Global Labour Studies' - Webster, Edward (Global Labour Journal, 2010)
Keywords: BURAWOY, Michael; double movement; global labour studies; globalization

Decommodification and Egalitarian Political Economy - Vail, John (Politics & Society, 2010)
This article contends that decommodification is an appropriate concept for understanding diverse initiatives such as fair trade, microfinance, open source, social enterprises, and the environmental commons as component features of a common process. Decommodification is conceived as any political, social, or cultural process that reduces the scope and influence of the market in everyday life. Given recent transformations in market societies, a more expansive framework for decommodification is urgently required. Decommodification would insulate non-market spheres from market encroachments; increase the provision of public goods and expand social protection; promote democratic control over the market by creating economic circuits grounded in a logic predicated on social needs rather than profit; and undermine market hegemony by revealing the market’s true social costs and consequences. By ensuring basic needs, enhancing individual capacities and capabilities, and promoting social cooperation and collaboration, decommodification constitutes a central feature of an egalitarian agenda.
Keywords: decommodification; double movement; icy silence; sociology

From Polanyi to Pollyanna: The False Optimism of Global Labor Studies - Burawoy, Michael (Global Labour Journal, 2010)
Keywords: EVANS, Peter, 1944-; MARX, Karl, 1818-1883; counter-hegemonic globalization; critique; labor studies; labour studies

The Aporia of Power: Crisis and the Emergence of the Corporate State - Kapferer, Bruce (Social Analysis, 2010)
The argument focuses on the corporate state as an increasingly significant political assemblage that has enabled new configurations of power with related social effects. Here the discussion proceeds from Karl Polanyi's thesis in The Great Transformation. A critical idea that Polanyi pursued related to the state production of economism and individualism, which prepared the ground for the expansion of capital in its globalizing form. The essay develops this idea, indicating that the nationalist capitalism of the state led to a radical change in the political and social orders of states, gradually giving rise to the corporate state assemblage. The emphasis here is on the corporate state as a socio-political order that places radically distinct structural dynamics into impossible conjunction, leading to progressively disastrous social effects concerning poverty and the emergence of new configurations in which war and violence take specific shapes.
Keywords: Great Transformation, The (Book); bureaucratic processes; corporate state; crisis; economism; globalization; individualism; nation-state; poverty; power (social sciences); reterritorialization; violence; war; war machine

The Idea of a Three-Dimensional Conflicts Law as Constitutional Form - Joerges, Christian (RECON Online Working Paper 2010/05, 2010)
‘Constitutionalisation’ is the key concept in the search for legitimate governance in the European Union and in the international system. This paper suggests the revitalising of a discipline which is widely neglected in European law and international law scholarship. It does not, however, recommend a return to the conflict of laws (private international law) in the traditional sense. The new type of conflicts law that the paper advocates is not concerned with selecting the proper legal system in cases with connections to various jurisdictions. This conflicts law is conceptualised as a response to the increasing inter-dependence of formerly more autonomous legal orders and to the democracy failure of constitutional states which result from the external effects of their laws and legal decisions on foreign systems and on their citizens who cannot understand themselves as their authors. European law has a vocation and many means both to compensate for the democracy failures of member states and to build upon this potential in its constitutionalisation. The conflicts law approach also provides new, albeit more restrained, perspectives at international level. WTO law is used to explore and document its constitutional perspectives. The conflicts law approach is differentiated into three dimensions. With this differentiated fabric, the approach responds to transformation processes which have affected contemporary law at all levels of governance after the rise of regulatory politics and the turn to governance. In its second dimension, conflicts law seeks to constitutionalise co-operative problem-solving under the lead of administrative bodies, while its third dimensions is concerned with both the recognition and the supervision of transnational governance arrangements and para-legal regimes.
Keywords: BLOCK, Fred; Europeanisation; World Trade Organization (WTO); always socially embedded' economy; constitutionalisation; deliberative democracy; economic law; economic sociology; multilevel governance; private international law; rule of law; social embeddedness; social regulation; supranationalism

Decency in Anglo-American Financial Centres? - Pixley, Jocelyn (Thesis Eleven, 2010)
How can a partial, revisable utopia of 'decent society' be used as a yardstick for assessing today's impersonal forms of social integration? In economic life - this essay's focus - Polanyi's hopes that the 'economic system' might cease 'to lay down the law to society' is a start. Recently, financial firms sold commodified promises and obligations on the allure of democratizing credit and providing financial 'choice' to millions. Yet these 'civilities' exploited people's hopes for a dignified life. Any new, partial utopia (as Keynes's was too - to remove the egregious, humiliating features of 'the society in which we live') is yet to be devised. Maria Markus's concept is useful to ask whether the instrumentalism of macro-economic concepts is a distortion of the institutions of money or intrinsic to them. Could solidaristic compromises through civil society minimize disrespectful relationships embedded in money to create decent institutions?
Keywords: MARKUS, Maria; POLANYI, Karl, 1886-1964; decent economic institutions; economic democracy; economic systems; embeddedness; essay (literary form); financial centres; social integration; utopias

Cultural political economy and critical policy studies - Jessop, Bob (Critical Policy Studies, 2010)
This article introduces cultural political economy as a distinctive approach in the social sciences, including policy studies. The version presented here combines critical semiotic analysis and critical political economy. It grounds its approach to both in the practical necessities of complexity reduction and the role of meaning-making and structuration in turning unstructured into structured complexity as a basis for ‘going on’ in the world. It explores both semiosis and structuration in terms of the evolutionary mechanisms of variation, selection, and retention and, in this context, also highlights the role of specific forms of agency and specific technologies. These general propositions are illustrated from ‘economic imaginaries’ (other types of imaginary could have been examined) and their relevance to economic policy. Brief comments on crisis-interpretation and crisis-management give this example some substance. The conclusion notes some implications for research in critical policy studies.
Keywords: complexity; crisis; crisis-management; cultural political economy; cultural turn; finance-led accumulation; green new deal; neoliberalism

Globalization, Crisis and Social Transformation: A View from the South - Munck, Ronaldo (Globalizations, 2010)
The dominant narrative around the unfolding capitalist crisis is firmly focused on the dominant economies, and in particular the US. This is understandable given that the proximate causes of the crisis lie in the imperial heartlands and crisis resolution measures taken there will have a global impact. But a 'view from the South' is needed to redress the balance and prevent the decimation of global majority likelihoods being presented as mere collateral damage. The first section below tackles the crisis from a global (globalization) perspective emphasizing its impact in the South and what that it might mean in terms of political prospects. I then go on to develop a hybrid Karl Polanyi/Antonio Gramsci theoretical lens on counter-movements based on their writings responding to the last systemic capitalist crisis in the 1930s. Finally, I turn to the ways in which the international labour movement and the subaltern or post-colonial worlds are contesting the terrain vacated by unregulated market capitalism. As Gramsci would say the old is dying but the new has not yet been born. La narrativa dominante alrededor de la crisis capitalista revelada, esta firmemente enfocada a las economias dominantes, y particularmente E.E.U.U. Esto es comprensible, dado que las proximas causas de la crisis yacen en la region central imperial y las medidas de resolucion de la crisis que se tomaron alli tendran un impacto global. Pero se necesita un 'punto de vista desde el sur' para compensar el equilibrio y prevenir la devastacion de las posibilidades de las mayorias globales presentadas como simple dano colateral. La primera seccion abajo trata la crisis desde una perspectiva global (globalizacion), enfatizando su impacto en el sur y lo que eso puede significar en terminos de prospectos politicos. Luego procedo con el desarrollo de una lente teorica hibrida de Karl Polanyi/Antonio Gramsci sobre movimientos opuestos en base a sus escritos que responden a la ultima crisis capitalista sistemica en la decada de 1930. Finalmente, vuelvo a las maneras en las cuales el movimiento laboral internacional y los mundos subalternos o postcoloniales estan disputando el terreno vacio por el mercado capitalista sin regulacion. Como Gramsci diria, lo viejo se esta muriendo, pero lo nuevo no esta aun por nacer. [image omitted]
Keywords: GRAMSCI, Antonio, 1891-1937; South; capitalism; countermovement; crisis; financial crises; financial crisis; globalization; hegemony; international markets; labour; post-colonial; social change; transformation

A British Bureaucratic Revolution? Autonomy Without Control, or "Freer Markets, More Rules." - Le Galès, Patrick; Scott, Alan (Revue Française de Sociologie, 2010)
This paper addresses a puzzle: how to account for changes in the routine behavior of groups, organizations and individuals in Britain? Following a detailed analysis of state-market interdependence and the role of the state in creating the market, an analysis drawn from the thinking of Weber and Polanyi, we suggest adapting Weber's notion of bureaucratic revolution: in what we call the British bureaucratic revolution, the state has played an essential role in social change by creating institutions and rules that are lastingly reorienting actors' behavior. The example of the healthcare field is examined in order to identify the specific mechanisms that have been impacting on behavior within an approximately ten-year period; namely, the introduction of 1) competitive practices (sanction/reward) and 2) auditing and inspection. If this interpretation is valid, then it is reasonable to assume that the effects of this bureaucratic revolution extend beyond Britain.
Keywords: Great Britain; bureaucracy; medical care; revolutions; social change

Work After Globalization: Building Occupational Citizenship - Standing, Guy (Edward Elgar Publishing, 2010)
Per Google Books: This is a scholarly and erudite work. . . There is a wealth of detail, all illustrated with plenty of fascinating examples. . . It is impossible to give the full flavour of this thoughtful and stimulating book in even a long review, but it deserves to be
Keywords: business & economics - labor; business & economics - labour; embeddedness; industrial citizenship; political science / labor & industrial relations; political science / labour & industrial relations; social science / sociology / general

Social Economy and the fight against Social Exclusion: Preliminary remarks with reference to the Greek welfare state - Adam, Sofia (1st International Conference in Political Economy, 2010)
Recent academic discourse and European social policies highlight the (potential) effectiveness of social economy practices as a means to address social exclusion especially for the more disadvantaged social groups. Apart from terminological debates on the aforementioned troubled concepts, fundamental questions needs to be examined: To what extent social economy practices flourish as a result of policy shifts towards further commercialization of public social services or to what extent do they emerge from bottom up collective survival strategies? This paper attempts to address this question with reference to the political economy of the Greek welfare state.
Keywords: Greece; economic sociology; embeddness; political economy; social economy; substantive approach; welfare state

The ordering of change: Polanyi, Schumpeter and the nature of the market mechanism - Harvey, Mark; Metcalfe, Stan (Markets, Rules and Institutions of Exchange, 2010)
Keywords: SCHUMPETER, Joseph Alois, 1883-1950; market mechanism

Fair Trade and the Double Movement: The Promise and Contradictions of Improving Labor Standards in the Global South via Market Mechanisms - Shorette, Kristen (Journal of Workplace Rights, 2010)
I examine Fair Trade (FT) as a social movement that emerges as a regulative force in response to the rise of neoliberalism. I apply Polanyi's (1944, 1957) classic concepts of embeddedness and the double movement to understand the conflict that arises within a coherently motivated social movement. Using interview and participant observation data along with content analysis of FT organization mission statements, this research examines the role of conflict within the FT movement over how best to improve the well-being of producers in the global South. I discuss the different, conflicting ways in which FT participants think about improving labor conditions in the global South and the inherent conflict in using market mechanisms to counter market forces. I conclude that while participants share the values of human rights, equality, and environmentalism, realizing these goals through concrete market activities reveals the tension between the benefits of liberalizing and the benefits of regulating the production and sale of FT goods that may impede the continued growth of the movement.
Keywords: developing countries; double movement; embeddedness; fair trade; human rights; labor laws & legislation; labour laws & legislation; neoliberalism; production standards; social movements; unfair competition; workplace rights

Local Food: A Social Movement? - Starr, Amory (Cultural Studies/Critical Methodologies, 2010)
This article analyzes the development of “local food” institutions from a social movements perspective. Over the last decade, institutions that “shorten the links” between producer and consumer have developed through a diverse collaboration of many social sectors (farmers, agronomic experts, retailers, chefs, food writers, and several distinct consumer sectors). Some agronomists and rural sociologists critical of the globalization and industrialization of agriculture have recognized this development as heralding Polanyian “reembedding” of market exchanges in social relations. This article analyzes whether and how local food is a social movement, using new social movement theory as an analytic framework.
Keywords: community-based economics; local food; local foods; localism; organic food; organic foods; social change; social movements; social psychology

The Role of the State in Making a National Market: The Evolution of the Grain Market in China (1978-2000) - Zhou, Wubiao (China Agricultural Economic Review, 2010)
The paper aims to examine Karl Polanyi's view of market evolution in the context of the emergence of a national grain market in China's transition economy. The dataset used includes information about inter-provincial grain trade on China's grain market from November 1999 to October 2000. A priori blockmodelling method is used for hypothesis testing. This paper finds that a partially integrated national grain market had emerged at the beginning of the twenty-first century in China in spite of local protectionism. Additionally, the emergence of this market is found to be partly a result of the reform-oriented state's attempt to create national wholesale grain markets.
Keywords: agricultural policy; agriculture; agriculture: aggregate supply and demand analysis; collectives; communes; economic development: agriculture; energy; environment; food policy; natural resources; other primary products; prices

Polanyi in Brussels: Supranational Institutions and the Transnational Embedding of Markets - Caporaso, James A.; Tarrow, Sidney (International Organization, 2009)
AbstractMany have argued that the success of European integration is predicated on reinforcing market structures and some have gone further to state that the creation of a transnational market results in a decoupling of markets from their national political and social frameworks, thus threatening to unravel historical social bargains. Drawing on the work of Karl Polanyi and John Ruggie and using their insights regarding the social embedding of markets, we dissent from this view by examining how the European Court of Justice (ECJ) has handled a key sector of the emerging European market—labor mobility. We argue that rather than disembedding markets, decisions of the ECJ—just as Polanyi and Ruggie would have predicted—activate new social and political arrangements. We find evidence for the development of a new legal and political structure, largely inspired by the Court but also imbricated in European Union legislation, at the regional level.
Keywords: European Court of Justice; embedded markets

Industrial Relations Today: Reining in Flexibility - Streeck, Wolfgang (Economics, Management & Financial Markets, 2009)
The paper was presented as a keynote lecture at the 10th anniversary of the Amsterdam Institute for Advanced Labour Studies (AIAS) in April 2008. It surveys the trajectory of scholarly work on labor after 1945, from its initial emphasis on rights of industrial and social citizenship to its present preoccupation with "flexibility" and "flexicurity." It recalls the dissolution of the "Fordist" compromise in the 1970s and the subsequent gradual expansion of markets as the dominant mechanism for the allocation of life chances and the governance of society. Marketization encountered surprisingly little resistance, in real life as in the evolving conceptual apparatus of scholarly work. Liberalization proceeded and continues to proceed regardless of the social dislocations it causes, on a scale wholly unimaginable and indeed unacceptable under the postwar settlement. The paper ends with speculation on what if at all might be the forces today that could trigger a Polanyian counter-movement to the progress of capitalist social and economic relations. In particular it discusses whether demographic change, in terms of both a declining birth rate and increasing life expectancy, might bring about a new wave of market-containing social policy.
Keywords: corporate growth; countermovement; industrial relations; international economic relations; labor laws & legislation; labour laws & legislation; socioeconomics; welfare economics

The unknown Karl Polanyi - Cangiani, Michele (International Review of Sociology, 2009)
Keywords: biography; essence of fascism

Subaltern strategies and autonomous community building: a critical analysis of the network organization of sustainable agriculture initiatives in Andhra Pradesh - Kumbamu, Ashok (Community Development Journal, 2009)
This paper examines and analyses the organization and functioning of subaltern peasant sanghams (grassroot associations of the poor) and their place-based as well as network-based strategies in building autonomous local communities that challenge the consequences of neoliberal globalization in general and the commodification of agriculture and food in particular. The major objective of the counter-hegemonic organizational strategies is to build self-protective and subsistence communities, to mend the metabolic rift between nature and society, and to re-reconstruct social fabric within communities. The question remains is whether place-based autonomous communities can sustain in an increasingly globalizing world. To better understand these political dynamics, I use Karl Polanyi's concept of ‘double movement’ and examine the making of a double movement in Indian agriculture and its socio-political and ecological implications for the Indian peasantry. I use the organizational strategies and activities of the Deccan Development Society, a prominent non-governmental organization that has been working in Medak district for more than two decades, as an illustrative case study.
Keywords: community development; community organizing; double movement; metabolic rift; peasant studies

The Extended Case Method: Four Countries, Four Decades, Four Great Transformations, and One Theoretical Tradition - Burawoy, Michael (University of California Press, 2009)
In this remarkable collection of essays, Michael Burawoy develops the extended case method by connecting his own experiences among workers of the world to the great transformations of the twentieth century—the rise and fall of the Soviet Union and its satellites, the reconstruction of U.S. capitalism, and the African transition to post-colonialism in Zambia. Burawoy's odyssey began in 1968 in the Zambian copper mines and proceeded to Chicago's South Side, where he worked as a machine operator and enjoyed a unique perspective on the stability of advanced capitalism. In the 1980s, this perspective was deepened by contrast with his work in diverse Hungarian factories. Surprised by the collapse of socialism in Hungary in 1989, he journeyed in 1991 to the Soviet Union, which by the end of the year had unexpectedly dissolved. He then spent the next decade studying how the working class survived the catastrophic collapse of the Soviet economy. These essays, presented with a perspective that has benefited from time and rich experience, offer ethnographers a theory and a method for developing novel understandings of epochal change.
Keywords: social science; sociology

An Introduction to Destructive Coordination - Vahabi, Mehrdad (American Journal of Economics and Sociology, 2009)
Polanyi (1944, [1957]1968) has distinguished three “patterns of social integration,” namely, “reciprocity,”“redistribution,” and “exchange.” This triad has provided the starting point for most subsequent discussion. Our purpose is to introduce a further type of coordination, the “destructive mode of coordination.” This mode achieves coordination by intimidation, threat, and the use of non-institutionalized coercive means. Resources and human efforts are allocated in order to appropriate what other people produce. Two simple examples provide an introductory illustration: traffic circles (roundabouts) and prisons. Appropriation through pirating provides a further example of destructive coordination. More specifically, biopiracy (blood patenting) is discussed in order to clarify the relationship between destructive coordination and the institutionalization of property rights. Finally, we focus on the role of destructive coordination as a transitional mechanism that is supported by the institutional vacuum, ultimately yielding to other modes of coordination.
Keywords: appropriation; destructive mode of coordination; social integration

Karl Polanyi in Budapest: On his Political and Intellectual Formation - Dale, Gareth (European Journal of Sociology / Archives Européennes de Sociologie, 2009)
AbstractA major thinker and inspiring teacher, Karl Polanyi's contributions have long been influential in a variety of disciplines, notably economic sociology and economic history. Two of his innovations, substantivist economic anthropology and the “double movement thesis,” are recognized as seminal. All of the works for which he is known, however, were written late in life, when in exile, and very little is known of his Hungarian writings, virtually none of which had, until now, been translated. Despite his fame, the biographical literature on Polanyi remains modest: some studies provide invaluable insights, yet all are brief. This article attempts to make some headway in remedying these lacunae. It sketches the contours of that extraordinary historical-geographical conjuncture in which he was formed, and explores his intellectual and political engagements in the Galilei Circle and the Radical Bourgeois Party. It seeks in particular to elucidate the complex roles played by questions of nation, ethnicity and class in the life of the young Karl Polanyi.
Keywords: Hungary; Jewish assimilation; biography; liberal radicalism

Precarious Work, Insecure Workers: Employment Relations in Transition - Kalleberg, Arne L. (American Sociological Review, 2009)
The growth of precarious work since the 1970s has emerged as a core contemporary concern within politics, in the media, and among researchers. Uncertain and unpredictable work contrasts with the relative security that characterized the three decades following World War II. Precarious work constitutes a global challenge that has a wide range of consequences cutting across many areas of concern to sociologists. Hence, it is increasingly important to understand the new workplace arrangements that generate precarious work and worker insecurity. A focus on employment relations forms the foundation of theories of the institutions and structures that generate precarious work and the cultural and individual factors that influence people's responses to uncertainty. Sociologists are well-positioned to explain, offer insight, and provide input into public policy about such changes and the state of contemporary employment relations.
Keywords: precarious work; precarity

Embeddedness of Social and Economic Relations in Systemic Transformation. Long-Term Evidence From the Post-Communist Transition in Poland, 1988-2003 - Wilk, Katarzyna (Polish Sociological Review, 2009)
This paper intervenes in the Granovetter-Polanyi debate by reassessing the level of embeddedness of social and economic relations under conditions of systemic transition. Using panel data collected in Poland, this analysis examines this relationship for three distinct periods of transition: initial (1988-1993), advanced (1993-1998), and post-transitional (1998-2003). This paper shows that during transition from communism to capitalism economic relations tended to disembed from social relations, but this relationship remained significant; friendship ties were conductive to an individual upward mobility, economic well-being and entrepreneurial activity. In contrast to Polanyi's argument, however, entrepreneurship—the most marketable area of individual advancement—is found to exhibit the highest degree of social-economic embeddedness. These results do not directly support either Polanyi's or Granovetter's arguments, however they do accord with a neo-Polanyian argument, as advanced in this paper.
Keywords: (dis)embeddedness; Poland; capitalism; disembeddedness; embeddedness; entrepreneurship; friendship ties; political doctrines; practical politics; social classes; social networks; social status; socioeconomics; status attainment

Who is right about the modern economy: Polanyi, Zelizer, or both? - Steiner, Philippe (Theory and Society, 2009)
Zelizer’s work may be read as an attack on the central Polanyian thesis: that the market system threatens social life by the undue prominence it lends the economy in the organization of modern society. The recent publication of Viviana Zelizer’s The Purchase of Intimacy (2005a) is therefore an excellent opportunity to review the general trend of her work Zelizer 1979, 1985, 1994, and contrast her leading ideas to the central thesis that gives Polanyi’s work its particular flavor: the danger encapsulated in the use of modern money and the functioning of the market system.
Keywords: ZELIZER, Viviana; market system; money

Second thoughts: on economics, sociology, neoliberalism, Polanyi's double movement and intellectual vacuums - Piore, Michael J. (Socio-Economic Review;2009, Vol. 7 Issue 1, p161, 2009)
The article presents a presidential address by Michael J. Piore, delivered at the Society for the Advancement of Socio-Economics (SASE) Annual Meeting 2008 in San José, Costa Rica, in which he discussed the relationship between sociology and economics, and the role that this relationship plays at the current political juncture in the transition from neoliberalism to the formation of public policy.
Keywords: double movement; economic sociology; neoliberalism

Human Rights and Business Practices: Double Movement or Neoliberal Hegemony? - Thomas, Mark (Conference Papers -- American Sociological Association, 2009)
Throughout the 1990s and into the early years of the 21st century, campaigns by labor rights activists brought the issue of labor exploitation by Northern transnationals (TNCs) operating in the Global South into the centre of public debate. Labor rights scholars raised the possibility of a broader Polanyian 'double movement' in the global economy, as the polarizing effects of neoliberal globalization produced anti-globalization movements and shifts towards forms of social protection through emerging approaches to transnational labor rights regulation. One of the results of these processes was the adoption of a human rights discourse by TNCs as they sought to re-define their public image in response to growing public awareness and condemnation of sweatshop labor practices. Read through a Polanyian lens, these developments would seem to confirm that a double movement was in fact producing a more socially responsible capitalism where the 'satanic mill' of the sweatshop would be moderated through corporations proclaiming respect for human rights. In this paper, I examine the adoption of human rights principles by corporate actors as both normative framework and business practice. I argue that rather than a double movement from market liberalism to social protection, the dynamics present in this process indicate tendencies towards the construction of a new hegemonic discourse to support neoliberal globalization - that of the 'socially responsible' corporation where business practices and human rights principles intersect. ..PAT.-Unpublished Manuscript
Keywords: employee rights; hegemony; human rights; neoliberalism; satanic mill; transnationalism

Markets Against Society: Labor's Predicament in the Second Great Transformation - Webster, Edward; Lambert, Robert (The ISA Handbook in Contemporary Sociology: Conflict, Competition, Cooperation, 2009)
Keywords: labour movement; northern compromise; second great transformation

Genealogies of Citizenship: Markets, Statelessness, and the Right to Have Rights - Somers, Margaret R. (Cambridge University Press, 2008)
REVIEW: Genealogies of Citizenship is a remarkable rethinking of human rights and social justice. As global governance is increasingly driven by market fundamentalism, growing numbers of citizens have become socially excluded and internally stateless. Against this movement to organize society exclusively by market principles, Margaret Somers argues that socially inclusive democratic rights must be counter-balanced by the powers of a social state, a robust public sphere and a relationally-sturdy civil society. Through epistemologies of history and naturalism, contested narratives of social capital, and Hurricane Katrina's racial apartheid, she warns that the growing authority of the market is distorting the non-contractualism of citizenship; rights, inclusion and moral worth are increasingly dependent on contractual market value. In this pathbreaking work, Somers advances an innovative view of rights as public goods rooted in an alliance of public power, political membership, and social practices of equal moral recognition - the right to have rights. "Building on Karl Polanyi, T. H. Marshall, and Hannah Arendt. Margaret Somers demonstrates that civil society rests on Ihe right to have rights. But this right has been swept away by three decades of market-dominated discourse and policies. Somers brilliantly shows how Hurricane Katrina's devastating impact on New Orleans was the culmination of this dynamic." -Fred Block
Keywords: ARENDT, Hannah; citizenship; civics and citizenship; civil rights; history / Europe / general; political science - history and theory; right to have rights

Is an Alternative Globalization Possible? - Evans, Peter (Politics & Society, 2008)
Building on Polanyi's concept of the “double-movement” through which society defends itself against domination by the self-regulating market, this article sets out some key organizational and ideological hurdles that the contemporary “movement of movements” must surmount to challenge the hegemony of neo-liberal globalization. After outlining neo-liberalism's failures, it makes an argument for the possibility of “counter-hegemonic globalization,” defined as a globally organized project of transformation aimed at replacing the dominant (hegemonic) global regime with one that maximizes democratic political control and makes the equitable development of human capabilities and environmental stewardship its priorities.
Keywords: double movement; globalization; neoliberalism; social movements; transnational networks

The market and the nation: Austrian (dis)agreements - Karner, Christian (Social Identities, 2008)
This article relates contemporary Austria's much-discussed and internally contested identity politics to transnational socio-economic transformations and their far-reaching local/national effects. A qualitative analysis of (wide-ranging contributions to) current debates on the environment, food production, climate change, social inequality and welfare, higher education, art, migration, and unemployment reveals a recurring pre-occupation with expanding/encroaching markets, their advocated limits, assumed costs or promises. The negotiation of national identities is shown to unfold in relation to three inter-related phenomena: first, widening commodification; second, what Karl Polanyi termed the 'double-movement' between 'dis-embedded' economics and political counter-assertions; third, competing ideological visions of the relationship between economic activity/market forces and social order, group boundaries, solidarities and hence exclusions/inclusions.
Keywords: Austria; commodification; economic anthropology; globalization; identity politics; markets; migration; nationalism; political science; public contracts; qualitative research; social order; socioeconomics

Beyond Ethnic Entrepreneurship: An Embedded Market Approach to Group Affiliation in American Enterprise - Valdez, Zulema (Race, Gender & Class, 2008)
The traditional ethnic entrepreneurship paradigm suggests that resource mobilization based on ethnic group membership and the particular structural conditions of the economy and society combine to facilitate ethnic enterprise. Yet, this model remains largely descriptive and imprecise with respect to how and why class and ethnic resources and structural opportunity matter. Furthermore, this approach neglects to consider the likelihood that other non-ethnic social groupings distinct from ethnicity, such as those rooted in class, gender, or racial group affiliation, might also influence entrepreneurship. To address these concerns, this article introduces an "embedded market" (Block, 2003; Polanyi, 1944) approach that situates the role of group affiliation within the context of American capitalism. This approach begins with the premise that the role of group affiliation in economic action originates in and is maintained and reproduced by the social structure of the capitalist system in which it is embedded. Specifically, the embedded market approach reconsiders ethnic group membership, along with other politically-influenced social groupings (e.g. class, gender, nativity, and race) as non-essential relationships of reciprocity. In this conception, group affiliation provides the basis for compensatory relief in the form of social capital to augment market uncertainty in the modern market economy. This article uses the case of Latina domésticas to demonstrate the compensatory role of group affiliation and its corollary social capital in facilitating ethnic and "non-ethnic" enterprise in American capitalism.
Keywords: United States; business enterprises - United States; capitalism; class; doméstica; embedded market; entrepreneurship; ethnic entrepreneurship; ethnic groups; gender; race; social capital; social classes

Karl Polanyi and the antinomies of embeddedness - Gemici, Kurtuluş (Socio-Economic Review, 2008)
While Polanyi argues that all economies are embedded and enmeshed in social relations and institutions, he tends to see market economy as disembedded, which reveals a tension in his thought. The main motivation for this paper is to understand the origins of this tension. On the basis of a systematic formulation of Polanyi's work, it is argued that Polanyi employs embeddedness in a dual manner: (a) as a methodological principle akin to methodological holism, and (b) as a theoretical proposition on the changing place of economy in society. These two formulations of embeddedness contradict each other. After tracing out the origins of this contradiction, this paper concludes by considering the implications of this analysis for economic sociology. It is argued that embeddedness as a methodological principle is the only acceptable usage of the term. Yet, in this capacity, embeddedness falls short of economic sociology's goal of providing a theoretical alternative to neoclassical economics.
Keywords: Austrian history of economic thought; cultural economics; economic anthropology; economic sociology; economic systems; embeddedness; evolutionary; historical; institutional; relation of economics to other disciplines

Nano-worlds as Schumpeterian emergence and Polanyian double-movements - Randles, Sally; Dewick, Paul; Loveridge, Denis; Schmidt, Jan C. (Technology Analysis & Strategic Management, 2008)
The overarching question raised in this special issue is whether societies can, do or indeed should steer new and emergent science and technological development and its management on to trajectories construed as more or less 'desirable'. It therefore sits at the interface of two arenas. These are governance: processes of shaping/steering emergent technologies and markets; and sustainability: normative agendas incorporating a range of potentially competing conjectures and internally inconsistent desires such as to facilitate rather than stifle innovation, to enable economic development, to anticipate or deploy strategies to cope with risk and uncertainty, and to encourage technological developments that benefit rather than harm humans, their quality of life and the natural environment. Despite the potential for apparent empirical inconsistencies and contradictions that manifest as outcomes of the negotiation of these aims, there is (pace Karl Polanyi) a normative entry point to all of the articles and the material they draw upon, which is the idea that markets and technologies should be the handmaiden of societies, not vice versa. It is now widely recognized that 'nanotechnology' is a diverse set of feasible procedures emerging from scientific possibilities to enable the production of artefacts at the nanoscale creating new products, processes and services. Attention has to be paid to the desirability of these artefacts, which involve social, economic, ecologic, political and ethical matters that surround their emergence. The purpose of this special issue is to set out the current and future prospects for the widespread use (or innovation) of technological convergence at the nanoscale to create nano-artefacts, and the needs for governance and regulation that will accompany these innovations.
Keywords: POLANYI, Karl, 1886-1964; SCHUMPETER, Joseph Alois, 1883-1950; double movement; economic development; editorials; emergence; governance; nano-; nanotechnology; new product development; quality of life; sustainability; technological innovations

Where Does the Market Come From? Why the Controversy Between Polanyi's "Substantivists" and "Formalist" Neoclassical Protagonists of a Universal Market Was Never Solved" - Heinsohn, Gunnar (Property Economics: Property Rights, Creditor’s Money and the Foundations of the Economy, 2008)
In Property Economics: Property Rights, Creditor’s Money and the Foundations of the Economy - Metropolis-Verlag, 2008.
Keywords: formalist; substantivist

Polanyi's Double Movement: A Critical Reappraisal - Maertens, Eppo (Social Thought & Research, 2008)
The article offers a critical reappraisal of Karl Polanyi's claim that the restructuring of the economy based on the ideals of the self-regulating market inevitably leads society to reassert itself against the commodification of land, labour and money. Dubbed as the "double movement," the author focuses his reappraisal on the two aspects of the movement. The first refers to the push for free market reforms by various groups in society, and the second refers to the counter-movements that he argues necessarily and spontaneously mobilize against it. In this paper, he argues that the first aspect is an area that deserves further attention, both from those who wish to apply his ideas as well as from those who wish to challenge them.
Keywords: central economic planning; commodification; critique; double movement; dual economy; economic structure; free enterprise; market ideology; markets; public welfare

The Great Transformation: The Political and Economic Origins of Our Time - Meier, Brian (Social Thought & Research, 2008)
The article reviews the book "The Great Transformation: The Political and Economic Origins of Our Time," by Karl Polayni.
Keywords: Great Transformation, The (Book); book review; economics; nonfiction

Third Way Labor Law Reform in Chile - Rosado Marzan, Cesar F. (Conference Papers -- Law & Society, 2008)
Latin America is currently undergoing Karl Polanyi's "double movement" at full swing, as most governments of the region are currently experimenting with policies that defy the neoliberal orthodoxy that has been reigning there for almost three decades. One of such governments has been the center-left Concertación governments of Chile, which have been elected since the restoration of democracy in 1990. In addition to poverty alleviation programs, Concertación has been in an ongoing process of reforming the country's labor laws, attempting to restore some of the labor rights existing prior to the 1973 coup, as well as creating new rights and institutions. The labor inspectorate has been strengthened and reformed under the framework of "Latin" systems of labor inspections, which are pedagogical rather than punitive in orientation. Labor courts are also being radically bolstered, providing workers with a renewed legal avenue to enforce their rights. Although the reforms fall short of full restoration of trade union rights, namely national collective bargaining, they do point to a clear break with the "stateless" regulatory, neoliberal model that Chile was once associated with and provide symbolic and intellectual fodder for further reforms in the country and beyond. ..PAT.-Unpublished Manuscript
Keywords: Chile; Latin America; labor laws & legislation; labour laws & legislation; law reform; mixed economy

Group Affiliation and Market Embeddedness in American Enterprise - Valdez, Zulema (Conference Papers -- American Sociological Association, 2008)
In this article, Polanyi's (1944) notion of society as constituted by three forms of economic integration (market exchange, reciprocity, and redistribution) is applied to entrepreneurship. In advanced capitalism, the market-exchange relationship is the dominant form of economic integration; secondary relationships of reciprocity and redistribution, however, co-exist alongside relations of market exchange. Following Polanyi (1944), this article introduces an "embedded market" approach to enterprise. The embedded market approach considers the differential effects of primary and secondary relationships on entrepreneurial outcomes. The traditional ethnic entrepreneurship paradigm suggests that resource mobilization based on ethnic group membership is essential for entrepreneurial success, as measured by participation and earnings. The embedded market approach reconsiders ethnic group membership, along with other politically-influenced human social groupings (e.g. class, gender, nativity, and race) as non-essential relationships of reciprocity. In this conception, group affiliation provides the basis for compensatory relief from market uncertainty in the form of social capital. Ultimately, the embedded market approach provides a systematic and comprehensive approach to understanding the role of group affiliation in facilitating ethnic and "non-ethnic" enterprise in America.
Keywords: Latino/a Sociology; United States; class and gender; commercial policy; entrepreneurship; ethnic entrepreneurship; inequality; international economic integration; new business enterprises; race

The Poverty of the Global Order - Da Costa, Dia; Mcmichael, Philip (Globalizations, 2007)
This paper argues that the legitimacy of the global order depends not on economic progress alone, but on the progressive naturalization of its epistemological foundations, through 'new solutions' to old problems by states and development agencies. New solutions become methods of social control through which the dominant visions of what count as viable futures are reproduced. We critique efforts to humanize development (e.g., by the World Bank, Amartya Sen) as evidence of development's epistemological crisis. Deploying Karl Polanyi's distinction between formal and substantive economy, we consider examples of substantive economy, which realize equality through strategic sovereignty and representational power, in collective and individual terms. These represent practical and epistemological 'spaces of hope' for critique of the crisis of the market epistemology that infects development studies and international relations. Este documento sostiene que la legitimidad del orden global no depende solamente del progreso económico, sino de la naturalización progresiva de sus fundamentos epistemológicos, a través de 'nuevas soluciones' a problemas antiguos mediante estados y agencias del desarrollo. Las nuevas soluciones se convierten en métodos de control social, a través de los cuales se reproducen las visiones dominantes de lo que cuenta como futuros viables. Criticamos los esfuerzos de humanizar al desarrollo (p.e. Banco Mundial, Amartya Sen) como evidencia de la crisis del desarrollo epistemológico. Utilizando la distinción de Kart Polanyi entre economía formal y economía sustancial, consideramos ejemplos de una economía sustancial, la cual realiza la igualdad por medio de una soberanía estratégica y un poder representativo, en términos colectivos e individuales. Estas, entre otras iniciativas, representan 'espacios de esperanza' prácticos y epistemológicos para criticar la crisis de la epistemología de mercado que infecta a los estudios de desarrollo y las relaciones internacionales.
Keywords: formal economy; international law; international relations; international trade; social control; social epistemology; sovereignty; substantive economy

The making of US monetary policy: Central bank transparency and the neoliberal dilemma - Krippner, Greta (Theory & Society, 2007)
This article explores the implications of the Federal Reserve’s shift to transparency for recent debates about neoliberalism and neoliberal policymaking. I argue that the evolution of US monetary policy represents a specific instance of what I term the “neoliberal dilemma.” In the context of generally deteriorating economic conditions, policymakers are anxious to escape responsibility for economic outcomes, and yet markets require regulation to function in capitalist economies (Polanyi ). How policymakers negotiate these contradictory imperatives involves a continual process of institutional innovation in which functions are transferred to markets, but under the close control of the state. Thus, under transparency, Federal Reserve officials discovered innovations in the policy process that enabled “markets to do the Fed’s work for it.” These innovations enlisted market mechanisms, but did not represent a retreat from the state’s active role in managing the economy.
Keywords: Board of Governors of the Federal Reserve System (U.S.); United States; capitalists & financiers; monetary policy; neoliberalism; policy sciences; public spending

The political economy reader: markets as institutions - Barma, Naazneen; Barma, Naazneen H.; Vogel, Steven Kent (Routledge, 2007)
This reader combines in a single volume the key writings of classical and contemporary thinkers on political economy. The articles provide both a theoretical approach to understanding capitalism and a survey of the varieties of capitalism around the world today, examining the interaction between politics and markets both in theory and practice. Drawing on history, economics, political science and sociology, it emphasizes the ways in which markets are embedded in and influenced by political and social institutions. Steven K. Vogel and Nazneen Haider Barma provide an informative overview of a number of the most significant controversies and contemporary debates in political economy through the selections of contending perspectives on a variety of issues, including: How can rich countries make their economies more competitive? How can poor countries achieve economic development? How can post-communist countries make a successful transition to markets? Will theinformation technology revolution render the national varieties of capitalism obsolete? Does globalization imply that the national varieties of capitalism will converge to one global capitalism? A Political Economy Reader will be an essential resource for students of political economy and economic sociology.
Keywords: business & economics; capitalism; economics; international economic relations; political economy; political science; sociology

The Future of Sociology - Burawoy, Michael (Sociological Bulletin, 2007)
Like a hurricane, third-wave marketisation is picking up velocity and destroying societies in its path, destroying the very grounds upon which sociology grows. Sociology and humanity have a common interest in upholding civil society, and keeping state and market at bay. Working with Karl Polanyi's The Great Transformation, I diagnose three waves of marketisation associated with the commodification of labour, money and land, generating counter-movements at local, national and global levels. I argue that sociology is reshaped with each wave: in the first, it is utopian; in the second, it is driven by policy concerns; whereas emerging with the third wave marketisation is public sociology. The possibilities and challenges of public sociology as well as its relation to policy, critical and professional sociology are the subjects of this paper.
Keywords: commodification; countermovement; government policy; humanity; labor; marketisation; markets; nature; public sociology; social sciences; societies; sociology; utopian socialism

The battle of the ancient economy - Hindess, Barry (Economy & Society, 2007)
Ancient Athens and Modern Ideology addresses the battle between primitivism and modernism over the ancient economy, focusing especially on the contributions of three major figures, Max Weber, Karl Polanyi and Moses Finley. Finally, a short Epilogue returns to the examination of Marx's puzzle and his manifestly unsuccessful attempt to resolve it. Mohammad Nafissi uses this discussion to put this dispute out of its misery by advancing his own resolution of the primitivist-modernist dispute. Unfortunately, the limitations he seeks to avoid are mostly those which the supporters of one or the other side have identified in the claims of their opponents. As a result, his attempted resolution fails to disrupt their shared assumptions regarding the special place of the ancient Greeks in human development.
Keywords: Athens (Greece); FINLEY, M. I. (Moses Israel), 1912-1986; Greeks; WEBER, Max, 1864-1920; book review; history of economics; ideology; primitivism; socioeconomics

Public sociology vs. the market - Burawoy, Michael (Socio-Economic Review, 2007)
Building on Karl Polanyi's theory of a societal reaction to the unregulated exchange of what he called fictitious commodities—labour, money and land—this paper links the history of sociology to the history of the market. If the first wave of marketization in the nineteenth century dwelt on the commodification of labour, prompting utopian sociologies, and the second wave of marketization of the twentieth century was provoked by the commodification of money, generating national policy sociologies, then the third wave of marketization that began in the last quarter of the twentieth century includes the commodification of the environment (land, air, water), and calls for public sociologies of a global dimension.
Keywords: commercial products; fictitious commodities; government policy; history of sociology; markets - social aspects; publicity - social aspects; social theory; socioeconomics; utopian socialism

Understanding the Diverging Trajectories of the United States and Western Europe: A Neo-Polanyian Analysis - Block, Fred (Politics & Society, 2007)
This article proposes a neo-Polanyian theoretical framework for understanding the dynamics within contemporary market societies. It uses this framework to analyze the divergence between the United States and other developed societies that has become more pronounced in the first years of the twenty-first century. The argument emphasizes the shifting political alliances of the business community in the United States and suggests that from 1994 onward, business lost power in the right-wing coalition to its religious Right allies. The growing power of a religious-based social movement is a critical ingredient in the unilateralist turn in the Bush Administration’s foreign policy.
Keywords: U.S. business; economic sociology; embedded economy; embeddedness; social theory; varieties of capitalism

The Great Transformation of Embeddedness: Karl Polanyi and the New Economic Sociology - Beckert, Jens (Social Science Research Network, 2007)
I argue that in its adaptation from Karl Polanyi’s The Great Transformation, the concept of embeddedness has itself undergone a great transformation. In the process, significant meanings of the concept have vanished, while others have been added. First I explore the different meanings the concept of embeddedness has achieved in the new economic sociology. Then I argue that it is not the embeddedness of economic action that should constitute the vantage point of economic sociology, but rather three coordination problems that actors face in economic exchange: the valuation of goods, competition and the problem of cooperation deriving from the social risks of exchange. I show that by proceeding from these coordination problems economic sociology, economic anthropology and economic history can find common research questions which allow them to enter into dialogue with each other more systematically. In the next section I focus on the social-reformist inclinations of Polanyi’s use of the notion of embeddedness and thereby highlight a challenge posed in The Great Transformation that was largely not taken up by economic sociologists. Finally, I discuss limitations for developing a macro theory of the economy that result from making embeddedness the core concept of economic sociology.
Keywords: economic history; economic sociology; embeddedness; political economy

Embeddedness, Path Dependency and Social Institutions: An Economic Sociology Approach - Ghezzi, Simone; Mingione, Enzo (Current Sociology, 2007)
This paper argues for a theoretical approach based on embeddedness which assumes that the economic actor is not an atomized and utilitarian individual, but is in fact positioned within specific historical and institutional contexts in various social networks. This approach is based on Polanyi's critically debated contribution which allows for an empirical study of the diversity of institutional structures and of the significance of configurations of insertion within different social networks. Such diversity results from the double movement of disembeddedness and re-embeddedness caused by the spread of constantly emerging market opportunities, and by the importance held by the historically and culturally different selective processes of path dependency in the construction of the institutions of social regulation and of the socialized preferences of economic actors. Within these processes attention is given to the transformation of social systems based on reciprocity (household, kin, social capital networks, etc.), associations of shared interests, forms of economic organization (in a plurality of coexisting ‘economies’), unequal distribution of power, and political intervention.
Keywords: abordaje de sociologí económica; culture; dependencia de camino e institutiones sociales; developing countries; dépendance au chemin parcouru; embeddedness; empirical research; entrepreneurship; imbricación; institutions sociales; kin network; market; path dependency; reciprocity; reciprocity (commerce); social groups; social institutions; social networks; social systems; socioeconomics; utilitarianism

Reading Karl Polanyi for the Twenty-First Century - Bugra, A. (Palgrave Macmillan, 2007)
Using Karl Polanyi's analysis of the separation of politics and the economy, the book argues that the market economy is not a spontaneous process, but a...
Keywords: commodification; financial economics; macroeconomics; market economy; monetary economics

The Politics of Liquid Modernity: Polanyi and Bauman on Commodification and Fluidity - Christodoulidis, Emilios (Liquid Society and Its Law, 2007)
Book edited by Jirí Pribán This collection of essays brings together Zygmunt Bauman and a number of internationally distinguished legal scholars who examine the influence of Bauman's recent works on social theory of law and socio-legal studies. Contributors focus on the concept of 'liquid society' and its adoption by legal scholars. The volume opens with Bauman's analysis of fears and policing in 'liquid society' and continues by examining the social and legal theoretical context and implications of Bauman's theory.
Keywords: BAUMAN, Zygmunt; commodification; fluidity; law / jurisprudence; liquid modernity; philosophy; political philosophy

Neoliberalism or Democracy: Competing Forms of Social Organization in Latin America - Dowd, Jeffrey (Conference Papers -- American Sociological Association, 2007)
While political turmoil is not new to Latin America, the tension between neoliberalism and democracy can help explain present-day turmoil. The current political situation in Latin America is the result of a disconnect between the goals of democracy, in particular, between social justice goals, upon which the legitimacy of democratic government rests, and the neoliberal economic policy of the region. Polanyi's concept of the always-embedded economy states that a market economy must be embedded in a market society. Following Polanyi, I argue that markets and democracy require different forms of social organization. Markets and democracy are alternate and competing forms of social organization. The predominance of one often coincides with the restriction of the other. For example, neoliberal governance that maintains market society undermines electoral efficacy. While this may be a general attribute of neoliberalism, previous economic crisis in Latin America increased the need for rhetorical commitment to social justice goals. Latin America's structural position has not changed, however, and international finance and global organizations, like the International Monetary Fund and the World Bank, still constrain Latin American governments. I argue that any resolution to the tension between neoliberalism and democracy must accept the conflicting nature of these two forms of social organization. ..PAT.-Unpublished Manuscript
Keywords: Latin America; always embedded economy; democracy; economic policy; embeddedness; free market; free-market; market; neoliberalism; political science; political theory; social justice

Moral Views of Market Society - Fourcade, Marion (Annual Review of Sociology, 2007)
Upon what kind of moral order does capitalism rest? Conversely, does the market give rise to a distinctive set of beliefs, habits, and social bonds? These questions are certainly as old as social science itself. In this review, we evaluate how today's scholarship approaches the relationship between markets and the moral order. We begin with Hirschman's characterization of the three rival views of the market as civilizing, destructive, or feeble in its effects on society. We review recent work at the intersection of sociology, economics, and political economy and show that these views persist both as theories of market society and moral arguments about it. We then argue that a fourth view, which we call moralized markets, has become increasingly prominent in economic sociology. This line of research sees markets as cultural phenomena and moral projects in their own right, and seeks to study the mechanisms and techniques by which such projects are realized in practice.
Keywords: capitalism; culture; governmentality; moral markets; moral order; performativity

Globalization, Welfare Reform and the Social Economy: Developing and Alternative Approach to Analyzing Social Welfare Systems in the Post-Industrial Era Special Issue on Globalization: Social Justice & Social Welfare - Gonzales, Vanna (Journal of Sociology and Social Welfare, 2007)
Our understanding of the relationship between globalization and contemporary social welfare systems is heavily influenced by three conventional approaches to studying welfare reform: the political economy, moral economy, and mixed economy approaches.In addition to analyzing the strengths and weaknesses of each of these approaches, a central aim of this article is to introduce the social economy approach as an emergent alternative. Drawing from a growing body of work on institutional innovation within the European third sector, I argue that the social economy approach makes a valuable contribution to understanding the role of welfare networks in recon-figuring globalizations 'impact on the character and quality of social provision so as to better reconcile social efficacy with social justice.
Keywords: globalization; social enterprises; social inclusion; social justice; third sector; welfare networks; welfare reform

Embeddedness and the intellectual projects of economic sociology (English) - Krippner, Greta R. [b1] (analytic); Alvarez, Anthony S. [b2] (analytic) (Annu. rev. sociology, 2007)
In this review, we explore how the concept of embeddedness has shaped-and been shaped by-the evolution of the subfield of economic sociology. Although embeddedness is often taken as a conceptual umbrella for a single, if eclectic, approach to the sociological study of the economy, we argue that in fact the concept references two distinct intellectual projects. One project, following from Granovetter's (1985) well-known programmatic statement, attempts to discern the relational bases of social action in economic contexts. Another project, drawing from Polanyi's [1944 (2001), 1957 1977] social theory, concerns the integration of the economy into broader social systems. Critically, these two formulations of embeddedness involve different views of the relationship between the economic and the social. The implication is that the obstacles to theoretical integration in economic sociology, while not insurmountable, are greater than is typically acknowledged. (English)
Keywords: GRANOVETTER, Mark; Réseau; action sociale; economic sociology; economic system; economy & society; economy/society; embeddedness; firms; marché; market; markets; network; networks; social action; système économique

India's Double-Movement: Polanyi and the National Alliance of People's Movements - Levien, Michael (Berkeley Journal of Sociology, 2007)
Through an examination of India's National Alliance of People's Movements (NAPM), the largest social movement alliance resisting neoliberal globalization in India, this paper attempts to theoretically reconstruct Polanyi's theory of (t the double movement" for the neoliberal age. Polanyi famously observed that early twentieth century liberal attempts to "dis-embed" the market from social controls created unprecedented social dislocations, leading to widespread protective (< countermovements "to "re-embed" the market within social constraints. I analyze the usefulness and shortcomings of Polanyi's formulation for understanding the current politics of neoliberal globalization. Specifically, I argue that Polanyi failed to explain how a "countermovement" is politically organized and did not develop an adequate theory for the anti-market countermovement he described. Using ethnographic observation ofNAPM's efforts to organize a national alliance against neoliberal globalization, I show how the nature of a "Polanyian" constituency creates previously untheorized obstacles for the effective political organization of a countermovement. These obstacles derive from inherent characteristics of a Polanyian constituency: 1) the economic and social diversity of—and therefore potential antagonism between—its prospective agents, who do not share similar relationships to the means of production, but only the common fact of being negatively affected by the market, and 2) the vastly different ways in which such diverse groups experience market displacements, leadings to a proliferation of single-issue movements whose commonality is hard to perceive and unity difficult to build.
Keywords: India; constituents; double movement; globalization; international alliances; neoliberalism; protest movements; resistance movements; social movements

Beyond the boycott: labor rights, human rights, and transnational activism - Seidman, G. (Russell Sage Foundation, 2007)
Keywords: business & economics - international; business & economics / business ethics; law / labor & employment; political science / human rights; political science / labor & industrial relations; political science / labour & industrial relations; social science - developing and emerging countries; social science / sociology / general

Time–space intensification: Karl Polanyi, the double movement, and global informational capitalism - Ó Riain, Seán (Theory and Society, 2006)
This article advances the concept of “time–space intensification” as an alternative to existing notions of time–space distanciation, compression and embedding that attempt to capture the restructuring of time and space in contemporary advanced capitalism. This concept suggests time and space are intensified in the contemporary period – the social experience of time and space becomes more explicit and more crucial to socio-economic actors’ lives, time and space are mobilized more explicitly in individual and corporate action, and the institutionalization of time and space becomes more politicized. Drawing on Polanyi’s concepts of fictitious commodities and the double movement, and developing them through an analysis of work organization and economic development in the Irish software industry, the article argues that the concept of time–space intensification can add significantly to our understanding of key features of the restructuring of the temporal and spatial basis of economic development and work organization.
Keywords: capitalism; double movement; fictitious commodities; social theory; time-space intensification

Globalization and contestation: A Polanyian problematic - Munck, Ronaldo (Globalizations, 2006)
The Polanyian problematic presents us with a unified, complex, and dialectical means to interpret globalization and its social contestation by diverse social and political forces. For Karl Polanyi (1886–1964), globalization as we know it would probably be conceived of as an extension of the ‘one big self-regulating market’ he discerned in his day, while his belief that ‘simultaneously a counter-movement was afoot’ provides an interpretative lens to examine the various facets of the counter-globalization movement. The Polanyian problematic of modern history as a ‘double movement’, whereby market expansion and social protection respectively lead phases, provides a useful antidote to all forms of economic reductionism when dealing with globalization on the one hand and political voluntarism with regard to contestation on the other. Basically, globalization is a human construct, and it can thus be deconstructed by society.
Keywords: Polanyi problem; countermovement; globalization

The Relationship between Economics and Sociology: The Contribution of Economic Sociology, Setting out from the Problem of Embeddedness - Rizza, Roberto (International Review of Sociology, 2006)
s essay aims to analyse the most recent acquisitions in economic sociology, setting out from the problem of embeddedness. Firstly, the contribution offered by Mark Granovetter shall be illustrated, demonstrating how the interpretation proposed by this scholar is concentrated on a structural-relational perspective that tends to trace the explanation of economic phenomena to a theory of social networks. In order to enrich and integrate this approach, the contribution offered by the new-institutionalist perspective in contemporary economic sociology will be emphasised, which has focused on the social construction of economic institutions. This current has underlined, on the one hand, the cognitive dimension of embeddedness, related to the way in which the uniformities structured by mental processes limit economic reasoning, and, on the other, the cultural dimension of embeddedness, concerning the role of collectively shared representations in the formation of economic goals. It will be concluded by illustrating the acquisitions of some theoretical perspectives linked to the polanyian tradition that have developed a 'plural' conception of economy, founded on the emphasis of socio-regulative principles, such as those of exchange, redistribution and reciprocity, which, in becoming hybrid, give shape to variable and historically anchored economic worlds. The concept of embeddedness roots historically and transmits a vision of economic processes as inseparable from noneconomic institutions
Keywords: GRANOVETTER, Mark; economic research; economic sociology; embeddedness; industrial management; social sciences; socioeconomic factors; socioeconomics

Governing the Market: The "Political" and the "Economic" in the Restructuring of the "Third World" - Makki, Fouad (Conference Papers -- International Studies Association, 2006)
My intention in this paper is to rethink the central contentions of "Globalization Theory" with respect to the relationship of the "state" to the "economy." I will do so via a consideration of recent discussions of the formation of the modern states system within the discipline of International Relations, and Karl Polanyi?s suggestive notion of the "double movement" presently enjoying a revival in sociological studies of the conjuncture of the 1990s. The paper concludes with reflections on how these critical reflections might make it possible to gain a betterappreciation of the current neoliberal restructuring of the erstwhile "Third World." PAT.-Conference Proceeding
Keywords: economic structure; economics; globalization; international markets; international trade

The Dark Side of Embeddeness: The Construction of Economic space and Prestige in Italy 1896-1907 - Polillo, Simone (Conference Papers -- American Sociological Association, 2006)
The creation of a national economic space is the necessary structural condition for the unfolding of the "self-protective" measures of society that Polanyi analyzed for the post-WWI period, and that he saw as more generally arising in response to free market policies. A national economic space is itself the product of specific institutional arrangements, in particular the state agencies that allow the state to centralize the monetary system in its own hands: in the modern period, these have been central banks. By analyzing a longitudinal sample of the minutes of the meetings of the governing body of the Bank of Italy in its crucial transitional period at the turn of the century (1896-1907), this paper attempts to trace the historical process by which the Italian economy came to be understood as a national space. It shows that the creation of an area of economic prestige measured by the technical success of the central bank and the strength of its relationship with the Treasury was a crucial achievement of the liberal state. ..PAT.-Unpublished Manuscript
Keywords: Italy; World War I; banking industry; central bank; embeddedness; manuscripts; monetary policy; money; saving and investment; self-protective measures; state

Retelling the Great Transformation - Steinberg, Marc (Conference Papers -- American Sociological Association, 2006)
In this paper I partly retell Polanyi's narrative of the industrial revolution found in his Great Transformation. I discuss how new labor laws consolidated in the 19th century created a legal structure of coerced contractual labor, that did not fit the ideals of free market economics. My retelling focuses on how capitalists in some industries relied on legal coercion of their workers as a means of discipline and labor process control. Through this retelling I demonstrate that Polanyi was still beholden to neo-classical economics in his historical account, errantly seeing the rise of a free market in labor with the Poor Law reforms of 1834 when in fact no such freedom existed. Therefore, he could not provide a fully-fledged institutional analysis of economic embeddedness that lies at the core of his theory. To realize a fully-developed institutional analysis I argue that we need to bring class conflict back into the narrative of institutional change through an analysis of legality and its transformation. I partly map out the outlines of a revised institutional analysis that places emphasis on the spatial organization of power, with 'stateness' conceptualized as a variable in which political power (and more especially authority) is scrutinized as historically accreted institutional structures. I also emphasize the historically specific role of the 'local state' in this narrative. ..PAT.-Unpublished Manuscript
Keywords: capitalists & financiers; criminal procedure; industrial laws & legislation; industrial relations; institutional embeddedness; labor laws & legislation; labour laws & legislation; law; quality control

Embeddedness as a Process - Chajewski, Leszek (Conference Papers -- American Sociological Association, 2005)
This article describes a strategy of modeling embeddedness of economic behavior as a process, as opposed to viewing it as a time-independent relationship between behavior and a social factor in which it is subsumed. I first reconstruct Polanyi's classic processual model of embeddedness and derive from it a set of intuitive tests, which are then applied to key modern approaches in economic sociology: structural, neo-institutional, neo-weberian and Fligstein's embeddedness-as-identity-formation approach. Finally, I describe main analytic and empirical consequences of the processual approach to embeddedness. Key among these consequences is that not all forms of embeddedness are of equal significance, therefore, economic sociology's empirical focus should shift from demonstrating that behavior is more likely to be embedded than not, to the forms of economic behavior that are likely to dominate alternative types of behavior.
Keywords: cultural and neo-weberian perspectives in economic sociology; economic sectors; economic systems; embeddedness; embeddedness and identity formation; embeddedness process; empirical research; forms of economic integration; market transitions; neo-institutionalism; new economic sociology; social factors; social status; socioeconomics

"Economic Life, Institutions, and Social Action: Reflections on Polanyi's Approach to Studying Economic Life" - Gemici, Kurtulus (Conference Papers -- American Sociological Association, 2005)
The article focuses on the relevance of economist Karl Polyani's economic theories and tries to analyze if his book titled "The Great Transformation," could be considered as the foundation of current economic sociology and international political economy. The author of the article says that Polayni's theories focuses on contemporary economic sociology, market economy's self-destructive approach and consideration of the market economy as integral part of the society. His work on institutedness and economy's embedness in society are working as base for most of the challenging theories in economic sociology.
Keywords: Great Transformation, The (Book); capitalism; economic behavior; economics; embeddedness; institutions; methodology; socioeconomics

Globalization - McMichael, Phillip (The Handbook of Political Sociology states, civil societies, and globalization, 2005)
Philip McMichael casts a critical eye on the process of globalization suggesting that it takes different forms across time and space. He specifies contemporary globalization as a discursive project, geared to institutionalizing corporate markets through multilateral and regional economic agreements driven by powerful states. From this perspective of depicting globalization as an exercise in power, he examines political countermovements to globalization. Global justice movements, he argues, are globalization’s “historical and relational barometer,” and they operate at various, but often interrelated, scales. Work- ing from Karl Polanyi’s “double movement” of implementation of and resistance to economic liberalism, McMichael questions the adequacy of Polanyi’s formulation for the elaboration of market rule in the twenty-first century. This question concerns the conventional interpretation of “sovereignty” as the centerpiece of nation-state formation, including the development of citizenship. Here, globalization is viewed through the lens of a sovereignty crisis, where corporate market rule compromises the social contract upon which the state/citizen relation is founded. The crisis is expressed differently across the world, as the impact of market rule generates alternative social movement conceptions of sovereignty, especially in the global south where corporate globalization is realized through a drastic intensification of social exclusion.
Keywords: counter-movement; critique; double movement; globalization; political sociology

The Continuing 'Wind of Change' in the Balkans: Sources of Housing Inequality in Bulgaria - Vesselinov, Elena (Urban Studies (Routledge), 2004)
The research in this paper explores the institutional changes in the housing system during the period of market transition in Bulgaria, which follow suit with the greater societal transformations. The societal changes are linked theoretically with Polanyi's understanding of the transition from a non-market to a market society. His argument helps in establishing the institutional context of the macroeconomic changes in the past decade. The article then focuses on the changing sources of housing inequality. It is argued that there are two urban regimes of housing inequality: the regime of controlled uniformity during the period of socialism and the regime of primitive diversity during the period of market transition. The two regimes are produced mainly through the changing role of the state.
Keywords: Bulgaria; cities & towns; equality; housing; macroeconomics; socialism; urban studies

Globalization, Labor and the 'Polanyi Problem' - Munck, Ronaldo (Labor History, 2004)
This article outlines what the Polanyi problem consists of and provides information on some of the implications that arise in developing a Gramscian/Polanyian strategy of counter-hegemony for the labor and the modern social movements, as of August 2004. Labor and new social movements are allegedly an integral element for a progressive solution of the so-called Polanyi problem, which is how the tendency towards the creation of a global free-market economy can be reconciled with a degree of stability and cohesion in society. Taking a Polanyian perspective allows the development of a historical perspective on the dual transformations of globalization and labor. Towards the end of the Second World War, Karl Polanyi wrote of how a self-regulating market that allegedly could not exist for any length of time without annihilating the human and natural substance of society. Such a utopia would allegedly destroy humanity and transform the world into a wilderness, an opinion mirrored by modern eco-socialists. The strategy and ideology of globalization as transformative revolution seems to echo and confirm Polanyi's account of the 19th century industrial revolution, an attempt to set up a self-regulating market.
Keywords: GRAMSCI, Antonio, 1891-1937; Polanyi and Gramsci; Polanyi problem; counter-hegemony; economic policy; free enterprise; globalization; international relations; labor movement; labour movement; social movements

Economic Sociology’s Legacy to Corporate Governance, 2004 - Kahn, Faith Stevelman (Conference Papers -- Law & Society, 2004)
This paper explores the intellectual tradition of Max Weber,Emil Durkheim, Joseph Shumpeter and Karl Polanyi — economic sociologists whose work has been largely ignored by corporate governance scholars focused on the more traditional areas of economics. The foundation laid by Weber is the central focus of the paper. Weber's writing in Economy and Society laid the groundwork for an approach to the study of firms and markets that diverges significantly from that in of the neoclassical economic model. Weber viewed firms and markets as being deeply embedded in and inseparable from the larger systems of social values and social structures that make a society durable. He grounded his view of economic action in a view of social action. Social actions are all deliberate (meaning purposive, which would include deliberately passive) acts undertaken in contemplation of others' acts and reactions. Transactions in money are generally social actions, since the value of money is determined by what people will decide to give you for it! Economic actions are constantly ormed by patterns of meaning, systems of power and social systems (the family....) that underlie them. From this perspective, the growth of the firm has as much to do with the need for rationalization and the rational/economic division of labor (esp. in a condition of limited liability) as it does with any immediate reduction of transaction costs. Rationality ( the struggle for meaning and systems that order chaos) is as pressing a force as efficiency. Recent writing in economics has come close to building a bridge back to economic sociology, especially with its interest in the effects (or lack of) trust in economic transacting as well as other "behavioral" variations. Economic sociology pursues these departures from qualitative rationality at the level of social structure, rather than individual psychological aberrancy. This paper tries to broader this more "socially" oriented view of the behavior of human beings in firms and markets. This intellectual background is related to contemporary issues in corporate governance legislation, and especially the Sarbanes Oxley reforms and then the increased demand for independent directors at public companies and mutual funds.
Keywords: DURKHEIM, Emile; WEBER, Max, 1864-1920; corporate governance; economic sociology; social action; social structure; socioeconomics

The third way and the third world: poverty reduction and social inclusion in the rise of 'inclusive' liberalism - Porter, Doug; Craig, David (Review of International Political Economy, 2004)
In the wake of frank neo-liberalism, and in the context of rising security fears, ways are being found to provide market liberalism with a more inclusive face. The Poverty Reduction Strategies currently prominent in international development, and Thirdway OECD 'Social Inclusion' policy frames claim common purpose to promote 'opportunity, empowerment and security' for people and places on the peripheries of global economies and societies. They share commitments to global economic integration and openness, market led growth, 'good' and 'joined up' governance, local and social partnerships, and wide-ranging activation of 'capacities'. But the high rhetorical aspirations of liberalism to social 'inclusivity' have so far overreached empirical gains for the poor. Drawing on developing country examples of Poverty Reduction Strategy and public policy in New Zealand's current Labour government, this paper sketches salient features of 'inclusive' liberalism. It critically examines its status as a Polanyian turn within a wider liberal project, which seeks to re-embed and legitimate a liberal social and economic order.
Keywords: New Zealand; developing countries; international competition; international political economy; liberalism; political planning; poverty; poverty reduction; self-efficacy; social inclusion; third way

Third Worldism and the lineages of global fascism: the regrouping of the global South in the neoliberal era - Patel, Rajeev; McMichael, Philip (Third World Quarterly, 2004)
We come to an analysis of Third Worldism through an historical understanding of the development project, one that locates Third Worldism as a moment in a broader series of resistances both to capital and colonialism, and to the techniques used by the state to maintain hegemony. Viewing Third Worldism in this wider context, we argue, enables us to not only explain the failure of Third Worldism to deliver on its vision of emancipation from colonialism, but to also explain the shape of contemporary resistance to the world capitalist order. We argue that the theory and practice of development depends on a certain biopolitics, rooted in a regime of sovereign state control, and designed to mobilise citizens in ways favourable to capital. We hold that Third Worldism embraced this form of sovereignty and its biopolitics. Further, by blending cultural studies analysis with a Polanyian interpretation of the rise of fascism, we argue that Third Worldism can be situated as a moment in the maturation of 'global fascism'. Finally, we argue that contemporary resistances to neoliberalism have recognised the complicity of the state with capital. These 'new internationalisms' arise from the ashes of Third Worldism, with an altered understanding of 'sovereignty' that challenges the trajectory of the Third World sovereign state.
Keywords: biopolitics (sociobiology); capitalism; colonies; fascism; global capital; global fascism; hegemony; liberty; sovereignty (political science)

Social Exclusion in a Comparative Context - Reimer, Bill (Sociologia Ruralis, 2004)
This paper outlines a framework for understanding social exclusion that is multidimensional, dynamic, multi-leveled, and relational. Inspired by Polanyi's classification of the modes of economic inclusion, we propose that social inclusion and exclusion processes are rooted in four types of social relations: market (exchange and barter), bureaucratic (rational-legal), associative (common interest), and communal (complex reciprocity and shared identity). Each type reflects different, but integrated processes of social exclusion and inclusion. These four types are outlined conceptually, then operationalized using data from a Canadian survey conducted in 1995 rural households. The results show the extent to which the four types of relations are used for social support, their interdependence, and their relationship to selected household characteristics and outcomes. The policy implications discussed emphasize the ways in which building capacity in all four types of relations can increase the level of social inclusion.
Keywords: Canada; economic inclusion; rural sociology; social exclusion

Desolation and Enlightenment: Political Knowledge After Total War, Totalitarianism, and the Holocaust - Katznelson, Ira (Columbia University Press, 2004)
During and especially after the Second World War, a group of leading scholars who had been perilously close to the war's devastation joined others fortunate enough to have been protected by distance in an effort to redefine and reinvigorate Western liberal ideals for a radically new age. Treating evil as an analytical category, they sought to discover the sources of twentieth-century horror and the potentialities of the modern state in the wake of western desolation. In the process, they devised strikingly new ways to understand politics, sociology and history that reverberate still. In this major intellectual history, Ira Katznelson examines the works of Hannah Arendt, Robert Dahl, Richard Hofstadter, Harold Lasswell, Charles Lindblom, Karl Polanyi, and David Truman, detailing their engagement with the larger project of reclaiming the West's moral bearing. In light of their epoch's calamities these intellectuals insisted that the tradition of Enlightenment thought required a new realism, a good deal of renovation, and much recommitment. This array of historians, political philosophers, and social scientists understood that a simple reassertion of liberal modernism had been made radically insufficient by the enormities and moral catastrophes of war, totalitarianism, and holocaust. Confronting their period's dashed hopes for reason and knowledge, they asked not just whether the Enlightenment should define modernity, but which Enlightenment we should wish to have. Decades later, in the midst of a new type of war and reanimated discussions of the concept of evil, we share no small stake in assessing their successes and limitations.
Keywords: ARENDT, Hannah; World War II; fascism; military history; political history; political philosophy; political theory; totalitarianism

Polanyi Symposium: a conversation on embeddedness - Krippner, Greta; Granovetter, Mark; Block, Fred; Biggart, Nicole; Beamish, Tom; Hsing, Youtien; Hart, Gillian; Arrighi, Giovanni; Mendell, Margie; Hall, John; Burawoy, Michael; Vogel, Steve; et al. (Socio-Economic Review (2004), 2004)
This conversation, transcribed from a conference in April 2002, is intended to illuminate current debates about the use and abuse of the embeddedness concept in economic sociology.
Keywords: economic sociology; embeddedness; markets; symposium

Introduction: Open Markets versus Welfare Citizenship: Conflicting Approaches to Policy Convergence in Europe - Taylor-Gooby, Peter (Social Policy & Administration, 2003)
Few would have predicted the rapid progress of the EU in developing common economic institutions 20 or 30 years ago, although many commentators might have foreseen the relatively slow development of convergent social policies. This paper sets the European debate in the context of the path-breaking work of Polanyi and Schumpeter at the end of the Second World War. It argues that the economic institutions of the EU are at least as important as the social policy institutions in understanding current developments, and suggests that a commitment to a broadly liberal market agenda at the economic level constrains and moulds social policies.
Keywords: European Union; SCHUMPETER, Joseph Alois, 1883-1950; economic institutions; market; social policy; welfare state

Global Transformation and Local Countermovements: The Prospects for Democracy Under Neoliberalism - Udayagiri, Mridula; Walton, John (International Journal of Comparative Sociology (Sage Publications, Ltd.), 2003)
This article compares Mexico and India's experiences with neoliberalism to propose that the collapse of the development state generates countermovements. In both nations, neoliberalism is associated with the decline of the one-party deminant system, and a restructuring of civil society. Variations emerge in the timing of democratization in these countries. In India, democratization preceded neoliberal reforms, whereas in Mexico democratization followed neoliberal reforms, but in both cases democratization mitigates the effects of neoliberalism on civil society. Conclusions drawn from the comparative analysis of Mexico and India concur with Karl Polanyi's proposition that there is a double movement of marketization and protectionest countermovements. The case studies suggest a pattern to these countermovements. Actors are confronted abruptly with threats to their well-being; not only economic threats but also environmental, political , and symbolic threats. The threatened value in each case is a former entitlement, typically a form of protection ensured by the state. Thus, even in the presence of countermovements, neoliberalism mediates a divergence of state and civil society relationships creating uncertain futures for democratic possibilities.
Keywords: India; International Monetary Fund; Mexico; democracy; democratization; liberalism

The World-Historical Origins of Pan-Islamic Nationalism in Iran - Araghi, Farshad (Conference Papers -- American Sociological Association, 2003)
In examining the world-historical context of the rise of pan-Islamic nationalism in Iran, this paper posits Islamic fundamentalism as a modern and global (rather than premodern and local) movement. Drawing on Polanyi and linking economy, polity, and culture, this study traces the origins of pan-Islamic nationalism in Iran to the transformation of the world-market relations in the second half of the nineteenth century and the rise of the food/agrarian regime after 1870. It shows that the relations of the state and the mercantile classes with the world market led to conflicting developments, viz., the national "contraction" of the state on the one hand and the international "expansion" of commercial classes on the other hand. The latter, in the course of their struggles for state representation, merged with the rising pan-Islamic reaction against European expansion in the "Islamic world." Pan-Islamism, by its capacity for articulating the economic nationalism of the mercantile classes in ethical terms, mobilized the masses of people for the struggle for the nationalization of the state. Hence, as a historical form, modernity and nationalism in the late nineteenth century Iran took a nonsecular character. Later, the Cold War politics revivified the pan-Islamic component of Iranian nationalism, creating the context for the rise to power of fundamentalism in the 1980s. The paper warns against the reification of place and culture rooted in binary conceptualizations of the local and the global phenomena.
Keywords: Iran; Islam; Islamic fundamentalism; culture; fundamentalism; market; nationalism; pan-Islamism; protestant fundamentalism; religion; religious fundamentalism; world; world-market relations

Labor Organizing and Neoliberal Politics - Rudy, Preston (Conference Papers -- American Sociological Association, 2003)
Neo-liberal policies and practices which impugn state policies as artificial interferences in the smooth operation of markets are at work globally, nationally and locally. Based on research about the Justice for Janitors in California, this paper examines the experience of the campaigns in San Jose and Sacramento. The paper is organized around a tension between two issues about markets that are explained by Karl Polanyi: their social reality as complex political constructions and the ideological justification for disembedding markets, aka the "Liberal Creed". In both campaigns the Justice for Janitors exposed the embeddedness of employers. On the other hand, in the ideological construction of their campaigns, the Justice for Janitors have not clearly confronted the "liberal creed" that justifies neo-liberal market practices. The JfJ campaigns have been successful at creating accountability for employers and politicians by revealing the concrete social relations within which markets are embedded, though they have largely failed to articulate an oppositional ideology to the liberal creed. At a minimum confronting this creed would place the state as central to the construction of market practices. The successes at instituting accountability of employers to democratic communities and the centrality of the state in securing that accountability will be undermined unless JfJ exposes the flaws of the liberal creed and clearly explains the importance of the state in securing the justice they seek.
Keywords: United States; ideology; labor; labour; liberal creed; liberalism; markets; neoliberalism; political planning

Reinstituting the Economic Process: (Re)embedding the Economy in Society and Nature - Adaman, Fikret; Devine, Pat; Ozkaynak, Begum (International Review of Sociology, 2003)
Polanyi argued that the project of creating a fully self-regulating market was utopian, in the sense of impossible. However, movement towards this utopia, the ever greater but never completed process of disembedding the economy from both society and nature, creates growing dislocations and tensions which call forth a counter movement. This double movement may be thought of as successive changes in the way in which the economic process is instituted. The focus of the paper is on the meaning of embeddedness, the ways in which the economy was reinstituted during the Great Transformation and the subsequent counter movements, and alternative approaches to further reinstituting the economy in ways that disembed it further or (re)embed it more firmly in society and nature. It is argued that prior to the creation of the capitalist market the economy was organically embedded in society and nature. However, the creation of separate economic institutions, the institution of the economic process as a distinct system with its own laws of motion, severed these organic links and the economy came to dominate both society and nature. Here, however, the symmetry between society and nature ends. Society has the capacity for conscious, purposeful action; nature does not. For the economy to be reinstituted in ways that create a sustainable organic relationship with nature, it must first be reinstituted in ways that bring it under social control.
Keywords: CAPITALISM; POLANYI, Karl, 1886-1964; SOCIAL control; UTOPIAS; capitalism; economic development; economic policy; embeddedness; nature; social control; utopias

Institutions, Politics and Culture: a Polanyian Perspective on Economic Change - Harriss, John (International Review of Sociology, 2003)
Presents the perspective of philosopher Karl Polanyi on economic change. Works of Polanyi on the topic; Analysis of pre-modern economies by Polanyi. According to Jeffrey Nugent, institutions make social life fairly predictable by restricting some actions and providing incentives for other actions. The article discusses Polanyi's book "The Great Transformation," the self-regulating market economy, scarcity, individual choice, economic development in India, trust in India's corporate sector, new institutional economics, and distribution of private property rights.
Keywords: Great Transformation, The (Book); India; NUGENT, Jeffrey; economic development; institutional economics; personal property; philosophers; scarcity; social interaction

The Enforcement of Contracts and Property Rights: Constitutive versus Epiphenomenal Conceptions of Law - Hodgson, Geoffrey M. (International Review of Sociology, 2003)
Discusses various conceptions of law. Concept of law as an epiphenomenon of underlying structures; Views of economist Karl Marx on law. Discusses doctrine of individualism, constitutive role of law, property rights, contracts, the emergence of law, social ontology, the relations of individuals with social structures, self-organizing institutions, self-enforcement, Karl Polyani's view that self-regulating markets are unattainable, rule of law, social reality, and how the nature of legal relations affects socio-economic behavior.
Keywords: MARX, Karl, 1818-1883; economists; individualism; law; personal property; rule of law; social reality; social structure; socioeconomics

Moral Philosophy and Economic Sociology: What MacIntyre Learnt from Polanyi - McMylor, Peter (International Review of Sociology, 2003)
Focuses on the issue of moral philosophy and economic sociology. Views of philosopher Alasdair MacIntyre on morality; Works on morality. Discusses morality in social science, Karl Polyani's writings on the social context of economic change, Marxist socialism, human cooperation, social relations, self-interest, moral responsibility, market order, public ownership, redistributive taxation, social welfare, Max Weber's ethic of responsibility, and the connections between MacIntyre's and Polyani's thoughts on morality.
Keywords: MACINTYRE, Alasdair C.; Marxian economics; WEBER, Max, 1864-1920; ethics; moral and ethical aspects; philosophers; responsibility; social psychology; social sciences; socioeconomics; sociology

The Creation of the European Market for Mobile Telephony: Overview of an Instituted Process - Mina, Andrea (International Review of Sociology, 2003)
Focuses on the creation of the European market for mobile telephony. Merits of the global system for mobile communications; Reasons for the emergence for a market for mobile telephony. Discusses the socio-economic factors that influenced the development of the mobile telephony market, the writings of Karl Polyani, instituted process, the process of standardization, digital technology, European telecommunications during the 1980s, and the development of market structure in the global equipment industry.
Keywords: Europe; global system for mobile communications; industrial organization (economic theory); instituted economic process; instituted process; mobile communication systems; standardization; telecommunication

Polanyian Perspectives on Instituted Economic Processes, Development and Transformation: Introduction - Ramlogan, Ronnie; Harvey, Mark (International Review of Sociology, 2003)
Focuses on the presentation 'Polanyian Perspectives on Instituted Economic Processes, Development and Transformation' at an international workshop held at Manchester, Connecticut. Organizer of the workshop; Theme of the workshop. The workshop was organized by the Centre for Research on Innovation and Competition. The article discusses varieties of capitalism, supply and demand, price formation, competition, economic motives, market economy, and the book "The Great Transformation," by Karl Polyani.
Keywords: Connecticut; Great Transformation, The (Book); Manchester Conn.; POLANYI, Karl, 1886-1964; United States; capitalism; competition; supply and demand; workshops (adult education)

Issues for a Neo-Polanyian Research Agenda in Economic Sociology - Randles, Sally (International Review of Sociology, 2003)
Kari Polanyi Levitt has commented that her father's writing was met with a 'deafening silence' in England, a silence which she suggests is 'yet to be explained'. Given The Great Transformation was purposefully, situated in England Polanyi Levitt's point is an interesting one, and one which still deserves attention. But the last two decades have witnessed an intensification of interest in Karl Polanyi's methodological approach and theoretical insights, from England as well as elsewhere, and representing a range of disciplines. This raises a string of associated questions: interest from who? Why now? And how? Further we could ask: Does this new interest have the potential to redress the Polanyi Levitt charge without falling prey to an opposite one of misusing or abusing the Polanyi legacy? This paper contributes to the much larger agenda of examining in a serious way the usefulness and applicability of Polanyi's key ideas and methods, particularly as they apply to the burgeoning interest in markets and exchange within New Economic Sociology (NES). A sub-set of this agenda is to explore whether Polanyian insights provide a more nuanced and critical understanding of competitive processes and innovation than is currently available within Economics, Sociology or indeed Economic Sociology.
Keywords: England; Great Transformation, The (Book); POLANYI LEVITT, Kari; POLANYI, Karl, 1886-1964; Polanyi's legacy; economic sociology; economics; socioeconomics; sociology

Karl Polanyi and the writing of The Great Transformation - Block, Fred (Theory & Society, 2003)
Karl Polanyi’s 1944 book, The Great Transformation , has been recognized as central for the field of economic sociology, but it has not been subject to the same theoretical scrutiny as other classic works in the field. This is a particular problem in that there are central tensions and complexities in Polanyi’s argument. This article suggests that these tensions can be understood as a consequence of Polanyi’s changing theoretical orientation. The basic outline of the book was developed in England in the late 1930s when Polanyi was working within a specific type of Marxist framework. However, as he was writing the book, he developed several new concepts, including fictitious commodities and the embedded economy, that led in new directions. Because circumstances did not give him the time to revise his manuscript, the book is marked by a tension between these different moments in his own theoretical development. The result is that Polanyi glimpses the concept of the always embedded market economy, but he does not name it or elaborate it.
Keywords: Great Transformation, The (Book); capitalism; economics; sociology

For a Sociological Marxism: The Complementary Convergence of Antonio Gramsci and Karl Polanyi - Burawoy, Michael (Politics & Society, 2003)
Analyzes the Marxist concept of society to interpret the rise and fall of communist orders, the shift from politics of class to politics of recognition, the transition from colonialism to postcolonialism and the development of an emergent transnationalism. Relationship between sociology and Marxism; Genesis of a sociological Marxism; Theorists of society and socialism.
Keywords: GRAMSCI, Antonio, 1891-1937; administration and politics; communism and society; postcolonialism; socialism; sociology; transnationalism

The Near-Death of Liberal Capitalism: Perceptions from the Weber to the Polanyi Brothers - Roth, Guenther (Politics & Society, 2003)
Provides an overview of some critical moments in the history of liberal capitalism as perceived by some historical witnesses. Views of brothers Max and Alfred Weber on the world economy before 1914; Historical parallels to the introduction of euro bills and coins in January 2002; Access of Germany to the world market for demographic and geographic reasons.
Keywords: Euro; POLANYI, Michael, 1891-1976; WEBER, Alfred; WEBER, Max, 1864-1920; administration and politics; capitalism; economics; history of liberal capitalism

Polanyi's 'Double Movement': The Belle Époques of British and U.S. Hegemony Compared - Silver, Beverly J.; Arrighi, Giovanni (Politics & Society, 2003)
Presents a comparative analysis of the double movement of the belle époque and collapse of British hegemony with the double movement of the late 20th and early 21st century belle époque and current crisis of U.S. hegemony. Emphasis on the book 'The Great Transformation,' by Karl Polanyi; Liberal crusade for free markets in the 1830s and 1840s; Role of Great Britain as the central entrepôt of world commerce and finance.
Keywords: Great Britain; Great Transformation, The (Book); United States; administration and politics; commerce; double movement; free enterprise

Employment, flexible working and the family - Crompton, Rosemary (The British Journal of Sociology, 2002)
This paper assesses some of the implications of one of the major social changes to have taken place in the West during the second half of the twentieth century — that is, the increased employment of women, together with normative changes in gender relations and in women's expectations. These changes have been linked to an increase in individualism, which itself is associated with the transcendence of ‘first modernity’. Thus it is suggested that new approaches to social analysis are required (Beck). Here it is argued that, rather than develop completely new approaches in order to grasp the changes that are under way, the ‘economic’ and the ‘social’ (that is, employment and the family) should be seen as intertwined, rather than approached as separate phenomena. Past debates in feminism, changes in the family, and flexible employment are critically examined. The growing tensions between employment and family life are discussed. It is argued that these changes are associated with the intensification of capitalist development, rather than reflecting a fundamental transformation of society. Existing approaches to the analysis of social change, including Polanyi's analysis of the development of ‘counter-movements’ against the ‘self-regulating’ market, will, therefore, still be relevant to our enquiries. In the concluding section, a programme of research that would examine these changes is outlined.
Keywords: capitalism; family; flexible employment; gender; modernity

Anomie, Social Change and Crime - Bernburg, Jon Gunnar (British Journal of Criminology, 2002)
The last decade has seen a revived interest in using anomie theory in crime and deviance research. The present paper contributes to this development by offering an examination of a particular extension of anomie theory, namely, Messner and Rosenfeld's Institutional-Anomie theory. Explicating Institutional-Anomie theory relative to the sociologies of Durkheim, Merton and Polanyi, I find that this theory goes beyond Merton by using a strain of thought that is critical of liberal society. By bringing in the notion of the disembedded market economy, a central notion in the institutionalism of Polanyi and Durkheim, this theory links crime, anomie, and contemporary social change. I also discuss some of the limitations of linking crime with societal level processes in a Durkheimian rather than Mertonian manner.
Keywords: DURKHEIM, Emile; MERTON, Robert; anomie; crime; criminology; disembeddedness

The 'new contractualism', social protection and the Yeatman thesis - Gaby Ramia (Journal of Sociology, 2002)
An important characteristic of public policy formulation over the 1980s and 1990s, particularly in the English-speaking countries, has been the increasing use of contractual principles as regulatory tools. The 'new contractualism' represents the recent re-emergence and adaptation of the social contract of the 17th and 18th centuries and the classical legal contract that emerged in the 19th century. The work of Anna Yeatman provides the most cogent and influential, non-neo-liberal scholarly appraisal of the new contractualism. Yeatman argues that the current contractualist agenda is consistent with equality of opportunity, occasioning a redefinition of citizenship so as to improve on the discourse of social protection. This paper argues that any attempt to remove social protection flawed though it is from discussions of the new contractualism is artificial. The social justice implications of such a position are perilous, for policy formulation has not yet entered a phase in which social protection can be superseded in a way which does not violate the rights of the socio-economically disadvantaged.
Keywords: English-speaking countries; YEATMAN, Anna; citizenship; commodity fiction; contractualism; double movement; equality; fictitious commodities; governance; human rights; political planning; social justice; social movements; social protection; sociology

Towards a Theory of Values-Based Labeling - Barham, Elizabeth (Agriculture and Human Values, 2002)
An outline of a theory of values-based labeling as a social movement argues that it is motivated by the need to re-embed the agro-food economy in the larger social economy. A review of some basic premises of embeddedness theories derived from the work of Karl Polanyi reveals their connection to particular values-based labeling efforts. From this perspective, values-based labeling presents itself as primarily an ethical and moral effort to counter unsustainable trends within presently existing capitalism. These labels distinguish themselves from ordinary commercial labels by a focus on process and on quality. Evaluating the transformative potential and progressive nature of values-based labeling poses a key challenge. One avenue for gauging this potential is conventions theory. This approach can be adapted to consider the decision making processes that go on within values-based labeling groups, as well as consumer decision making based on such labels, as instances of what is termed a politics of ethical judgment. The conclusion emphasizes the need for more research in this area and suggests how it could be furthered.
Keywords: agricultural policy; agro-food economy; embeddedness; food policy; household production and intrahousehold allocation; marketing; relation of economics to social values; social economy

Globalization and Democracy: A New 'Great Transformation'? - Munck, Ronaldo (Annals of the American Academy of Political & Social Science, 2002)
Examines the relationship between democracy and development to set the scene for the pressing contemporary issue of how globalization might affect democracy and vice versa. Reference to the work of Karl Polanyi who posited a dual movement of market expansion matched by increasing social control over it; Impact of globalization.
Keywords: POLANYI, Karl, 1886-1964; democracy; double movement; economic development; globalization

The Great Depression and the Decline of Liberal Capitalism: Polanyi and Schumpeter - Trigilia, Carlo (Economic Sociology, 2002)
This chapter contains section titled: * Market Domination and Society's Self-Defense * The Decline of the Bourgeoisie and Anti-Capitalist Policies * Analytical Convergence and Political Divergence
Keywords: SCHUMPETER, Joseph Alois, 1883-1950; capitalism; depression; economic level; economic sociology; international relations; social conditions

Chapter 6: Our time - Heiskala, Risto (Will Europe Work?, 2001)
The article focuses on Europe in the age of global networks and flowing identities. In the article the author discusses the articulation of Europe. He starts with a discussion on the identity of Europe, goes on with a discussion of globalization and closes with an attempt to tie these two themes together. He then raises, in a new context, sociologist Karl Polanyi's question: "What Kind of a Time Is Our Time?" Throughout the article, specific emphasis is put on the European Union, as this network state currently uniting fifteen and in the nearest future possibly twice as many European states as today is often what is referred to combined with the term "Europe", even if it would be a mistake to believe that these two are identical. The article also throws light on the affect of Islam on the countries of Europe. In several European countries there are enclaves of millions of Muslim migrant workers and there are Muslim countries at the borders of Europe in North Africa and the Middle East.
Keywords: Europe; Islam; globalization; identity (philosophical concept); immigrants

Regulationist and Autopoieticist Reflections on Polanyi's Account of Market Economies and the Market Society - Jessop, Bob (New Political Economy, 2001)
This article re-interprets and develops Polanyi’s substantive institutionalist analysis of capitalist market economies and the market society in the light of two more recent approaches to the same issues. These are the Parisian ‘regulation school’ on contemporary capitalism and systems-theoretica l accounts of the modern economy. All three regard the capitalist economy (or, for autopoietic systems theory, the market economy) as an operationally autonomous system that is nonetheless socially embedded and needful of complex forms of social regulation. For each, an adequate account of economic activities should explore how they are related to the wider social environment; how they are embedded in a wider nexus of social institutions; how the latter assist in reproducing the capitalist (or market) economy; and how their development is coupled to that of these and other environing institutions. There are also some important differ- ences among these approaches, however, which enable an exploration of their respective limitations and also provide useful bases for further theoretical and empirical research. Thus, after presenting these three perspectives on the institutedness and embeddedness of economies. I consider some basic problems in analysing the improbable stability and reproducibility of the capitalist economy, paying particular attention to governance and meta-governance.
Keywords: capitalism; economics; market society; political economy; regulation school; substantive approach

Rural Community Life and the Importance of Reciprocal Survival Strategies - Meert, Henk (Sociologia Ruralis, 2000)
Although Belgian poverty is mainly concentrated in urban regions, the profound restructuring of labour and food markets, the dismantling of the welfare state and the growth of new types of households are also producing poverty and social exclusion in rural areas. This paper stresses that not every deprived rural household should be regarded as excluded from society. By developing survival strategies, households attempt to escape from social marginalization. To understand these responses, a typology of survival strategies is constructed, based on Polanyi’s spheres of economic integration (market exchange, redistribution and reciprocity). These survival strategies, including agricultural and non-agricultural activities, are analysed in relation to the Hageland,a peripheral rural area in Flanders. Based upon Doreen Massey’s geological metaphor, the current potentials and obstacles embedded in the historical layers of the socio-spatial structure of the area, are assessed. By comparing the results of this research with similar research amongst urban households, some particularities of rural poverty are distinguished.
Keywords: Belgium; economic integration; poverty; urban poverty

Sustainable Agriculture in the United States and France: A Polanyian Perspective - Barham, Mary Elizabeth (2000)
Keywords: France; social movements; sustainable agriculture

Three Pillars of Welfare State Theory: T.H. Marshall, Karl Polanyi and Alva Myrdal in Defence of the National Welfare State - Holmwood, John (European Journal of Social Theory, 2000)
Current social and political theory is sceptical of the future of welfare states in the face of global markets. Their moral claims, too, have been challenged by the neo-liberal association of market capitalism and individual freedom and by an implicit acceptance of that critique - of the welfare state as bureaucratic - by left-wing commentators. This article offers a defence of the national welfare state as the guarantor of 'complex freedom'. This defence is derived from the theoretical contributions of Marshall, Polanyi and Myrdal and offers a reconsideration of the debate immediately after the second world war over the welfare state and its relevance today. Marshall's concept of social rights has become a familiar part of our own debate, but it is argued that Polanyi provides the rigorous critique of market relationships which is missing, and Myrdal locates gender issues as central to the understanding of welfare state development and women's rights as integral to social rights.
Keywords: economic policy; gender; globalization; government policy; human rights; markets; public welfare; social & economic rights; social rights; welfare; welfare economics

Competing economic ideologies in South Africa's economic debate - Lazar, David (British Journal of Sociology, 1996)
This paper develops an analytical framework for the sociological analysis of the clash of economic ideologies. The framework is then used to make sense of the economic debate in South Africa in the 1990s. The argument is that, following Karl Polanyi, we must treat economic life as 'embedded' in social life; that is, economic action is a form of social action. However, the notion of 'embeddedness' must not blind us to the tendency in all economies, especially contemporary market economies, for economic motivations to become differentiated from the rest of our lives. Accordingly, the framework developed through a critique of key assumptions of neoclassical economic theory attends to both the embeddedness and the differentiation of the economic element. Having established a framework of analysis, I apply it to the debate in South Africa about the most relevant frame- work for economic policy in the post-Apartheid economy. The article traces the gradual move of the African National Congress (ANC) away from statist economics to a much more market-oriented policy and shows how this reflects the ANC leaders need to balance the demands of their constituency's (embedded) conception of rationality against the potential investor's more mainstream conception of economic rationality, which is itself embedded in prosperous communities with property and skills. A similar analysis is applied to the development of the economic policy of the ANC's rival, the former ruling National Party (NP). The NP advocates an economic policy framework based on an individual self- reliance and 'free' markets, that is, on an individualistic calculative rationality similar to that of the neoclassical textbooks. However, the NP too has to pursue politics and they, although rather differently from the ANC, have sought to reconcile individual maximizing rationality with the collective rationalities of the oppressed black communities in order to win maximum support.
Keywords: South Africa; South Africa - economic conditions; economic policy; social action; social classes; socioeconomics

Karl Polanyi’s ‘socialist accounting’ and ‘overview’ in the age of data analytics - Rief, Silvia (New Political Economy, 2022)
Digital capitalism’s information infrastructure is the subject of contentious debates concerning its transformative effects on the political economy and society. A frequent proposition, referring to older arguments of the ‘socialist calculation debate’, is that with big data analytics the pro-market arguments of neoliberal economists such as Hayek or Mises become obsolete. This article critically examines this proposition by drawing on Karl Polanyi’s notion of overview; a core theme in his outlines of a socialist economy and accounting written in the 1920s. In these contributions to the early Austrian socialist calculation debate, Polanyi discusses how to gain knowledge of the economic and social processes in such a way that the economy can be democratically governed according to its socialist aims and purposes. This article highlights the relevance of Polanyi’s work on socialist accounting, along with his later perspectives on technology and on social scientific method, for reflecting upon data- and algorithm-driven economic governance. Polanyi’s critical analysis of abstraction effected through methods of knowing suggests a sceptical stance vis-à-vis current versions of technological ‘solutionism’, which places its faith in data and algorithms as tools for economic and social, or socialist, planning.
Keywords: Karl Polanyi; accounting; data analytics; digital socialism; economic theory; overview; socialist accounting; socialist calculation

Planning laissez-faire: Supranational central banking and structural reforms - Braun, Benjamin; Carlo, Donato Di; Diessner, Sebastian (Zeitschrift für Politikwissenschaft, 2022)
The mandate of the European Central Bank (ECB) does not extend to labor market and social policies at the national level. Why, despite the reputational costs, did the ECB act as a staunch advocate of structural labor market reforms from 1999 through 2015? We discuss this question through the theoretical lens of Karl Polanyi’s The Great Transformation. Although Polanyi has been a key reference point for the debate on the social consequences of European economic and monetary integration, one of his key insights has received surprisingly little attention—that central banks have the power to mitigate the impact of international economic integration on domestic social protection. Polanyi regarded central banks—much like trade unions—as national-level institutions of non-market coordination, acting as a protective buffer against the functional pressures of the fixed-exchange-rate monetary regime that was the international gold standard. By contrast, the ECB, as a supranational central bank, embodies these functional pressures. This helps explain why, rather than protecting existing social structures against the logic of the fixed-exchange-rate monetary regime, the ECB has sought to protect the monetary regime by going out of its way to re-shape labor market institutions at the national level.
Keywords: European Central Bank; Europäische Zentralbank; Karl Polanyi; monetary integration; social protection; sozialpolitik; structural reforms; strukturreformen; wirtschafts- und währungsunion

Karl Polanyi and the Paradoxes of the Double Movement - Vail, John (Routledge, 2022)
This book offers a critical reconstruction of the double movement, the central thesis of Karl Polanyi’s The Great Transformation, one of the most influential books of the 20th century. The double movement is the establishment of a free market economy and the subsequent effort by society to ameliorate the destructive effects of the market. In Polanyi’s bold vision, the double movement constituted the hidden gear of social change and historical transformation within capitalism. The book is a forensic examination and critique of Polanyi’s argument. It develops an interpretive framework of the double movement as four interrelated social processes: the establishment of the self-regulating market, the rise of a market society that deepens and extends market imperatives, a social protection phase that constrains the market and safeguards society, and the contradictions and crises that result from this clash of social principles. The book will be an indispensable guide for students and scholars across the social sciences which illuminates the relevance of Polanyi’s insights to a critical understanding of the contemporary era –the scourge of insecurity and inequality, the multiple crises of neoliberalism, the rise of right wing populism- as well as those interested in egalitarian and emancipatory alternatives to capitalism.
Keywords: double movement; market society

The Greater Transformation: Digitalization and the Transformative Power of Distributive Forces in Digital Capitalism - Pfeiffer, Sabine (International Critical Thought, 2021)
This article discusses digitalization and its connection with the political economy of transformation. Its point of departure is Karl Polanyi's historical analysis as presented in The Great Transformation. Polanyi analyzed the development of “self-regulating” markets—with transformative and destructive consequences for individuals, nature, and society—and government efforts to contain these consequences. Polanyi's perspective is compared to Marx's theorem of the development of productive forces. Their respective focal points are different but complementary. For Polanyi, the decisive historical and theoretical break (and the cause of the destructive effects) lies in the act of purchasing human labor, whereas for Marx it lies in the act of producing value and in the relations of production as well as the relations of distribution linked to it. Working from this theoretical basis, current developments in digitalization are analyzed not as a further development within productive forces but as a transforming development of distributive forces. Following the logic of The Great Transformation, current developments should thus not be interpreted as a second great transformation but as the augmentation of the first, leading to a “greater” transformation associated with even more destructive potential. This leaves little hope for a smooth transition into any form of post-growth society.
Keywords: digital capitalism; digital transformation; distribution; political economy; productive forces

CAPITALISM, DEMOCRACY, AND SOCIAL THEORY IN KARL POLANYI: AN INTERVIEW WITH GARETH DALE - Santos, Rodrigo Salles Pereira dos; Onto, Gustavo Gomes (Sociologia & Antropologia, 2021)
Resumo Uma introdução à entrevista realizada com Gareth Dale (Brunel University) − economista político e especialista na trajetória e na obra de Karl Polanyi − e a um conjunto de textos inspirados na abordagem polanyiana publicados neste número de S&A. Recupera questões-chave apresentadas na entrevista e na obra de Dale, dando relevo à literatura recente produzida sobre o autor, à contínua e difundida relevância das ideias de Polanyi para a compreensão do capitalismo e da democracia, e a uma leitura crítica e aberta de suas contribuições teóricas. Divulga as contribuições específicas, teóricas e empíricas, de quatro artigos originais que mobilizam ativamente conceitos polanyianos no entendimento da pluralidade dos processos de enraizamento e das dinâmicas do movimento duplo, de mercantilização da terra e do trabalho, e da centralidade da praça de mercado no capitalismo contemporâneo; além dos aportes de um registro de pesquisa e duas resenhas sobre agências e pedagogias econômicas e financeirização da vida cotidiana. An introduction to the interview with Gareth Dale (Brunel University) − a political economist and expert on Karl Polanyi’s life and work − and to a set of papers, inspired by the Polanyian approach, published in the current issue of S&A. The paper highlights key questions presented in the interview and in Dale’s work, with a focus on the recent literature produced about the author, the continuous and widespread relevance of Polanyi’s ideas for the understanding of capitalism and democracy, and a critical and open reading of his theoretical contributions. Next, the paper presents the specific contributions, both theoretical and empirical, of four original papers that actively dip into Polanyian concepts in understanding the plurality of the embeddedness processes and the dynamics of the double movement, the commodification of land and labor, and the centrality of the marketplace in contemporary capitalism; as well as the contributions of a research recording and of two book reviews on economic agencies and pedagogies and the financialization of everyday life.
Keywords: DALE, Gareth; Karl Polanyi; capitalism; democracy; market

On the meaning and contemporary significance of fascism in the writings of Karl Polanyi - Millett, Kris (Theory and Society, 2021)
This paper assesses the contribution of Karl Polanyi, a theorist largely ignored in fascism scholarship, toward understanding fascism’s interwar rise and present-day implications. In exploring Polanyi’s work in The Great Transformation and lesser-known and unpublished writings, a sophisticated and largely original conception of fascism emerges, rooted in the idea of ‘anti-individualism’ as its foundational trait. Polanyi accounts for fascism’s philosophical content, ideological plasticity, political function and societal form, intervening in debates over how to define fascism, its ambiguity with the populist far-right, and on its both economically reactionary and socially revolutionary qualities. Polanyi’s analysis suggests an enduring vulnerability on the part of liberal capitalism to fascist currents as (1) a solution to the instability of the market economy (and broader incompatibility between capitalism and democracy) at the systemic level, and (2) to the crisis of the individual subject on a social and moral level. I end by considering how Polanyi’s theory might be applied to locate current neo-fascist movements and elucidate the sociological problems underpinning their existence.
Keywords: Anti-individualism; Fascism; Neo-fascism; Polanyi; Totalitarianism; Vitalism

Karl Polanyi: a theorist of mixed economies - Szelényi, Iván; Mihályi, Péter (Theory and Society, 2021)
Karl Polanyi’s scholarship is interpreted in radically different ways. The “hard” reading of Polanyi sees him as a radical socialist; the “soft” reading presents him as a theorist of mixed economy. This article sides with the soft interpretation. It uses Polanyi’s biography to explain his theoretical “elusiveness,” presents a novel interpretation of his three types of economic integration, claiming all economies are “mixed.” While it acknowledges Polanyi as one of the major sources of world system theory, it claims that Polanyi saw not only the dangers, but also the necessity and positive consequences of globalization. Finally, it shows that, in spite of Polanyi’s life-long commitment to the political left, his scholarly work did not offer an apology of socialism. Instead this article uses Polanyi’s theory of economic integration to build a critical political economy of state socialism.
Keywords: capitalism; reciprocity; redistribution; rent-seeking; socialism; world system theory

Going public with Polanyi in the era of Trump * - Burawoy, Michael (The Routledge International Handbook of Public Sociology, 2021)
After considering different possible elements of the ‘Trump era,’ I will turn to The Great Transformation to periodize capitalism into three waves of marketization and their counter-movements. In the first wave, we follow the commodification of land, money and especially labor, so-called fictitious commodities, and the local counter-movements marketization inspired, reaching to the level of the state. In the second wave, the focus turns on the way marketization generated a reaction from states, seeking to regulate commodification – in other words, processes of de-commodification. Given the tension between capitalism and democracy, in Polanyi’s view essentially two forms of regulation were possible: either democracy suppresses capitalism and we get socialism, or capitalism suppresses democracy and we get fascism. He neither paid much attention to the popular forces that led in either direction nor to the possibility of a compromise between capitalism and democracy that reigned in three decades after World War Two. Beginning in the 1970s, we witnessed the beginning of a third wave of marketization – more commonly known as neoliberalism – that Polanyi did not anticipate. I attribute his failure to anticipate another wave of marketization to the contradictory pressures of accumulation that are temporarily alleviated by commodification. In this third wave, I show how democracy is discredited, and consensus politics dissolves into polarizing movements within and beyond parliamentary politics. The lived experience driving these movements, I argue, revolves around processes of re-commodification and ex-commodification of nature, money, labor and knowledge. This is the terrain upon which sociology must engage its publics. I highlight two approaches, both founded on an organic public sociology that engages directly with publics. On the one hand, there is the empathic public sociology that wades into communities in order to comprehend the distinctive ‘deep narrative’ of right wing populism, typified by Arlie Hochschild’s Strangers in Their Own Land. On the other hand, there is the affirmative public sociology that creates a collective vision based on a dialogue with the practitioners of real utopias, typified by Erik Wright’s How to Be an Anti-Capitalist in the Twenty-First Century.
Keywords: Trumpism; marketization; public sociology

Fascism and the enduring problem of the liberal individual in Polanyi - Millett, Kris (Dewey Studies, 2021)
This application of Polanyi to the question of fascism’s resurgence provides an important corrective to mainstream liberal explanations (e.g., Albright 2018), inviting the reader to “look up rather than down” (Lim 2021) by tying fascism’s significance to the functioning of the capitalist system rather than to the personalities of fascist politicians or their degree of mass support. The merits of this notwithstanding, I argue that current Polanyian treatments have neglected to engage with a core aspect of Polanyi’s theory, which is that fascism, at its roots, is a fundamentally anti-individualist ideology that aims to address a moral and social crisis of the individual subject in liberal capitalism. Omitting this risks obfuscating what makes fascism distinctive as well as why its ideas have retained their appeal.
Keywords: essence of fascism; fascism; individualism

Ecology, Democracy, and COVID-19: Rereading and radicalizing Karl Polanyi - Ryan, J. Michael (COVID-19: Volume I: Global Pandemic, Societal Responses, Ideological Solutions, 2020)
The SARS-CoV-2 virus, and the associated COVID-19 pandemic, is perhaps the greatest threat to life, and lifestyles, the world has known in more than a century. The scholarship included here provides critical insights into the ethics and ideologies, inequalities, and changed social understandings that lie at the heart of this pandemic. This volume maps out the ways in which the pandemic has impacted (most often disproportionately) societies, the successes and failures of means used to combat the virus, and the considerations and future possibilities – both positive and negative – that lie ahead. While the pandemic has brought humanity together in some noteworthy ways, it has also laid bare many of the systemic inequalities that lie at the foundation of our global society. This volume is a significant step toward better understanding these impacts. The work presented here represents a remarkable diversity and quality of impassioned scholarship and is a timely and critical advance in knowledge related to the pandemic. This volume and its companion, COVID-19: Volume II: Social Consequences and Cultural Adaptations, are the result of the collaboration of more than 50 of the leading social scientists from across five continents. The breadth and depth of the scholarship is matched only by the intellectual and global scope of the contributors themselves. The insights presented here have much to offer not just to an understanding of the ongoing world of COVID-19, but also to helping us (re-) build, and better shape, the world beyond.
Keywords: COVID-19; disease & health Issues; health

Polanyi meets Bolsonaro: Reactionary politics and the double movement in twenty-first-century Brazil - Evans, Peter (International Sociology, 2020)
Twenty-first-century Brazil’s political evolution is a window on the dynamics of contemporary political transitions. The inability of Brazil’s Workers’ Party to sustain its social democratic project and the subsequent rise of the reactionary regime of Jair Bolsonaro are, in turn, part of a global pattern of political change. Karl Polanyi’s vision of the ‘double movement,’ in which the dominance of the market vies with the countervailing movement for social protection, offers an analytical springboard for reflecting on these political transitions. Trying to understand the movement for social protection leads to examining ebbs and flows in the momentum of mobilization. Trying to understand how market dominance leads to reaction brings us back to Polanyi’s advocacy of ‘crass materialism’ as a lens for looking at reaction, and from there to consideration of how the structural power of capital undercuts efforts at social protection and opens the door to reaction.
Keywords: Brasil; Brazil; Brésil; Polanyi; finance; finanzas; protección social; protection sociale; reacción; reaction; réaction; social protection

This freedom kills: Karl Polanyi’s quest for an alternative to the liberal vision of freedom - Brie, Michael (Karl Polanyi and twenty-first-century capitalism, 2020)
The chapter reconstructs the emergence and formulation of Karl Polanyi's central research question: How is responsible freedom possible in a complex modern society? The origins of this question in the time before the First World War and the confrontations with the challenge of neoliberalism and fascism are discussed. It is shown that Karl Polanyi's concept of freedom has four dimensions. Polanyi connects negative, positive, substantial and social freedom with each other and formulates a highly innovative research programme which forms the basis for The Great Transformation and later works.
Keywords: freedom; freedom in a complex society

Commodified money and crustacean nations - Desai, Radhika (Karl Polanyi and twenty-first-century capitalism, 2020)
Though Polanyi referred to three distinct fictitious commodities, one, money, and the fate of the apex structure that commodified it, the gold standard, structured The Great Transformation’s narrative. Despite this centrality of money and its commodification to Polanyi’s masterwork, there is near-deafening silence in Polanyi scholarship on money as a fictitious commodity. This chapter ends it. It traces Polanyi’s understanding of fictitious commodities to its sources in classical political economy and explains how the near total dominance of the antithetical tradition of neoclassical economics obscures understanding. The chapter also argues that the resulting argument shared a great deal with the classical Marxist theories of imperialism and of uneven and combined development of previous decades, particularly their arguments about the centrality of powerful nation states to capitalism. It stresses another hitherto neglected aspect of Polanyi’s argument, that the double movement led to the emergence of ‘crustacean nations’. As such, the chapter argues, The Great Transformation contributes a great deal towards a new approach to understanding world affairs, geopolitical economy, which challenges Ricardian ‘universalist’ understandings and takes the ‘materiality of nations’ seriously. It, and Polanyi, are more relevant than ever in our ‘deglobalizing’ age of multi-polarity.
Keywords: Marxism; fictitious commodities; imperialism; money

Introduction: Karl Polanyi in the twenty-first century - Desai, Radhika (Karl Polanyi and twenty-first-century capitalism, 2020)
This introduction places the contributions that follow in the context of Polanyi’s rising influence, its causes and effects, and of the key twenty-first century developments that make his oeuvre more relevant than ever. It emphasizes how the contributions push the boundaries of received understandings of Polanyi. While some contributions fill gaping holes, such as those on money as a fictitious commodity, others overturn received understandings, whether that of the double movement or fictitious commodities, or the provenance (Central European or American) of his principal ideas and concerns or how he understood socialism. Yet others demonstrate how amenable Polanyi’s ideas are to further development. Last but not least, the introduction outlines Polanyi’s historical diagnosis as it emerges from these innovative contributions and argues that the stark choice he felt faced European societies, socialism or fascism, is once again before us as we face the groundswell of nationalist and far right forces.
Keywords: capitalism; contemporary relevance; fascism; socialism

The reality of society - Rotstein, Abraham (Karl Polanyi and twenty-first-century capitalism, 2020)
In these remarkably stirring reflections, delivered at the 2014 conference from which most of the contributions to this volume emerge, the late Abe Rotstein, Polanyi’s student and collaborator, recalls the projected sequel to The Great Transformation, to be titled Freedom and Technology. Whereas the former was built on a social sciences approach using institutional analysis, the sequel was to follow the intention Hegel expressed in the words ‘Wir die religiöse Vorstellung in Gedanken fassen’ (We want to turn religious expression into philosophical thought). Polanyi took religion seriously – not its outer ceremonial trappings but the important truths that lay behind and beneath these beliefs and practices. The sequel was to trace humanity’s progression through three major revelations: the knowledge of death, the discovery of our inner life and conscience, and the realization of freedom amid our social obligations. This was the idea of ‘the reality of society’ around which the whole book was to be built. It was the precursor of our cherished civil freedoms and closely connected with Polanyi’s idea of freedom in a complex society; it is also deeply threatened in an age of state and corporate cyber surveillance.
Keywords: freedom; reality of society; technology

Fictitious ideas, social facts and the double movement: Polanyi’s framework in the age of neoliberalism - Thomasberger, Claus (Karl Polanyi and twenty-first-century capitalism, 2020)
In the last decades, Karl Polanyi has gained recognition as one of the most important social scientists of the twentieth century. His seminal book, The Great Transformation, is listed among twentieth- century classics. How can this book, written more than seventy-five years ago, be applied to the current conditions? In order to answer this question the chapter not only compares the civilization of the nineteenth century in Europe with our own epoch. It also reconstructs some of Polanyi’s most important insights, such as his critique of the liberal utopia (in its classical and neoliberal version), his interpretation of the double movement, his vision of the meaning of the industrial revolution, his understanding of the problem of freedom in a complex society and his idea of a necessary ‘reform of human consciousness’. The chapter closes with a discussion of the question of how Polanyi’s categories can be used fruitfully so as to throw light to the post-war era and our society today.
Keywords: Great Transformation, The (Book); double movement; freedom in a complex society; liberal utopia; social facts

The Contemporary Relevance of Karl Polanyi to Critical Social Enterprise Scholarship - Roy, Michael J.; Grant, Suzanne (Journal of Social Entrepreneurship, 2020)
The importance of the work of Karl Polanyi to social enterprise scholarship is often maintained. However, explanations as to how and why his ideas are so relevant to the field are still relatively scarce. In this essay, we argue that engaging with Polanyi’s work directly, and Polanyian scholarship more widely, can provide a deep understanding of the underlying assumptions within current social enterprise conceptualizations, and provide insights into how the relative positioning of market and society may be manipulated to maintain hegemonic positions. Three of Polanyi’s key concepts are considered and discussed in turn: the ‘substantive economy’, the notion of ‘embeddedness’, and his ‘double movement’ thesis. The contemporary relevance of each concept, and the implications for future research, are presented and discussed, with a view to providing a platform from which to pursue a reinvigorated, emancipatory critical research agenda.
Keywords: Polanyi; Social enterprise; critical research; critical social enterprise scholarship; double movement; economic sociology; embeddedness; social business; social enterprise; social innovation; substantive economy

Embedding the atom: Pro-neoliberal activism, Polanyi, and sites of acceptance in American uranium communities - Malin, Stephanie A.; Alexis-Martin, Becky (The Extractive Industries and Society, 2020)
In North America, uranium workers are fighting for their right to participate in a free-market system that provides them with small personal benefits. These workers experience powerlessness, instability, and unpredictability – or social dislocation – by living amidst capitalism’s polluted ecosystems, unstable economies, and disintegrating communities. However, they feel reliant on uranium for their livelihoods and strongly support the industry’s renewal and form sites of acceptance to support industry renewal. Here, we explore the phenomenon of pro-neoliberal activism emerging in communities that identify with uranium markets and that trust in corporate self-regulation, private transparency, and the perceived benefits of potential economic development. Polanyian theory helps us analyze these curious socio-environmental outcomes. While social movements might be ‘progressive,’ ‘regressive,’ or otherwise diverge, Polanyi consistently characterized double movement activists as protecting communities and ecosystems from unstable, self-regulating market systems. But here we see something different and ask: First, how does pro-neoliberal activism contribute to the embedding and institutionalization of neoliberal regimes in uranium mining communities? Second, what structural mechanisms precede and help to facilitate socio-cultural support for free markets and corporate self-regulation, as opposed to support for re-embedding markets in local, public social protections for the US uranium industry?
Keywords: double movement; environmental justice; pro-neoliberal activism; uranium

Polanyi, Callon, and Amazon: Institutionalist, ANT, and DRAN Approaches to Platform Economies - Caliskan, Koray (Sociologica, 2020)
Drawing on a detailed analysis of Grabher and König’s study of platformization (Grabher & König, 2020), this essay develops a revision of Actor-Network Theory by proposing how a Device, Representation, Actor and Network or a DRAN Approach can be more helpful in making sense of platform economic processes. First, it locates the ways in which Grabher & König’s article approach platforms from an updated Polanyian perspective. Second, it elaborates on how the aforementioned article critiques static Polanyian perspectives while at the same time building a double tension by a) not being clear whether we observe "the platform economy" as an object or platform economization as a process, and b) not paying sufficient attention to how platforms that draw on intangible materialities move beyond being mere marketization relations. Third, it presents how to address these tensions by drawing on novel theoretical advances of DRAN Approaches and fresh empirical research concerning platform economies, located at the intersection between computer science and social sciences. Proposing a possibility to integrate historical and contemporary studies of economic processes, the essay ends by elaborating on how Grabher & König’s article has a potential to enable a multi-perspective dynamic research strategy in making sense of not only the contemporary working of platforms, but their historical and socio-technical condition of possibility.
Keywords: CALLON, Michel; Platform economy; Polanyi; actor-network theory; platform

Ecology, democracy, and COVID-19: Rereading and radicalizing Karl Polanyi - Duzgun, Eren (Ecology, democracy, and COVID-19, 2020)
This chapter argues that Karl Polanyi’s economic sociology offers foundational concepts for a radical analysis of the social and ecological conditions that have caused the coronavirus pandemic. Furthermore, it shows that Polanyi’s work, often claimed for social democracy, has the potential to provide much more radical insights into the question as to how to “re-embed” our economies, thereby leading to a fundamental rethinking about the ways in which the present crisis can be overcome.
Keywords: COVID-19

State Formation, Habitus, and National Character: Elias, Bourdieu, Polanyi, and Gellner and the Case of Asylum Seekers in Ireland - Loyal, Steven; Quilley, Stephen (Historical Social Research, 2020)
Synthesizing material derived from Norbert Elias, Pierre Bourdieu, Karl Polanyi, Max Weber, Benedict Anderson and Ernest Gellner, in Part I the concept of “national character” is delineated as a special case of “habitus” relating to the socio-spatial scale of the nation state. In relation to problems of state-formation, national character is shown to be a figurational and co-developmental function of the system of nation-states in which patterns of mutual identification and “imagined community” involve both the coercive codification and internalization of particular national narratives and origin myths which define “people like us” in terms of a symbolic family; and also, in relation to competing nation-states, the projection and internalization of national group charisma and shame. In Part II, these ideas are applied to the pattern of state formation in Ireland and the recent history of the reception, cultural accommodation, and treatment of asylum seekers.
Keywords: BOURDIEU, Pierre, 1930-2002; ELIAS, Norbert; Ireland; Irishman; Kultur; Sozialpsychologie; Staatenbildung; culture; figuration; habits; habitus; nation; national identity; national stereotype; nationale Identität; nationales Stereotyp; social psychology; state formation

Karl Polanyi and the Global Network Inspired by His Work - Mendell, Marguerite; Aulenbacher, Brigitte; Novy, Andreas (Österreichische Zeitschrift für Soziologie, 2019)

Cucumbers and Courgettes: Rural Workfare and the New Double Movement in Hungary - Hann, Chris (Intersections. East European Journal of Society and Politics, 2016)
The paper is an application of the economic anthropology of Karl Polanyi to contemporary rural Hungary. After addressing the influence of Polanyi’s critique of market society and his standing in the discipline of anthropology, the main focus is the community of Tázlár on the Danube-Tisza interfluve. The paper traces the history of the ‘fictitious commodities’ of land and labour in this relatively isolated settlement, which was not fully integrated into the national society until the socialist era. The innovative symbiosis of household and cooperative farming was destroyed in the 1990s. In the depressed economic climate of today, workfare schemes are popular because they treat villagers as human beings rather than as commodities to be exploited for maximum profit. The workfare initiatives of populist power holders can be interpreted as one facet of a complex ‘double movement’ in which postsocialist society seeks to defend itself against the domination of the market.
Keywords: (post)socialism; Danube-Tisza interfluve; Hungary; Karl Polanyi; double movement; fictitious commodities; neoliberalism; workfare

Embeddedness, Redistribution and Double Dependence: Polányi-reception Reconsidered - Lengyel, György (Intersections. East European Journal of Society and Politics, 2016)
This article – a modified version of a lecture – is a contribution to the reception of Polányi in the West and the East, more precisely, to the inquiry about what impact Polányi’s views have had on American and Hungarian economic sociology, which are the contact points between the two, and what research perspectives they offer. It concentrates on the perception of embeddedness and redistribution, not touching on other views unless they are conducive to the comprehension of certain connections. Polányi’s oeuvre is so rich and it has inspired such a wide range of debates that a conclusive review is impossible within a single article. It is hoped however that the polemic on the concept of embeddedness may be illuminating and also the aftermath of the forms of integration, particularly redistribution, important. The concept of double dependence is touched upon as well, for it grasps an essential feature of the post-socialist Eastern European economies. It is worth mentioning it in this context, for Polányi’s influence left its mark upon it and it is also related to the conceptual apparatus of the substantive view.
Keywords: Polányi; dependent market economy; double dependenc; embeddedness; fictitious commodities; forms of integration; post-socialist transformation; redistribution; state socialism; varieties of capitalism